Dominant circulation patterns influencing the tropical night in the East Asian monsoon region - Ruidan Chen; Wenting Lin; Siao Tang; Lan Wei (Atmospheric Research, 2026)

Life history strategy composition of fishes in the Yangtze River Basin and their response to the Ten-Year Fishing Ban - Lan Zhu; Dan Yu; Pengcheng Lin; Fei Liu; Tao Chang; Xin Gao; Mingzheng Li; Huanzhang Liu (Reviews in Fish Biology and Fisheries, 2026)

The role of immune cell crosstalk and signaling pathways in the pathogenesis of pulmonary fibrosis - Xia Liu; Haixu Chen; Changying Guo; Yu Lin; Fei Wang; Zhi Lan (Molecular Biology Reports, 2026)

High spatial variations of potential nitrification and N2O production across the Yangtze River and associated major tributaries - Caixia Lan; Qiuxun Lin; Mengting Qi; Yuxuan Fu; Guosen Zhang; Ye Li; Min Liu; Lijun Hou; Xiaofei Li (Water Research, 2026)

Early-life supplementation of bovine Milk Osteopontin prevents adult obesity by elevating succinic acid and acting through its receptor GPR91 - Lan Liu; Yilei Lao; Zixin Zhang; Chenming Lin; Yeqing Zhou; Zhimin Zhang; Bo Lönnerdal; Zhijian Cai; Junfen Fu (Food Research International, 2026)

The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Endocrine-disrupting chemical-induced gene networks confer coronary heart disease risk revealed by causal inference and single-cell analyses - Tao Yao; Yun-Lu Lin; Luo-Xiang Fang; Yu-Tian Wang; Lan-Feng Zhou; Ning Zhang; Gang Chen (Food and Chemical Toxicology, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

Quasi-static cyclic tests of innovative prefabricated CFST bridge piers with replaceable components - Zhehan Cai; Jianguang Lin; Ying Sun; Pengcheng Xu; Zhiyu Lan; Kaiqi Lin; Weidong Zhuo (Engineering Structures, 2026)

High-temperature resistant homogeneous imidazolium functionalized poly (phthalazinone ether sulfone) anion exchange membranes for electrodialysis - Fanchen Sun; Qian Liu; Lin Zhuo; Xuefu Che; Peng Shi; Weiwei Kong; Yiping He; Hongyuan Lu; Lan Gong; Shouhai Zhang; Xigao Jian (Desalination, 2026)

Multifunctional CaO-enabled persulfate activation for pentachlorophenol degradation in contaminated soil: Calcium-mediated transformation and oxidative enhancement - Dawei Lan; Ping Liu; Fengjiao Zhang; Jiang Lin; Ying Ran; Wan Cheng; Jing Chen; Xiaohui Wu; Anxu Sheng; Linling Wang (Journal of Environmental Chemical Engineering, 2026)

Food-derived extracellular vesicles modulate ferroptosis: Implications for functional food development and healthy aging - Lin Zhang; Wangying Qiu; Mingrun Lu; Shuting Lan; Zuokai Lv; Haiyan Zhang; Yue Pang; Xingcan Zhang; Wenjing Xu; Haitao Wang; Jiahui Liu; Jiahui Ma; et al. (Food Research International, 2026)

Effect of pandan leaf (Pandanus amaryllifolius Roxb.) powder on the rheological, gel and structural properties on corn starch hydrogel for 3D printing - Yalei Lan; Jieqiong Lin; Yuhan Jiang; Chenyu Zhang; Chunling Que; Xianxiang Chen; Chuan Li; Kexue Zhu; Jun Yang (Food Chemistry, 2026)

Self-sustaining slab dynamics of the underthrusting Indian lithosphere shaping the giant Himalayan Orocline - Chunsen Li; Hengcheng Ying; Xiao Xu; Xiaoyu Guo; Xiaofei Tong; Lingyan Li; Hongcheng Shi; Zizhao Yuan; Yanqi Lin; Xinglang Yin; Huolong Xu; Xiaodong Lan (Earth-Science Reviews, 2026)

Interaction effects of Micropterus salmoides and Edwardsiella piscicida under ammonia nitrogen and nitrite stress - Changyi Lin; Biao Jiang; Jiahao Zhang; Wenhao Wu; Yuan Liang; Xuerou Lan; Jianshan Bai; Youlu Su (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Carboxylate-driven interfacial regulation via polyacrylic acid additive for stable magnesium metal batteries - Bo Li; Hui Miao; Jiu-Xi Dong; Meng-Qi Zhu; Song-Lin Li; Cheng-Bao Liu; Fen Zhang; Shuo-Qi Li; Lan-Yue Cui (Chemical Engineering Journal, 2026)

Sustained-release salt reservoir enables durable solid electrolyte interphases for practical micron-sized silicon composite anodes - Kui Lin; Junke Wu; Zhengguang Song; Yuling Yi; Fuxi Peng; Shiwen Wang; Zhimin Zou; Tongbin Lan; Junxiong Wu; Chunhai Jiang (Chemical Engineering Journal, 2026)

Efficient biosynthesis of limonene from sugarcane molasses using engineered yeast - Shengliang Cai; Xiaoyuan Wang; Jingtao Zhou; Chengcheng Yuan; Xiaoling Lin; Lan Wei; Dongying Chen; Pingxu Chen; Chaoyi Zhu; Shuang Li (Biomass and Bioenergy, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Assimilatory sulfate reduction potential in the plastisphere microbiome is linked to plastic mineralization in sulfur-rich mining-impacted river sediments - Tianle Kong; Zhili Du; Jianhua Zhou; Zhihao Zheng; Jian Zhang; Shui Zhang; Feng Jiang; Xiaoxu Sun; Wei Huang; Ruijian Zhang; Fangbai Li; Wenjie Lin; et al. (Water Research, 2026)

Unveiling the electrochemical reduction pathway of manganese release in drinking water distribution systems: A galvanic cell perspective on colored water risks - Tanyu Li; Dibo Liu; Luyao Kang; Jialiang Lan; Jun Wang; Gang Wen; Shuguang Xie; Lin Deng; Chao Chen (Journal of Hazardous Materials, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

Spatiotemporal multiscale quantitative evaluation of formation damage during drill-in operations in deep fractured tight reservoirs based on geoscience-engineering integration - Chong Lin; Yili Kang; Lan Wang; Hai He; Gao Li; Hongling Zhou (Geomechanics for Energy and the Environment, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Integrated plasma proteomics and metabolomes reveal potential biomolecules linking PM2.5 to depression - Lan Chen; Dashan Zheng; Shengtao Wei; Ge Chen; Yang Shen; Leiyuan Liu; Hualiang Lin (Environmental Toxicology and Pharmacology, 2026)

Synergistic Li/cu co-doping in Fe/Mn-based layered oxides for elevated voltage and activated anionic redox for high-energy sodium-ion batteries - Jiajun Cai; Yihong Lan; Zhuoyuan Li; Yubin Hong; Guoming Lin; Huihui Lin; Chen Wang; Weiguang Lan (Chemical Engineering Journal, 2026)

Materials-centric protein corona design in polyurethanes for pro-regenerative immune modulation and soft tissue repair - Jingjing Lin; Mingtao Luo; Haonan Qi; Xue Wu; Junhong Li; Yuan Feng; Zhen Li; Feng Luo; Jiehua Li; Hong Tan; Ting Lan; Yanchao Wang (Chemical Engineering Journal, 2026)

Fe(II) complexation-regulated iron allocation supports coupled nitrogen and phosphorus removal in an anammox-FePs granular system - Lan Lin; Xiaohua Wang; Qian Zhang; Ying Song; Xiaojun Wang; Shaohua Chen; Wenzhi Cao; Yanlong Zhang (Bioresource Technology, 2026)

Effects of size-specific particulate matter on acute lower respiratory infection in children under 3 years of age: A ten-year time-series study in Foshan, China - Linping Chen; Jiayi Liang; Zihan Lin; Zitong Zhuang; Lan Chen; Xiaojie Wang; Xiangming Zhong (Atmospheric Environment, 2026)

Characterization and classification of a novel bacteriophage, vB_RsoP_HXg1W, infecting Ralstonia pseudosolanacearum: a new member of the genus Serkorvirus in the family Autotranscriptaviridae - XiaoLi Yu; Zheng Fang; Qingshan Wu; Rui Wu; Chuangen Lin; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2026)

miR-4632-5p Alleviates Lumbar Disc Degeneration by Targeting MAP3K11: A Novel Role in Mitigating Nucleus Pulposus Cell Degeneration - Xinfei Lan; Haiyan Xue; Mianlong Lin; Jinxiang Zhang; Qingfeng Zhang; Canhua Xu (Biochemical Genetics, 2026)

An Analysis of Growth Characteristics and Population Dynamics of Cynoglossus gracilis in the Offshore Waters of Liaoning Province, China - Lin Zhang; Yingyou Zhou; Zengqiang Yin; Qifa Zhang; Yikai Lan; Quan Yu; Jiahang Wei; Fan Du; Lei Chen (Fishes, 2026)
This study investigated the population dynamics of Cynoglossus gracilis in the offshore waters of Liaoning Province, China, to support sustainable fisheries management. Biological samples were collected from five major fishing ports between March and November 2024. Population dynamics were assessed based on growth, mortality, and exploitation parameters, and four seasonal fishing closure scenarios were evaluated using egg production per recruit (EPR) and spawning biomass per recruit (SBR) models. The estimated exploitation rate (E = 0.53) indicated that the stock was experiencing relatively high fishing pressure but remained close to the sustainable exploitation reference level. Yield-per-recruit analysis suggested that increasing the minimum catchable size could improve resource utilization efficiency. Among the evaluated closure scenarios, the April–September closure provided the greatest conservation benefit by enhancing reproductive potential and protecting spawning stock biomass. These findings provide valuable insights for optimizing harvest regulations and seasonal closure strategies, contributing to the sustainable management of Cynoglossus gracilis resources in the offshore waters of Liaoning Province.

The cortical morphology of cingulate cortex and microarchitecture of cingulum bundle correlate with cancer pain and anxiety in lung cancer patients - Lin Tang; Xiaosong Lan; Xiaoyu Zhou; Yu Tang; Jiahui Zheng; Junhao Huang; Yong Tan; Jing Zhang; Hong Yu; Meng Lin; Hua Lan; Xinying Ren; et al. (Brain Imaging and Behavior, 2026)

Hydrogen oxidation coupled to dissimilatory arsenate reduction: A potentially widespread pathway associated with arsenic mobility in anoxic sediments - Duanyi Huang; Xiaoxu Sun; Wenjie Lin; Xiaolong Lan; Zewen Tan; Youhua Ren; Ying Huang; Yubo Cao; Weimin Sun (Water Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Metabolic rewiring and transcriptional interference underlie the biocontrol efficacy of Burkholderia arboris BB417 against Ralstonia solanacearum species complex - Shanwen Ding; Juan Zhang; Yang Wang; Guobing Lan; Lin Yu; Yafei Tang; Zhenggang Li; Bin Guo; Zifu He; Xiaoman She (Pesticide Biochemistry and Physiology, 2026)

CsMYB6 promotes crocins biosynthesis in response to JA signaling in Crocus sativus L - Shiyu Wang; Chuyu Lin; Xingyun Shi; Aicun Zhou; Ting Chen; Ying Zheng; Qingsong Shao; Lei Zhang; Lan Ding; Bingcong Xing (Journal of Plant Physiology, 2026)

Iron ores with contrasting redox properties drive iron biogeochemical cycling to enhance acesulfame and nutrients removal in constructed wetlands - Mingjun Li; Zhiyi Lin; Peihao Yan; Tianzhi Lan; Jian Zhang; Huijun Xie; Haiming Wu (Journal of Hazardous Materials, 2026)

Short-, medium-, and long-chain chlorinated paraffins in human serum from South China: Evidence of LCCP exposure and CP substitution - Weifeng Ruan; Jinling Peng; Xi He; Jiayi Song; Xiaozhen Zhang; Yuan Liu; Rongjie Shi; Lan Zhuo; Xiaoshi Lin; Guangshan Xie; Min Hu; Yousheng Jiang; et al. (Journal of Hazardous Materials, 2026)

Radio frequency-enhanced remediation of PAHs-contaminated soils using peroxydisulfate: Performance and mechanistic insights - Wenhao Qi; Anxu Sheng; Dawei Lan; Zezhou Zhao; Yao Shi; Fengjiao Zhang; Jiang Lin; Ying Ran; Wei Lou; Jing Chen; Xiaohui Wu; Linling Wang (Journal of Environmental Management, 2026)

The luxury effect under environmental filtering: Drivers of residential plant diversity in 15 high-altitude cities - Yao Yao; Zhiwen Gao; Lin He; Luyi Lan; Xiaoya Yu; Ruishen Yang; Junwei Wang; Yuandong Hu; Qiong La; Liangjun Da (Journal of Environmental Management, 2026)

Soil quality degradation induces synergistic evolution of carbon components: Microbial extracellular polymeric substances - driven mechanism - Renjie Hou; Sisi Liu; Anshuang Su; Miao Wang; Hai Wang; Sen Lin; Xin Zhao; Xu Leng; Jian Zhang; Lan Luo; Chunjiao Wang (Journal of Environmental Management, 2026)

Differential correlation analysis of gas products and active groups reactions in coal oxidation and pyrolysis - Xiaoyuan Jiang; Lin Lan; Shengqiang Yang; Buzhuang Zhou; Jiawen Cai (Fuel, 2026)

Operational stabilization of high-rate partial denitrification-anammox using intermittent low-speed stirring in an expanded granular sludge bed reactor - Zibin Luo; Lan Lin; Weizhe Xia; Yu-You Li (Chemical Engineering Journal, 2026)

Remediation of composite groundwater contaminants in petrochemical sites via lab-scale permeable reactive barriers - Jintong Lan; Xi Cai; Lijun Qiu; Yang Lin; Zhihui Ai; Xiao Liu (Chemical Engineering Journal, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

Influence of Pollution Source Geometry on Groundwater Copper Transport under Tailings Leakage Scenarios - Si-Chen Wu; Guo-Qin Lin; Xiao-Cong Lan; Jing Zhang; Shi-Tao Peng; Zi-Jing Chen (Water, Air, & Soil Pollution, 2026)

Portable Upper-limb Muscle Tone Assessment by Integrating Multi-sensor Signals - Yue Zhang; Ying Zheng; Hao ShangGuan; Ting Chen; Wan-Zhu Wang; Ya-Lan Wang; Peiqiang Lin; Bingwei He; Wenyao Hong; Xin-Yuan Chen (Annals of Biomedical Engineering, 2026)

Data-driven outcome prediction and rational resource allocation in severe traumatic brain injury: a multicenter retrospective study integrating survival analysis and machine learning ensembles - Shuyue Li; Xingzhi Liu; Jun Lei; Hao Lin; Min Li; Seidu A. Richard; Zhigang Lan; Ling Feng (Acta Neurologica Belgica, 2026)

Synergistic foliar application of zinc and manganese reduces Cd accumulation in rice by enhancing leaf sequestration and modulating Cd transporter gene expression - Chang Li; Hang Zhou; Xia Zhou; Peng Zeng; Lin Song; Lan-Xin Ma; Jiao-Feng Gu (Plant and Soil, 2026)

Targeting eIF5A2 hypusination with bikinin sensitizes hepatocellular carcinoma to lenvatinib by suppressing TFEB-mediated autophagy - Shuqian Wang; Qingyun Zhou; Qiaomei Lin; Shufen Zhang; Ying Cai; Fangnan Wu; Fangyuan Kuang; Lianghui Wang; Shangzhi Xie; Jiahua Lan; Li Zheng; Guodong Xu; et al. (Human Cell, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

LEO satellite-enhanced GNSS-R joint position and velocity estimation algorithm for moving targets - Xuqiao Wang; Lan Du; Peiyuan Zhou; Zejun Liu; Zhongkai Zhang; Ken Deng; Lin Bao (International Journal of Remote Sensing, 2026)

Multi-objective hierarchical reinforcement learning for efficient and safe robotic manure cleaning in dairy barns - Wei Wei; Congcong Sun; Lin Wu; Jianglin Lan (Computers and Electronics in Agriculture, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Mobile phone cases as hotspots for perfluoroalkyl substances and pathogenic bacteria: An analysis based on user habits - Zhimin Xu; Zheng Lin; Runtong Huang; Rui Du; Shuai Xiao; Shunan Zhang; Heru Pramono; Yifan Wang; Renqiang Yu; Meijing Lan; Lei Wang (Journal of Hazardous Materials, 2026)

Hierarchically porous UiO-66-(OH)2@COF-OMe composites with multiple binding sites for synergistic extraction of polybrominated diphenyl ethers from surface waters - Jingpu Tang; Wentao Lan; Hongyan Zeng; Chenchen Lin; Xiaoping Wu (Journal of Hazardous Materials, 2026)

Surface-bound species-dominated peroxymonosulfate activation by an N-doped durian shell biochar-supported CoO/Co3O4/ZrO2 composite with strong electronic coupling for efficient carbamazepine degradation - Nguyen Lan Thanh; Nguyen Nhat Huy; Nguyen Hong Nam; Phan Thi Thuy; Le Viet Ngan; Ta Cong Khiem; Kun-Yi Andrew Lin; Vu Dinh Thao; Le The Son; Tran Viet Thu; Tran Tien Dat; Nguyen Trung Dung (Journal of Environmental Sciences, 2026)

Carbon nitride supported copper catalyst activating peroxydisulfate for efficient paracetamol degradation - Nan Huang; Ya-Lan Xu; Wen-Long Wang; Yan-lin Chen; Qian-Yuan Wu; Hong-Ying Hu (Journal of Environmental Sciences, 2026)

Gastric pH-induced liquid–liquid phase separation between lactoferrin and osteopontin protects against proteolysis and modulates intestinal uptake - Lan Liu; Chenming Lin; Meidan Zheng; Xinyue Tu; Yaming Yu; Zehan Song; Guoqiang Qi; Shanshan Li; Mingying Yang; Bo Lönnerdal; Yajun Shuai (Food Research International, 2026)

An integrated γ-aminobutyric acid–phytic acid strategy mitigates oxidative stress and quality deterioration in spinach during ambient-temperature storage - Shiai Zeng; Lan Gao; Kai Wang; Xuwei Liu; Peihong Fu; Lin Li; Lei Zhao (Food Bioscience, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Unveiling sulfur-vacancy-induced electron transfer pathways in FeNi2S4 steering peroxydisulfate activation from radical to non-radical oxidation - Yuansheng Wang; Xueming Lin; Zhicong Lan; Jiayi Li; Honghao Zeng; Hanyun Zhang; Min Yu; Jiaqu Tan; Dongya Li; Fan Yang (Chemical Engineering Journal, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Aptamer-driven tetrahedral framework nucleic acids for targeted resveratrol delivery in ulcerative colitis therapy - Botao Liu; Siyi Yang; Jiale Liang; Lan Yao; Bo Huang; Yu Chen; Yun Wang; Yunfeng Lin (Chemical Engineering Journal, 2026)

Bimetallic MOF/3D exosomes-loaded gelatin-dialdehyde starch hydrogel coating: Multimodal regulation of the bone-implant interface - Hui Su; Jian Yin; Jialu Wei; Hao Yang; Pengde Han; Zhangping Wang; He Lin; Lei Xie; Xiao Huang; Jinping Lan; Yong Huang (Chemical Engineering Journal, 2026)

Erratum to “Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface” [Bioresour. Technol. 451 (2026) 134559] - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Plant growth–promoting bacteria reshape rhizosphere microecology to regulate Cd, Pb, and Zn mobilization at root–soil interface - Caixing Lai; Kaiyang Ying; Xusheng Jiang; Xuehong Zhang; Hongwei Yu; Huachun Lan; Gang Liu; Geoffrey I. Sunahara; Jie Liu; Hua Lin; Yi Li; Guo Yu (Bioresource Technology, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

From general remediation to targeted control: a heavy metal management strategy for the Longjiang River, South China, based on source apportionment and risk assessment - Xiaolong Lan; Zengping Ning; Yin Li; Qingxiang Xiao; Haiyan Chen; Wenjie Lin; Yanlong Jia; Zhongwen Huang; Tangfu Xiao (Environmental Geochemistry and Health, 2026)

A novel AgNPs spongy trap coupled with portable XRF: a field-ready strategy for sensitive mercury analysis in soils - Lin Li; Yan Xu; Guanyu Lan; Zhenzhen Yao; Xiaoqin Chen; Mengyu Liu; Hongwei Shi; Xue Li; Xuefei Mao (Analytica Chimica Acta, 2026)

Enhanced co-removal of nutrients and glyphosate from rural sewage in siphon-driven constructed wetlands: Optimization and mechanisms - Yanhui Zhao; Yingfei Li; Yu Zheng; Peihao Yan; Yuanqi Lai; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Water Research, 2026)

Mapping global floodplain development disparities highlights drivers behind intensifying flood losses - Zhiyang Lan; Wenbin Liu; Rafael Jan Pablo Schmitt; Chaoyang Wu; Yingjie Li; Deliang Chen; Peirong Lin; Kailiang Yu; Xinli Bai; Kaihao Zheng; Tingting Wang; Hong Wang; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Microbial biodegradation of polyethylene in estuarine sediments: metabolic pathways of Pseudomonas under denitrifying conditions - Zhiyuan Lin; Xiaoxu Sun; Zexin Wang; Duanyi Huang; Tianle Kong; Wei Huang; Baoqin Li; Zewen Tan; Fei Huang; Xiaolong Lan; Wenjie Lin; Guangjie Chen; et al. (Journal of Hazardous Materials, 2026)

Two purified polysaccharides from Anemarrhena asphodeloides alleviate type 2 diabetes in mice through remodeling gut microbiota and modulating glycolipid metabolism - Juncheng Chen; Li Zhu; Liqian Chen; Guihong Fang; Baolian Li; Jing Zhou; Meijuan Lan; Lin Li; Bing Li (Food Bioscience, 2026)

Integrated transcriptomic and functional analyses provide insights into the heat stress response mechanisms and HrcA mediated potential regulatory in Tetragenococcus halophilus JY1 - Fangming Lan; Yu Zhang; Chi Zhao; Jiayi Lin; Dongdong Sun; Juliang Dai; Lixin Luo (Food Bioscience, 2026)

Piperazine-based bis-benzoxazine-derived self-crosslinked AEMs with suppressed swelling for low-resistance electrodialysis desalination - Lan Yang; Xinrui Lu; Hao Xu; Yafei Cheng; Qiuhua Li; Haiyang Yan; Xiaocheng Lin (Desalination, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Engineering a siderophore-macrolide conjugate via Trojan horse strategy for targeting Pseudomonas aeruginosa and related resistant pathogens - Chun-Yan Zhang; Wei-Min Chen; Guo-Bin Yang; Jing-Hua Wei; Zu-Ju Liang; Xi-Bing Hu; Ping Lan; Jing Lin; Jun Liu (Chemical Engineering Journal, 2026)

Two Novel Peniphenone Derivatives with Distinct Stereoconfigurations from Ascidian-Derived Fungus Diaporthe sp. SYSU-MS4722 and Their Anti-Fibrotic Activities - Shuya Ren; Yanhong Han; Yan Yan; Yuran Zhou; Siwen Yuan; Junjie Chen; Heng Guo; Zhenjian Lin; Qifeng Lin; Senhua Chen; Lan Liu; Yongkang Qiao; et al. (Journal of Ocean University of China, 2026)

Enrichment Characteristics of Normal-Pressure Marine Shale Gas in the Complex Tectonic Zone: A Case Study of the Lower Cambrian Niutitang Formation in Northern Guizhou - Wenjibin Sun; Zhonghu Wu; Yujun Zuo; Chao Pan; Hao Liu; Baofeng Lan; Jianyun Lin; Bin Chen; Qinggang Chen (Journal of Earth Science, 2026)

Study on prestack reservoir prediction of deep volcanic rock gas reservoirs in Chaganhua sub-sag of Songnan Fault Depression - Qin-lin Yang; Xue-pei Fan; Chen-chen Bi; Lan-mei Ke; Ye Yang; Da Zhang; Shu Wang (Applied Geophysics, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Action on hot nights: A scoping review of nighttime heat thresholds and their critical role in urban climate resilience - Pixin Gong; Qi Liu; Xi Lin; Yanbing Lin; Hui Xu; Li Lan (Sustainable Cities and Society, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Optimization and mechanism study of phosphorus and rare earth elements separation from phosphate ore by two-step leaching process - Yue Ma; Junhu Wu; Yanru Jin; Yue Lan; Lin Yang (Minerals Engineering, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Sulfonated azobenzene-derived nanogels: Hypoxia-specific degradation enables superior nucleic acid-mediated tumor therapy - Jia Zhou; Shubo Du; Lan Wang; Qiong Wu; Changmin Yu; Wei Du; Lin Li; Shao Q. Yao (Chemical Engineering Journal, 2026)

Simultaneous removal of sulfamerazine and nutrients in wastewater by alternate coupling of photocatalysis and microalgal system: From system construction to multi-interactions and purification effects - Lin-Lan Zhuang; Rui Li; Xiao-Xiong Wang; Yuxin Wu; Yanhui Zhao; Xiaojia Yi; Hongyang Liang; Weiyi Qian; Jian Zhang (Chemical Engineering Journal, 2026)

Corrigendum to “Large old trees sustain avian communities and critical plant-bird interactions in highly urbanised environments” [Biological Conservation 313 (2026) 111582] - Lin Xie; Xiao Huang; Tianhao Xia; Lan Wu; Si-Chong Chen (Biological Conservation, 2026)

Epidemiology of esophageal cancer in Xiamen, China, 2011–2020: trends in incidence, mortality, and survival from a population-based registry study - Haixia Zhang; Youlan Chen; Yilan Lin; Jiahuang Chi; Yanqi Lan; Qun Lou; Ahua Wu; Zhinan Guo (Cancer Causes & Control, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Pyrite addition drives sulfur cycling for efficient sulfamethoxazole removal and detoxification in sulfur-based constructed wetlands - Sihan Zhang; Jiaxing Lu; Lin-lan Zhuang; Huacheng Xu; Guoqiang Wang; Mingde Ji; Qiang Kong; Zhen Hu; Jian Zhang (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Pericyte NNMT drives an immune-hostile vascular niche and restricts cancer immunotherapy - Sheng Wang; Geni Ye; Caiyun Zhang; Lin Tan; Zhang Zhang; Xi Xu; Xinhui Chen; Yiming Zhang; Xiaoling Xu; Jinghua Pan; Tong Lan; Junqiu Zhang; et al. (Science Bulletin, 2026)

Transcriptomic analysis identifies VvMYB90 and VvNAC92 as key regulators mediating anthocyanin biosynthesis and fruit color differentiation in three grape cultivars - Han Lin; Kaili Mao; Shilong Chai; Jiangmin Lan; Hongbo Xiao; Zhixiong Guo; Tengfei Pan; Wenqin She (Plant Science, 2026)

Impact of extreme rainstorm on the stability of biological activated carbon in drinking water treatment: Differential microbial responses in new versus aged filters - Jia Niu; Haibing Wang; Yue Wang; Tian Lin; Rongxing Lan; Lihong Chen; Xianhua Liu; Kaiqin Xu; Xiaochen Chen; Xiaoyun Wang (Journal of Water Process Engineering, 2026)

Siphon-driven tidal flow enhances pyrene removal in iron-based baffled constructed wetlands: Feasibility and mechanism - Jiaxing Lu; Zizhang Guo; Lin-lan Zhuang; Jian Zhang (Journal of Environmental Chemical Engineering, 2026)

Preparation of Aromatic Camellia oleifera Seeds Oil by Roasting and Its Quality - Huanling Lan; Wenxia Liao; Huanhuan Ma; Liuying Lu; Xueyuan Lin; Yuting Wang; Yi Chen; Chang Li (Food Research International, 2026)

Synergistic regulation of chalkiness reduction in ratoon season rice by ABA and ascorbic acid: A physiological perspective - Hailong Xu; Bianhong Zhang; Xin Wu; Yijiang Hu; Americ Allison; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Anqi Li; Qingyang Zhang; et al. (Field Crops Research, 2026)

Optimizing synergistic microalgae cultivation and photocatalysis processes for antibiotic and nutrient removal in wastewater - Lin-Lan Zhuang; Hongyang Liang; Weiyi Qian; Zhen Hu; Xiao-Xiong Wang; Jian Zhang (Bioresource Technology, 2026)

Interactions of spatial type, activity intensity, and season on thermal comfort and multidimensional health in older adults - Yuanjing Wu; Boze Huang; Jing Le; Cuize Lin; Xindong Huang; Jielan Li; Siren Lan; Qunyue Liu (Building and Environment, 2026)

Identifying climate-resilient potential OECMs for migratory birds: A framework for future-oriented conservation planning - Guanjiao Lin; Siren Lan; Xiaohe Li (Biological Conservation, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

Muscle-specific transcriptomic and metabolomic signatures reveal heterogeneous aging trajectories and altered intercellular communication in male murine skeletal muscle - Caifen Guo; Xinqiang Lan; Chunping Huang; Xiang Wang; Dongqin Zhang; Lin Zeng; Qiquan Wang; Yang Xiang; Jian Li (Biogerontology, 2026)

Anoikis-Related Genes Can Accurately Predict the Occurrence of Endometriosis: A Retrospective Cohort Study via Machine Learning Analysis - Lin Hong; Lan Zheng; Yu-Feng He; Ya-Xing Fang; Hui Chen; Kang-Jia Chen; Shu-Guang Zhou (Biochemical Genetics, 2026)
Endometriosis is one of the most common benign gynecological disorders, characterized by persistent pain and challenges with fertility. Anoikis, a specific form of apoptosis, occurs when cells detach from the extracellular matrix. Recent researches have revealed that anoikis resistance is the most important prerequisite for endometriosis development, but it's still not entirely apparent, yet, what part anoikis plays in endometriosis pathogenesis. We obtained the GSE141549 dataset from the GEO database, which served as our training cohort. Anoikis-related genes (ANRGs), sourced from the GeneCards database, were integrated with differentially expressed genes (DEGs) identified in GSE141549. Consequently, we obtained a collection of differentially expressed anoikis-related genes (DE-ANRGs). Subsequently, we employed machine learning algorithms to screen for key diagnostic DE-ANRGs and developed a nomogram model to predict and diagnose endometriosis. Ultimately, we validated our findings through in vitro experiments and an online endometriosis database. Within the training cohort, a total of 47 DE-ANRGs were identified. Furthermore, three machine learning methods pinpointed four diagnostic genes (CAV1, PDK4, CSPG4, SERPINE1). Based on these genes, we constructed a nomogram to facilitate the prediction and clinical diagnosis of endometriosis. To assess model's predictive accuracy, clinical adaptability, and discriminative ability. We performed calibration curves, Receiver Operating Characteristic curves and decision curve analysis. All assessments demonstrated our model's outstanding performance. Ultimately, consistent expression trends of four genes were observed in GSE7305 test cohort, clinical specimens, and the Turku database when compared to the training cohort. In addition, we also have revealed the immune landscape differences, which may offer new promising immunotherapeutic targets for endometriosis patients in the future. In addition to offering novel perspectives on the role of anoikis in endometriosis pathogenesis, our analysis also identified a panel of distinctive biomarkers with significant diagnostic potential. Graphical abstract

NUFIP1-engineered exosomes modulate propofol-induced neurotoxicity in neonatal rats via the ERS apoptotic pathway - Pengyue Zhao; Yang Yan; Bin Lan; Xingpeng Yang; Yizhao Ma; Yichen Bao; Lin Qi; Xiaohui Du; Songyan Li; Wen Sun (Apoptosis, 2026)

Long-term Prediction of Saltwater Intrusion Based on Sequence Learning Framework - Tongfang Li; Kairong Lin; Zheng Kang; Jingwen Zhang; Tian Lan (Journal of Environmental Management, 2026)

Boron-doped secondary shell coordination architectures in iron single-atom catalysts boosts peroxymonosulfate activation and high-valent iron-oxo species formation for superior aquatic micropollutant purification - Junli Zheng; Shanhong Lan; Junjie Hu; Junjun Ma; Yajie Wu; Ceng Zeng; Hao Luo; Jinquan Wan; Qintie Lin; Junlong Xie (Journal of Environmental Sciences, 2026)

Advances in marine bioactive compounds for cell-cultured fish: from cellular regulation to application strategies - Xiaoyi Cai; Jieqiong Lin; Yalei Lan; Chunling Que; Xianxiang Chen; Jun Yang; Wenjie Wang; Chuan Li (Food Research International, 2026)

Quantifying situation-dependent uncertainty in tropical cyclone track forecasts with a recurrent neural network approach - Hsiao-Chung Tsai; Fang-Yi Lin; Yung-Lan Lin; Nai-Ning Hsu; Treng-Shi Huang; Russell L. Elsberry (Natural Hazards, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Microplastics in crustaceans imposing potential risk on human health: transferring, degradation, synergy, and metabolism - Huibin Chen; Xiaona Shen; Jingying Lin; Qihui Huang; Lan Zhao; Ruiyu Zhu; Li Li; Zhiyu Liu; Chao Zhao (Critical Reviews in Food Science and Nutrition, 2026)

SPVD-DETR: A novel real-time end-to-end object detector of sweetpotato virus disease from unmanned aerial vehicle ortho imagery - Fanguo Zeng; Ziyu Ding; Junzhi Chen; Yubin Lan; Lifei Huang; Yongxin Liu; Xuejun Yue; Lin Yuan (Computers and Electronics in Agriculture, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

Synergistic effects of amendments and Vetiveria zizanoides on soil quality and heavy metal bioavailability in a historical mine site: A 2-year field evaluation - Xiaolong Lan; Wenjie Lin; Jiaqi Li; Yin Li; Yaqi Zhao; Yili Gan; Yanlong Jia; Zengping Ning; Tangfu Xiao; Enzong Xiao (Ecological Engineering, 2026)

Boron nitride nanosheets via arginine-assisted embedded with phosphomolybdic acid as pesticide carriers for visualization in pest control - Li Hao; Minyan Zhou; Jialin Zeng; Jiechun Lin; Lan Hua; Ziting Yin; Mei Guan; Qiangcheng Zheng; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2026)

16S rRNA gene-based big data profiling and comparative statistical analysis of anammox communities under different feed regimes - Haotian Liu; Zijian Tao; Ying Song; Lan Lin; Jingpeng Li; Meizhen Wang (Bioresource Technology, 2026)

Nitrogen removal driven by zonal supply of thiosulfate and pyrite in an up-flow blanket filter (UBF) reactor - Qian Zhang; Lan Lin; Tingsheng Hu; Qianyi Liu; Ying Wang; Haozhe Mo; Wenbiao Jin; Wei Zhang; Jun Chen; Huabin Zeng; Xiaojun Wang; Shaohua Chen; et al. (Bioresource Technology, 2026)

Low C/N organic residues enhance reductive soil disinfestation for the suppression of Ralstonia solanacearum - Hui-Juan Duan; Yue Yin; Jun Zhao; Xian-Yong Lin; Gui-Lan Duan (Plant and Soil, 2026)

The correlation between social support and hopelessness among cancer survivors: a meta-analysis - Lu-Ting Shen; Jian-Zeng Lan; Attiq-Ur-Rehman; Wei Li; Meng-Wei Ge; Rui Feng; Kang Zhong; Si-qi Gao; Hong-Lin Chen (Cancer Causes & Control, 2026)

A monogamous male's dilemma: Managing two females and parental care in white‐faced plovers - Boya Xie; Xi Lin; Xiaotong Niu; Heiman Ho; Xinlei Liu; Xin Lan; Zitan Song; Yachang Cheng; Yang Liu (Ecology, 2026)

Associations of air pollution and genetic risk and their interaction with risk of Alzheimer’s disease: identification of risk loci and potential biological pathways - Shanshan Ran; Jingyi Zhang; Miao Cai; Lan Chen; Zhengmin Qian; Fei Tian; Gan Wu; Ri’enna Boyd; Stephen Edward McMillin; Huai-cai Zeng; Yin Yang; Hualiang Lin (GeroScience, 2026)

Two new compounds from the capitula of Chrysanthemum morifolium cv. Fubaiju - Jin-Lin Chen; Yue-Hao Huang; Si-Yu Yang; Xue-Fang Zhuo; Yao-Lan Li; Yu-Bo Zhang; Jun-Jie Zhong; Guo-Cai Wang (Natural Product Research, 2026)

Comprehensive evaluation and analysis of cold tolerance in Neopyropia yezoensis strains based on multiple traits - Zi-Xiang Zhai; Guo-Ying Du; Lan Wu; Lin Tian; Li-Hong Ma (Aquaculture, 2026)

Stabilizing photogranule systems under low-light and limited-aeration: From operational strategy to underlying mechanism - Xiaojing Yang; Lan Tang; Jinke Sun; Fahui Ji; Peng Qi; Meng Yan; Yanjuan Luo; Chen Yang; Yanting Lin; Hui Lu (Water Research, 2026)

How Chlorella vulgaris remove florfenicol from wastewater—— from the aspects of kinetics, mechanism, limiting factors and long-term regulation - Lin-Lan Zhuang; Kehan Zhou; Wanqing Tian; Rui Li; Yingdong Shi; Zhongzhong Wang; Jian Zhang (Water Research, 2026)

Attached microalgae-simulated plants enhanced multiple-pollutant removal in a tidal flow constructed wetland: quantified efficiencies, pathways, and biological mechanisms - Shu-Han Ge; Mei-Zi Yang; Wei-Yi Qian; Lin-Lan Zhuang; Hai-Ming Wu; Zhuo Chen; Xiao-Xiong Wang; Jian Zhang (Water Research, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

A new Coniopteris (Dicksoniaceae) from the Middle Jurassic of the Baojishan Basin, Gansu, China, with discussion on its heteromorphic pinnule characteristics - Lan-Xing Wei; Cun-Lin Xin; Zhi -Peng Jiao; Fang-Fang Zhang; Hong Li (Review of Palaeobotany and Palynology, 2026)

Coupled CFD-DEM modeling of fine particles and fibers migration and clogging mechanisms in bridging regions - Ran Lin; Yinjian Huang; Jinzhou Zhao; Lan Ren; Zhihao Yu; Zhiqiang Li; Jianfa Wu; Yi Song; Cheng Shen (Computers and Geotechnics, 2026)

PET imaging-guided biomimetic nanoplatform reprograms the tumor immune microenvironment and disrupts stromal barriers to potentiate immunotherapy in malignancy - Yuan Feng; Wenyu Song; Zhaoguo Lin; Zihan Zhang; Wenzhu Hu; Xingyi Wang; Yueling Deng; Yongkang Gai; Zi Ye; Dawei Jiang; Xiaoli Lan; Xiao Zhang (Chemical Engineering Journal, 2026)

Regulating electrode wettability by construction of the liquid-liquid interface for improving metal electrodeposition performance - Chenrui Lan; Haopeng Feng; Lingyue Zhang; Jiawei Yue; Yangfeng Wu; Jiajia Wang; Jing Tang; Lin Tang (Chemical Engineering Journal, 2026)

Large old trees sustain avian communities and critical plant-bird interactions in highly urbanised environments - Lin Xie; Xiao Huang; Tianhao Xia; Lan Wu; Si-Chong Chen (Biological Conservation, 2026)

Deep Shale Matrix Permeability Evolution During Well Shut-In Under True Triaxial Stress - Jinzhou Zhao; Yanshan Guo; Zhihao Yu; Lan Ren; Ran Lin; Jianfa Wu; Yi Song; Cheng Shen (Rock Mechanics and Rock Engineering, 2026)

An Integrated Machine Learning and Remote Sensing Method for Predicting Cyanobacterial Blooms: A Case Study in China’s lakes along a large-scale water diversion project - Yue Zhang; Jun Hou; Lin Lan; Zheng Wu; Hanzhi XU; Jun Wu; Guoxiang You; Wei Ding; Qianqian Zheng; Lingzhan Miao (Environmental Management, 2026)

Harnessing pyroptosis to restrain melanoma through aripiprazole - Yu-Teng Chang; I-Hsiang Lin; Jeng-Jer Shieh; Tsuo-Hung Lan; Jia-Ning Syu; Shiau-Shian Huang; Po-Hsun Hou (Apoptosis, 2026)

Making waves: Does the polyvalent iron cycle truly exist in constructed wetlands during wastewater treatment? - Meizi Yang; Yanhui Zhao; Xiaojia Yi; Yuanqi Lai; Yin-Hu Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

Mapping plasma metabolic profiles reflecting air pollution and their association with kidney failure: A prospective cohort study - Peng Hu; Shengtao Wei; Ge Chen; Lan Chen; Fei Tian; Zitong Zhuang; Manting Rao; Zhenhe Huang; Hualiang Lin (Journal of Hazardous Materials, 2025)

Optimization and mechanism exploration of NH2-functionalized MIL-101(Fe) for enhanced adsorption of antibiotics in single and binary systems: Experimental analysis and DFT calculations - Si Duan; Yuanhua Lin; Guihong Lan; Yudi Jing; Mohd Talha (Journal of Environmental Chemical Engineering, 2025)

Ag/AgCl@NH2-MIL-88B functionalized pH-responsive aerogel for enhanced organic pollutant removal via adsorption and photo-Fenton-like degradation synergy - Anrong Yao; Yafang Wang; Kai Wang; Haoyi Hu; Siyao Tian; Yeqian Ge; Lin Yang; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Journal of Environmental Chemical Engineering, 2025)

The growth-promoting effect and mechanism of microalgae on plants in PAHs contaminated soil - Yuechang Wang; Shengnan Wang; Lin-Lan Zhuang; Shuang Liu; Yuanjun Su; Zhen Hu; Xiaoping Wang; Shaoming Cui; Gang Peng (Journal of Environmental Sciences, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Sustainable energy generation through engineered copper molybdate: a ternary metal oxide catalyst for efficient oxygen evolution in alkaline environments - Hung-Chang Cheng; Dhanapal Vasu; Hsin-Yu Lin; Zhen-Yuan Lan; Leggins Abraham; Tetsu Yonezawa; Te-Wei Chiu (Fuel, 2025)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Natural amino acid-tailored deep eutectic solvents for comprehensive bamboo valorization under mild conditions - Fan Zhang; Qixuan Lin; Wu Lan; Jianbo Huang; Zhenhua Su; Fengxia Yue; Chuanfu Liu (Chemical Engineering Journal, 2025)

Valorization of blueberry pomace and red mud to zero valent iron biochar for antibiotic degradation with diminishment of toxic reagents - Xu Su; Jie Han; Yuwei Huang; Xuanming Wang; Siyu Wang; Ziyi Ge; Hechong Yuan; Juying Liu; Xuerong Xiang; Fan Xia; Li Lin; Yu Lan; et al. (Bioresource Technology, 2025)

Pregnant PM2.5 exposure promotes uterine contractility via miR-200a-PGR-oxytocin signaling pathway leading to preterm birth - Jingyi Zhang; Shanshan Ran; Shengtao Wei; Zijun Yang; Huaicai Zeng; Guang Jia; Zhangjian Chen; Lan Chen; Fei Tian; Ge Chen; Zilong Zhang; Hualiang Lin (Atmospheric Environment, 2025)

Characterizing the mediating role of metabolic signatures in the associations between air pollution exposure and inflammatory bowel disease - Jiayue Zhang; Chengwei Chai; Lan Chen; Fei Tian; Ge Chen; Xiaojie Wang; Yin Yang; Hualiang Lin; Zilong Zhang (Atmospheric Environment, 2025)

Biomineralization-driven simultaneous carbon/phosphorus recovery and membrane fouling control in anaerobic membrane bioreactor for swine wastewater treatment - Qianyi Liu; Hongyu Xie; Yin Xu; Ziang Zhou; Yuqi Chen; Lan Lin; Rasheed Adeleke; Heng Li; Yuanpeng Wang; Shaohua Chen; Yanlong Zhang (Water Research, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

A revisiting of 2021 Japanese electricity spot market dysfunction event: How it happened and what can we learn from it? - Hong-Zhou Li; Lin-Lan Bu; Maria Kopsakangas-Savolainen; Mika Goto (Energy Policy, 2025)

Design, preparation and application of triboelectric energy harvester with antibacterial performances - Changmei Lin; Zhenhao Pei; Jinxin Lan; Jianhui Huang; Minghua Liu; Shilin Cao; Xiaojuan Ma (Chemical Engineering Journal, 2025)

Regulating the charge transport ability of the TiO2/CsPbI2Br perovskite interface layer by MoS2 nanoparticles for high-performance carbon-based all-inorganic perovskite solar cells - Zhaowei Huang; Lin Gao; Fengli Liu; Shihui Xu; Yaxuan Chai; Jing Li; Qing Yao; Haozhen Deng; Liuxue Sun; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2025)

A point-of-care testing biosensing platform integrated with physiologically based pharmacokinetic model for on-site therapeutic drug monitoring of methotrexate - Feng-Feng Zhang; Mei-Juan Wu; Zi-Wei Yu; Yi-Lan Lin; Pin-Fang Huang; Meng-Meng Liu (Chemical Engineering Journal, 2025)

Stable and efficient n-type perylene diimides radical as cathode interlayer with wide thickness tolerance for organic solar cells - Lin Hu; Senmei Lan; Guobin Shen; Fang Wang; Yingzhi Jin; Zhen Su; Jia Yao; Mengzhen Du; Zheng Yan; Wei Li; Dan Zhou; Erjun Zhou; et al. (Chemical Engineering Journal, 2025)

Dual-targeting pluripotential biomimetic nanovehicle modulates tumor immune microenvironment for potentiated cancer chemoimmunotherapy - Nan Wang; Mingjian Zhu; Shengfei Yang; Jiahe Wu; Manning Zhu; Lan Ma; Xunqi Zhang; Donghang Xu; Bo Zhang; Jianqing Gao; Nengming Lin (Chemical Engineering Journal, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

A comprehensive perspective on intestinal health, physiological status, and growth performance of Larimichthys crocea with different stocking densities in recirculating aquaculture systems - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture International, 2025)

Biodiversity Buffers Phytoplankton Biomass Production Against Nanoparticle Pollution Through Increased Facilitation - Yiping Zuo; Qianna Xu; Michael Southard; Guangxing Zhang; Lan Gan; Hao Zhang; Pu Yan; Louis Walls; Mary Steinbeck; Muhan Zhao; Yongsheng Chen; Lin Jiang (Ecology Letters, 2025)
Although biodiversity is widely recognised for its role in maintaining ecosystem functioning under environmental change, its importance has received relatively little attention in the context of emerging environmental stressors such as nanoparticles. By assembling phytoplankton communities across a gradient of species richness and exposing them to varying concentrations of copper oxide nanoparticles, we experimentally explored how biodiversity modulates ecosystem functioning under nanoparticle exposure. We found that the positive effect of biodiversity on phytoplankton biomass production was amplified at higher nanoparticle concentrations, allowing diverse communities to maintain biomass despite strong inhibitory effects of nanoparticles on monocultures. This enhanced biodiversity effect was primarily driven by increased complementarity, specifically through more frequent facilitative interactions among species under nanoparticle stress. Our findings advance the understanding of how biodiversity preserves ecosystem functioning and underscore its role in mitigating the impacts of emerging anthropogenic stressors.

Multiple light sources excited fluorescence image-based non-destructive method for citrus Huanglongbing disease detection - Kangting Yan; Xipeng Fang; Weiguang Yang; Xidan Xu; Shaozhen Lin; Yali Zhang; Yubin Lan (Computers and Electronics in Agriculture, 2025)

Maintaining high levels of HIF-1α protects osteoarthritis cartilage by activating autophagy - Xiaolei Chen; Gangning Feng; Lufei Shao; Xue Lin; Xiaoxin He; Yong Yang; Xin Zhao; Jiangbo Yan; Long Ma; Yong Zhou; Kuanmin Tian; Hui Wang; et al. (Tissue and Cell, 2025)

Association between serum metal levels and NLRP3 gene polymorphisms with cognitive function in aluminum workers: A combined epidemiological and genetic study - Youxing Li; Wenxue Li; Yaqin Pang; Yufang Cen; Rongqing Xiao; Yinxia Lin; Boya Li; Jingyi Lu; Yincai Lan; Ahmad Razali Bin Ishak; Guangzi Qi; Mohd Shukri Bin Mohd Aris (Journal of Trace Elements in Medicine and Biology, 2025)

Exploring controls on precipitation-runoff dependencies: Implications for non-stationary and spatially heterogeneous analyses - Tian Lan; Xinyue Du; Xue Xie; Kairong Lin; Hongbo Zhang; Xinghui Gong; Yongqin David Chen; Chong-Yu Xu (Journal of Hydrology, 2025)

The synergistic performance and mechanism of coal dust suppression contributed by Bacillus pasteurii assisted with a potent indigenous Lysinibacilus MN-5 - Gang Zhou; Yixin Xu; Wenqi Shao; Xueqiang Lv; Yongguang Lan; Xianchao Jia; Jintuo Zhu; Guochao Yan; Jianmin Bai; Lin Li (Journal of Environmental Chemical Engineering, 2025)

Optimizing 3D food printing inks: The impact of polysaccharides on Camellia seed protein emulsion gels - Jiaru Lin; Chenhao Liang; Tong Lin; Ruimin Zhong; Yong Cao; Yaqi Lan (Food Hydrocolloids, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Modification effect of prenatal polyunsaturated fatty acids on the associations between air particulate matter exposure and infant's growth: A birth cohort study - Yu Liu; Xiaonan Gu; Lili Qin; Xuanqing He; Minyan Lan; Yujing Chen; Qian Chen; Zhen Wang; Zhaoyan Liu; Lizi Lin; Jing Wei; Yanhong Wei; et al. (Environmental Pollution, 2025)

Selective recovery of precious metals from E-waste leachates using zinc-modified biochar in capacitive deionization - Yangfeng Wu; Haopeng Feng; Tang Jing; Chenrui Lan; Nile Wu; Nana Chai; Jiawei Yue; Lin Tang (Desalination, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Interfacial charge transfer in Ti3C2O2/NLCOF heterojunction enables efficient photocatalytic H2O2 production - Na Lv; Shu Lin; Lan Ding; Kezhen Qi; Weibin Zhang; Vadim Popkov (Chemical Engineering Journal, 2025)

Cluster-net structured polymer hydrogel elastomer engineered as artificial temporomandibular joint disc for establishing mechanical homeostasis - Hao Dai; Jianming Zhao; Kun Qiao; Tianyi Lin; Yajie Xie; Lin Lan; Jie Wang; Yuchen Liu; Shuo Chen; Yudong Zheng; Yang He (Chemical Engineering Journal, 2025)

Partial oxidation doped strategy for high performance and stable perovskite solar cells - Lina Tan; Jihuai Wu; Chunyan Deng; Weichun Pan; Yuqian Yang; Liuxue Sun; Xia Chen; Jianming Lin; Zhang Lan (Chemical Engineering Journal, 2025)

Bioinspired phosphorylated cellulose nanocrystals-based multi-crosslinked binder for enhanced stability and sustainability in silicon anodes - Lan Zhao; Fengcai Lin; Haijun Li; Lingling Qian; Yingshan Shi; Zhiyi Cao; Xuan Yang; Biao Huang; Beili Lu; Hanyang Liu; Lirong Tang (Carbohydrate Polymers, 2025)

Chitosan-based Janus dressing with asymmetric wettability for rapid hemostasis, antibacterial protection, and tissue regeneration in hemorrhagic wound management - Jiyuan Wang; Haowen Ye; Kaitong He; Weikang Jiang; Wei Lan; Zu’an Zeng; Peiran Lin; Han Wang; Botao Gao; Wenlong Wang; Yadong Tang (Carbohydrate Polymers, 2025)

Reply to the comments on “Hygrothermal properties of Tibetan paper: The effects of air pressure and printed scriptures” - Yige Liu; Xi Lin; Cunming Li; Yucai Guan; Chi Feng; Li Lan (Building and Environment, 2025)

Coal Spontaneous Combustion Early Warning Methods Based on Slope Grey Relation Analysis - Xing-wang Huo; Hai-dong Chen; Yong-liang Xu; Lan-yun Wang; Lin Li (Natural Resources Research, 2025)

Model experiments and numerical analysis of the influence of tunnel diameter on tunnel rockburst - Yaofeng Yan; Yuanyou Xia; Lan Zhang; Jian Huang; Yuanhang Zhang; Minjia Yan; Zhouhao Yuan; Manqing Lin (Journal of Mountain Science, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Energy poverty and household consumption upgrading: evidence from the China family panel studies - Hongying Lin; Ya-Lan Liu (Environment, Development and Sustainability, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

Effects of exercise intensity on large yellow croaker (Larimichthys crocea): A comprehensive analysis of growth, physiology, muscle fiber structure, and gut health - Songpeng Jia; Mengqi Lu; Tianyi Lan; Zhenyu Gao; Jie Ding; Ran Meng; Xuelei Wang; Xiongfei Wu; Lin Huang; Xujie Li; Zhongming Zheng; Weiliang Shen (Aquaculture, 2025)

Fate and health implications of polycyclic aromatic hydrocarbons in a sustainable food waste recycling system using housefly maggots and Nile tilapia - Chao Zheng; Zhang Cheng; Zhi-Lin Chen; Yu Bon Man; Qiao Liu; Liu-Lan Zhao; Song Yang; Ming Hung Wong (Aquaculture, 2025)

Non-destructive prediction of soluble solids content and firmness and maturity determination of guava fruit using color and fluorescence imaging - Shaozhen Lin; Kangting Yan; Zhilei Sun; Zhijie Zhang; Yubin Lan; Linlin Wang; Yali Zhang (Postharvest Biology and Technology, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Proline-rich nuclear receptor coactivator (Pnrc), the Drosophila aaquetzalli homologue, is important in survival of Henosepilachna vigintioctopunctata - Ahmad Ali Anjum; Lan-Lan Liao; Lin Jin; Guo-Qing Li (Journal of Insect Physiology, 2025)

Microbial synergistic metabolic mechanism of enhanced tetrabromobisphenol A removal by bio-electrochemical system coupled constructed wetland - Xiao-Qiu Lin; Zhi-Ling Li; Xue-Qi Chen; Ling Wang; Lan Yu; Ai-Jie Wang (Journal of Hazardous Materials, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Distinguishing dominant drivers on long-term vegetation dynamics across China considering time-lag and accumulation effects using machine learning techniques - Qianxin Wang; Lin Huang; Meng Yang; Lan Wang; Wei Cao (Journal of Environmental Management, 2025)

Boosting the initial Coulombic efficiency of Bi2S3-based anode for practical sodium-ion batteries - Lankun Shi; Rongji Jiao; Dawei Lan; Li Wang; Yu Gao; Meng-Fang Lin; Zhongmin Lang; Wenxiu He; Guixiao Jia; Jinlong Cui; Shaohui Li (Chemical Engineering Journal, 2025)

Scalable synthesis of anatase TiO2 nano-in-micro spheres for hybrid sodium-ion capacitors - Zerui Yan; Sicheng Fan; Xia Zou; Qinyao Jiang; Dafu Tang; Kun Lan; Jiaxin Li; Yingbin Lin; Zhigao Huang; Dong-liang Peng; Qiulong Wei (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of the Basic Helix-Loop-Helix (bHLH) Transcription Factor Family in Gastrodia elata - Shanshan Lan; Xin Lin; Maoqiong Wei; Guangheng Feng; Hongcheng Liu; Jinliang Shao; Xinyu Li; Zeli Chen; Zhenhuan Liu (Plant Molecular Biology Reporter, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

In vitro and in vivo evidence on the association of pregnant PM2.5 exposure with preterm birth and potential role of placental miRNA-21 regulating TLR4/NF-κB and activating NLRP3 inflammasome - Shanshan Ran; Wenxue Li; Zijun Yang; Jingyi Zhang; Zhangjian Chen; Guang Jia; Qingmei Lin; Huai-cai Zeng; Yin Yang; Zilong Zhang; Yonggui Gao; Lan Chen; et al. (Journal of Hazardous Materials, 2025)

Insight into the mechanism of pyrolysis temperature on the performance of biochar-based MOF materials in capacitive deionization for heavy metal removal - Yangfeng Wu; Haopeng Feng; Jing Tang; Chenrui Lan; Nile Wu; Nana Chai; Jiawei Yue; Lin Tang (Desalination, 2025)

Iron-modified electroactive material mediated chain elongation: Bridging pseudocapacitance and caproate biosynthesis - Zi-Lin He; Yong-Yao Zhang; Tian Lan; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Chemical Engineering Journal, 2025)

Spatial confinement-enabled full-color emission from carbon dots via controlled sp2 domain assembly in spray pyrolysis - Lin Lan; Zhenfeng Gan; Yuan Ma; Rui Bao; Xin Kong; Liang Liu; Jianhong Yi (Chemical Engineering Journal, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

Target analysis of per- and polyfluoroalkyl substances in surface water: Occurrence, seasonal trends, and risk-based prioritization in the Minjiang River - Hui Zhang; Xin-Yue Wang; Yu-Hua Zheng; Jing-Run Hu; Xiao-Lin Li; Hong-Ling Yin; Rui Xiao; Xiao-Lan Zhu; Ting Chen; Huan Chen (Science of The Total Environment, 2025)

Modulating the electronic configuration of single-atom nanozymes using cobalt nanoclusters for enhanced mycotoxin degradation - Yaqi Zhang; Huikang Lin; Lan Wang; Lijun He; Yong Man; Bingxuan Jia; Zheng Yan; Shimo Kang; Haijiao Xie; Aibo Wu (Food Chemistry, 2025)

Electronic state reconfiguration of NiMoCox boosts electrocatalytic upcycling of polyethylene terephthalate plastic wastes for simultaneous production of formate and green hydrogen - Shaofeng Wang; Shuaidong Li; Yutong Li; Yue Xu; Zhaomeng Wu; Yingjian He; Yongwei Zhao; Zheer An; Ying Lan; Yanxiao Hu; Jingzi Zhang; Yan Huang; et al. (Chemical Engineering Journal, 2025)

Priming effects by cellulose inputs decrease with warming regardless of the decomposition stages of soil carbon pools - Junjie Lin; Guoxin Lan; Zhenyu Yang; Shuang Zhou; Dafeng Hui; Peng Wang; Shuai Zhang; Lifeng Ping; Shengdao Shan (Plant and Soil, 2025)

Chronic and Intergenerational Toxicity of Chloramine-T in Moina macrocopa Following Prolonged Exposure - Xue Lei Hu; Sui Jun Cai; Ming Chen; Le Yi Lin; Jin Lan Peng; Jin Ling Liu; Yun Hui Li; Lu Wang (Bulletin of Environmental Contamination and Toxicology, 2025)

The impact of changing ambient population composition on crime during COVID-19 lockdowns - Xin Gu; Lin Liu; Su Yeon Han; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Applied Geography, 2025)

Genomic analysis of the novel Stenotrophomonas phage vB_Srh_LBjhp91a, isolated from a Karst cave in China - Lou Ren; Zheng Fang; Shixia Li; Qingshan Wu; Lan Xiang; Chuangen Lin; Qiuping Liu; Leitao Tan; Qingbei Weng (Archives of Virology, 2025)

The substrate configuration influences pollutant removal in constructed wetlands: From the aspects of submerged status of substrate and carbon-felt distribution - Xiang-Zheng Li; Tong Wang; Ting Yang; Xue Li; Lin-Wei Wu; Lin-Lan Zhuang; Jian Zhang (Water Research, 2025)

Design of GO@TiO2 and PDA@CNC decorated gelatin aerogel for efficient adsorption and photocatalytic degradation of organic pollutants - Chang Liu; Anrong Yao; Wei Li; Qian Xu; Lin Yang; Yeqian Ge; Jianwu Lan; Shaojian Lin; Jinghong Qiu (Journal of Water Process Engineering, 2025)

Application of cold plasma for rice bran preservation: Effects on stability and quality - Wencheng Yang; Huanhuan Ma; Huanling Lan; Wenxia Liao; Xueyuan Lin; Chang Li (Innovative Food Science & Emerging Technologies, 2025)

Impact of Staphylococcus carnosus DG06 inoculation on microbial and metabolic profiles during Cantonese soy sauce fermentation - Chi Zhao; Yuxiang Zhang; Fangming Lan; Huizhen Wu; Weixin Li; Weifeng Lin; Lixin Luo (Food Research International, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Corrigendum to ‘Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater’ [Environ. Res., Volume 273 (2025) 121161] - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

GNA15 induces drug resistance in B cell acute lymphoblastic leukemia by promoting fatty acid oxidation via activation of the AMPK pathway - Jie Luo; Shirui Pan; Jing Luo; Lan Wang; Jiaxiu Yin; Haiqiu Zhao; Rong Su; Mingyan Liao; Lin Liu; Jiamin Zhang (Molecular and Cellular Biochemistry, 2025)

Protease-hydrolysis-driven approach towards the quantification of cellular mRNA after drug treatment in protein nanopores - Ling Zheng; Jizhen Lin; Wenqiang Tian; Ting Weng; Xu Wang; Lan Sun; Chaker Tlili; Xiaohan Chen; Junzhong Lai; Baoquan Zhao; Deqiang Wang (Analytica Chimica Acta, 2025)

The underlying mechanism of Porcine Teschovirus 2 3Cpro antagonizing the NLRP3 inflammasome - Xin-yu Zhang; Yu-ying Li; Wei Chen; Yi-min Zhou; Lin Zhou; Lu-lu Xie; Yan-Qing Hu; Hai-xin Huang; Chen-chen Zhao; Yan Qin; Tian Lan; Wen-chao Sun (Veterinary Microbiology, 2025)

Rapid Indian Monsoon response to the Younger Dryas event in the Southeastern Tibetan Plateau - Xiqian Wang; Liangcheng Tan; Ashish Sinha; Hai Xu; Haiwei Zhang; Jianghu Lan; Jin Zhang; Tianli Wang; Dong Li; Le Ma; Jingjie Zang; Xing Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

LSTM-FKAN coupled with feature extraction technique for Precipitation–Runoff modeling - Tongfang Li; Kairong Lin; Tian Lan; Yuanhao Xu (Journal of Hydrology, 2025)

Thermal sensitivity and rising greenhouse gas emissions in riparian zone soils: Implications for ecosystem carbon dynamics - Shuxun Cheng; Amit Kumar; Guoxin Lan; Wenling Zhang; Zhuolin Yu; Shuai Zhang; Zhi-Guo Yu; Meijuan Yao; Junjie Lin (Journal of Environmental Management, 2025)

The effect of sulfamethoxazole on the growth of microalgae biofilms and the internal transportation and transformation of nutrients in the biofilm - Fengkai Sun; Yukai Jiao; Shuang Liang; Lin-Lan Zhuang; Jian Zhang (Environmental Research, 2025)

Biochar-amended constructed wetlands enhance sulfadiazine removal and reduce resistance genes accumulation in treatment of mariculture wastewater - Yuan-yuan Gao; Yu-xin Wu; Wang-chao Chu; Li Lai; Jia-hao Sun; Lin-lan Zhuang; Fei-fei Liu (Environmental Research, 2025)

Association between exposure to perfluoroalkyl substances (PFASs) and risk of hyperemesis gravidarum - Lan Zhang; Xiuxiu Ma; Tong Su; Yue Wang; Miaomiao Hai; Feifei Qi; Le Ma; Shunming Zhang; Jing Lin (Environmental Pollution, 2025)

Community structure and metabolic potentials of keystone taxa and their associated bacteriophages within rice root endophytic microbiome in response to metal(loid)s contamination - Yanlong Jia; Duanyi Huang; Xiaolong Lan; Xiaoxu Sun; Wenjie Lin; Weimin Sun; Yize Wang (Environmental Pollution, 2025)

rGO/Ti3C2 MXene synergistic spontaneous realization of efficient clean water production and pollutant degradation - Lin Lin; Danyi Li; Siyi Xu; Fangzheng Wang; Linfan Li; Lan Zhang; Jihao Li (Desalination, 2025)

Double-edged sword role of Fe(II) in the dynamics of anammox coupled Fe-P crystals granulation and phosphorus removal - Ying Wang; Yushi Jinag; Lan Lin; Zikun Zhang; Qian Zhang; Wenzhi Cao; Yanlong Zhang (Chemical Engineering Journal, 2025)

Chitosan-based porous carbon material with lamellar stacking structure for efficient CO2 adsorption and catalytic conversion - Chunliang Yang; Lan Luo; Tianxiang Zhao; Jianxin Cao; Qian Lin (Chemical Engineering Journal, 2025)

An anti-miR-301a and zinc coordination driven nanozyme loaded in nanoparticle for oral therapy of inflammatory bowel disease based on colitis microenvironment regulation - Jiafeng Zou; Chuanhe Xia; Min Yao; Xier Pan; Shulei Zheng; Yiting Lin; Xinlin Zhao; Yanwen Wang; Yanzuo Chen; Minbo Lan; Junshan Wang; Feng Gao (Chemical Engineering Journal, 2025)

Perovskite quantum dots Revolutionize Lithium-Sulfur battery Performance: Cathode catalytic Breakthrough with CsPbBr3 - Renjing Duan; Xiaoshi Lang; Xiang Wang; Lan Li; Tingting Qu; Lin Wang; Jianbin Li; Chuangang Yao; Kedi Cai (Chemical Engineering Journal, 2025)

Interfacial engineered biomass-derived G/VMT-PCNCs networks as high-performance proton-conducting humidity sensors - Lirong Tang; Junwei Wu; Zhiyi Cao; Qiqi Hong; Fengcai Lin; Ningning Tan; Lan Zhao; Xinda You; Beili Lu; Xuan Yang; Biao Huang; Hanyang Liu (Carbohydrate Polymers, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Immune dysregulation of decidual NK cells mediated by GRIM19 downregulation contributes to the occurrence of recurrent pregnancy loss - Ying Wang; Anliang Guo; Lin Yang; Xiaojuan Han; Qianni Li; Jin Liu; Yilong Han; Yang Yang; Lan Chao (Molecular and Cellular Biochemistry, 2025)

Spinocerebellar Ataxia 44 Caused by a Novel GRM1 Variant: Reviewing the Contrasting Pathogenic Mechanisms Underlying Two GRM1-Associated Hereditary Ataxias - Shih-Chun Lan; Yung-Yee Chang; Tsu-Kung Lin; Min-Yu Lan (The Cerebellum, 2025)

Kuenenia-enriched hydroxyapatite granules enable stable high-rate nitrogen removal of high-strength food waste permeate in an EGSB-anammox system: Insights into granule performance and process scalability - Lan Lin; Wenzhao Zhao; Shen Cui; Ying Song; Yuanfan Zhang; Yu-You Li (Journal of Water Process Engineering, 2025)

Multisite synergistic interaction induced selective adsorption of CB5-Ti3C2T2 complex for strontium ion: A combined theoretical and experimental study - Sifan Li; Pengcheng Zhang; Yujuan Zhang; Kaikai Qiu; Lin Wang; Jianhui Lan; Yu Zhang; Xuwen Zhao; Chengzhen Miao; Weiqun Shi (Journal of Hazardous Materials, 2025)

Toxicity of rare earth elements europium and samarium on zebrafish development and locomotor performance - Boyu Yang; Luning Sun; Zheng Peng; Qing Zhang; Mei Lin; Zhilin Peng; Jue Yang; Lan Zheng (Journal of Hazardous Materials, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Restorative effects of highway roadside urban forests: A simulated approach - Qunyue Liu; Kunneng Jiang; Ziming Wang; Yumeng Wang; Huiting Zhang; Qingju Wang; Hangqing Chen; Donghuang Lin; Ulrika K. Stigsdotter; Yuxiang Lan (Forest Policy and Economics, 2025)

Unravelling the response mechanism of extracellular polysaccharides synthesis and salt stress resistance in Tetragenococcus halophilus JY1biofilm formation - Jiayi Lin; Chi Zhao; Jvliang Dai; Yu Zhang; Fangming Lan; Lixin Luo (Food Bioscience, 2025)

Investigating the main contributors to esterification activity and identifying the aqueous-phase ester synthases in Daqu - Yu Tie; Lin Wang; Bo Ding; Zhao Deng; Qian Yang; Min Zhu; Zhengyun Wu; Lan Tang; Taikei Suyama; Wenxue Zhang (Food Bioscience, 2025)

Long-term exposure to ambient air pollutants and risk of prostate cancer: A prospective cohort study - Yu Chen; Siru Yang; Jiahao Lin; Shaohua Gu; Lan Wu; Wenkai Huang; Jun Yang; Mengmeng Li (Environmental Research, 2025)

Effect of microplastics on carbon, nitrogen and phosphorus cycle in farmland soil: A meta-analysis - Guoxin Lan; Xiaohang Huang; Tongqing Li; Yingjie Huang; Yang Liao; Qiushi Zheng; Qin Zhao; Yue Yu; Junjie Lin (Environmental Pollution, 2025)

Capturing the spatial arrangement of POIs in crime modeling - Lin Liu; Xin Gu; Minxuan Lan; Hanlin Zhou; Debao Chen; Zihan Su (Computers, Environment and Urban Systems, 2025)

Mussel-inspired integrated functional 3D printed scaffolds with molybdenum disulfide nanoflowers for tumor therapy and bone reconstruction - Lan Li; Rongcan Wu; Ruchen Hong; Xiaolong Chen; Tingting Huang; Siyi Huang; Xianglei Mo; Zhiyi Wang; Wenge Liu; Yanjin Lu; Ye Wu; Jinxin Lin (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

Lifetime exposure to health-related air pollutants in the United Kingdom: A spatiotemporal evaluation (1930–2010) through WRF-CMAQ modeling - Ge Chen; Yiming Liu; Haofan Wang; Menghe Wang; Lan Chen; Hejun Hu; Shiyu Zhang; Baozhuo Ai; Miao Cai; Zilong Zhang; Qi Fan; Hualiang Lin (Atmospheric Environment, 2025)

Upregulation of C1QC as a Mediator of Blood–Brain Barrier Damage in Type 2 Diabetes Mellitus - Cheng Huang; Jiaxing Lin; Lan Chen; Wenzhe Sun; Jinjun Xia; Min Wu (Molecular Neurobiology, 2025)

Blue light-emitting diode promotes mineralization of stem cells from the apical papilla via cryptochrome 1/Wnt/β-catenin signaling - Lin Ye; Hao Li; Wantong Zhang; Yan Zhou; Xiaorong Lan; Yao Wang (Journal of Molecular Histology, 2025)

Investigating the Sensitivity of NIPAM Gel Dosimetry in CyberKnife Systems Using MRI-based R2 Mapping - Yu-Hsuan Lin; Shih-Wei Huang; Hung-Yi Chen; Hao-Ting Lan; Feng-Yi Su; Shin-Lei Peng; Chun-Hsu Yao (Journal of Medical and Biological Engineering, 2025)
Purpose The CyberKnife delivers precise radiation with sharp dose gradients challenging to measure. N-isopropylacrylamide (NIPAM) gel phantom can capture 3D dose distributions effectively. This study investigates the feasibility of using NIPAM gel dosimetry combined with magnetic resonance imaging (MRI)-based transverse relaxation rate (R2) mapping to verify dose distributions delivered by the CyberKnife system. Methods A total of 24 gel samples were divided into 8 dose groups (0, 3, 6, 9, 12, 15, 18, and 21 Gy), with three samples per dose group for repeat measurements. The NIPAM polymer gels were irradiated by a CyberKnife ® M6 FIM system with a 6 MV x-ray beam. MR images of the NIPAM gel phantom were made 24 h after irradiation using the 3T MRI scanner. The R2 maps corresponding to dose distribution were analyzed using Matlab software. Results Our results demonstrate that R2 values increase with rising irradiation doses, confirming dose-dependent sensitivity. The dose-response curve exhibits a slope of 0.1688 Gy⁻¹ s⁻¹, reflecting the gel dosimeter’s sensitivity, with a strong correlation (R² = 0.85, p = 0.001). Additionally, R2 values vary with depth, peaking at the 30 mm dose center point (D center ) and then gradually decreasing, indicating maximum dose accumulation at D center followed by a decline with increasing depth. Conclusion This study demonstrates that NIPAM gel dosimetry with MRI-based R2 mapping effectively verifies CyberKnife dose distributions. It exhibits strong dose sensitivity and accurately captures sharp gradients, highlighting its potential as a superior alternative to conventional dosimetry methods.

The Implementation of a MOOC-Based Flipped Classroom Teaching Method in the Context of Oncology Radiotherapy Residency Training - De-Yang Yu; Lin Zhang; Ya-Li Li; Tian Lan; Li-Na Gu; Shan-Shan Yang (Journal of Cancer Education, 2025)

Rhizosphere microecological mechanism of carbon sequestration and its emission mitigation in rice ratooning - Jinying Li; Bin Qin; Chaojie Lan; Hailong Xu; Jingnan Zou; Bianhong Zhang; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Agriculture, Ecosystems & Environment, 2025)

Unprecedented short-circuit current density and efficiency of vacuum-deposited organic solar cells based on 8H-thieno[2′,3′:4,5]thieno[3,2-b] thieno[2,3-d]pyrrole - Bin-Wen Chen; Ming-Wei An; Kang Wang; Sang Young Jeong; Xu Wang; Zhen-Lin Qiu; Kun Cao; Shan-Yu Zheng; Lu Wang; Han Young Woo; Da-Qin Yun; Lin-Long Deng; et al. (Science Bulletin, 2025)

Five brasilane-type sesquiterpenoids with neuroprotective activities from Xylaria nigripes - Hong-Ping Long; Xi Zhou; Si-Qian Zhou; Lan-Qing Li; Ai-Lin Liang; Wen-Yu Lu; Wen-Xuan Wang; Shao Liu; Jing Li; Ji-Kai Liu (Phytochemistry, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

The influence of coal price uncertainty on investment and consumption dynamics: Evidence from China - Boqiang Lin; Tianxu Lan (Energy Policy, 2025)

Blending of Sb2S3/PbS nanoparticles optimizes the CsPbI2Br perovskite/carbon electrode interface to facilitate efficient charge carrier transfer in perovskite solar cells - Fengli Liu; Haozhen Deng; Yu Jing; Lin Gao; Yuan Xu; Ruoshui Li; Chunyan Deng; Deng Wang; Zhenbo Du; Le Yang; Yicheng Cao; Jihuai Wu; et al. (Chemical Engineering Journal, 2025)

Association between low-dose ionizing radiation and hypertension: a cohort study in China - Beining Wu; Lin Song; Lan Lin; Jin Wang; Lejia Zhu; Weiling Chan; Geyang Li; Li Zhou; Zhongying Xu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Estimating the impact of 2D urban landscape patterns on extreme precipitation based on non-stationary models in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Xue Xie; Kairong Lin; Mingzhong Xiao; Tian Lan; Chunyu Dong; Jingwen Zhang; Zhaolin Fang (Science of The Total Environment, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Research on inland ship hydrodynamic modeling and parameter identification based on CFD - Shigan Ding; Mao Zheng; Sasan Tavakoli; Songlong Li; Jiafeng Lan; Bowen Lin; Tianyue Zou; Mingyang Zhang (Ocean Engineering, 2025)

Oxygen influences in vitro assessment for phenolic compounds: Digestive stability, α-glucosidase inhibitory activity and bioavailability - Yi Wang; Ruge Lin; Laiming Zhang; Suqing Lan; Xingqian Ye; Haibo Pan; Shiguo Chen (Food Chemistry, 2025)

Developing a spatial optimization design approach towards energy-saving and outdoor thermal comfortable densely-built residential blocks using a dynamic local energy balance model - Lin Liu; Zihong Zhang; Shiying Lan; Xiaoyu Tian; Jing Liu; Wei Liao; Dan Wang (Energy and Buildings, 2025)

A natural clay-based Janus micro-nanosystem with ultra-temperature resistant piezoresistive sensing and self-switching fire warning for smart fire safety - Kai Wang; Yafang Wang; Anrong Yao; Haoyi Hu; Wuhou Fan; Shaojian Lin; Jianwu Lan (Chemical Engineering Journal, 2025)

The effects of temperature on work performance in the typical office environment: A meta-analysis of the current evidence - Xi Lin; Chao Guo; Pawel Wargocki; Shin-ichi Tanabe; Kwok Wai Tham; Li Lan (Building and Environment, 2025)

Hygrothermal properties of Tibetan paper: The effects of air pressure and printed scriptures - Yige Liu; Xi Lin; Cunming Li; Yucai Guan; Chi Feng; Li Lan (Building and Environment, 2025)

Subduction-collision and rapid uplift of the NW Yangtze Block during the Ediacaran-Cambrian transition: new evidence from the shoshonite series - Qi Deng; Zheng-Jiang Wang; Hao Liu; Shuang-Jian Li; Jia-Hong Liu; Qi-Yu Wang; Jia-Shan Lin; Xiao-Wei Lan (International Geology Review, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

Genetic characterization of a novel HIV-1 circulating recombinant form (CRF162_cpx) involving CRF01_AE, CRF07_BC and subtype B in Guangdong, China - Yun Lan; Linghua Li; Mingfeng Xiao; Yaqing Lin; Xuemei Ling; Feng Li; Fengyu Hu (Virus Genes, 2025)

Self-powered photoelectrochemical sensor based on molecularly imprinted polymer-coupled CBFO photocathode and Ag2S/SnS2 photoanode for ultrasensitive dimethoate sensing - Shuqin Chen; Wanfu Lan; Dapeng Yang; Jingying Xu; Yikun Hu; Hetong Lin; Liang Feng (Analytica Chimica Acta, 2025)

ds-FCRN: three-dimensional dual-stream fully convolutional residual networks and transformer-based global–local feature learning for brain age prediction - Yutong Wu; Chen Zhang; Xiangge Ma; Xinyu Zhu; Lan Lin; Miao Tian (Brain Structure and Function, 2025)

Tea Saponins: a Novel Stabilizer for Enhancing the Oral Bioavailability of Albendazole Nanocrystals - Sumin Lan; Kexi Chen; Liqiang Feng; Panle Sima; Xiaoyao Ji; Feihua Wu; Yining Lin (AAPS PharmSciTech, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

FV-DLV3+: a light-weight flooded vegetation extraction method with attention-based DeepLabv3+ - Lin Shi; Xiaoji Lan; Xiyue Duan; Xinggen Liu (International Journal of Remote Sensing, 2025)

NLRX1 in fish: A negative regulator of innate immunity during Edwardsiella piscicida infection via targeting TRAF6 through the NACHT domain - Binliang Wang; Xuan Lan; Sihan Lin; Hong Xu; Xiaodong Zhang; Junxia Yin; Yiwei Hu (Aquaculture, 2025)

Recent advancements in antibiotics removal by bio-electrochemical systems (BESs): From mechanisms to application of emerging combined systems - Jing Tang; Zijun Li; Xinxin Xiao; Baicheng Liu; Wei Huang; Qingqing Xie; Chenrui Lan; Shuai Luo; Lin Tang (Water Research, 2025)

The crucial involvement of gamma-Mangostin and CYP1B1 in the mechanism underlying the toxicity caused by cigarette smoke extract: In silico and in vitro insights - Hao Lin; Zijian Li; Tao Zeng; Ying Wang; Lan Zhang (Toxicology, 2025)

Global occurrence, food web transfer, and human health risks of polycyclic aromatic hydrocarbons in biota - Jingqian Xie; Ruo Lan; Li Zhang; Jun Yu; Xinran Liu; Zhiyang You; Fen Yang; Tian Lin (Science of The Total Environment, 2025)

Environmental life cycle assessment on the recycling processes of power batteries for new energy vehicles - You Zhou; Xue-Dan Cui; Ai-Jun Lin; Yan Dong; Gui-Lan Duan (Journal of Cleaner Production, 2025)

Effects of sulfamethoxazole on Chlorella vulgaris growth, pollutant removal, and algal physicochemical properties in a suspended-attached microalgae culture system - Peihua Li; Lin-Lan Zhuang; Jian Zhang; Yin-Hu Wu; Hong-Ying Hu (Journal of Cleaner Production, 2025)

pH-dependent medium-chain fatty acid synthesis in waste activated sludge fermentation: Metabolic pathway regulation - Yun Wang; Shu-Lin Wu; Wei Wei; Lan Wu; Sansi Huang; Xiaohu Dai; Bing-Jie Ni (Journal of Environmental Management, 2025)

Predicting the efficiency of arsenic immobilization in soils by biochar using machine learning - Jin-Man Cao; Yu-Qian Liu; Yan-Qing Liu; Shu-Dan Xue; Hai-Hong Xiong; Chong-Lin Xu; Qi Xu; Gui-Lan Duan (Journal of Environmental Sciences, 2025)

Multifunctional nanofiber system with photothermal-controlled drug delivery and motion monitoring capabilities as intelligent wound dressing - Peiran Lin; Kaitong He; Jiahui Luo; Jiyuan Wang; Yuting Liu; Jian Zhang; Hao Fan; Shunfen Huang; Wei Lan; Wenlong Wang; Xuhui Zhang; Botao Gao; et al. (Chemical Engineering Journal, 2025)

Structural analysis and accelerating wound healing function of a novel galactosylated glycosaminoglycan from the snail Helix lucorum - Ya Li; Xingzi Wang; Jiangyan Chen; Luyun Sun; Debing Pu; Lisha Lin; Lan Luo; Xi Gong; Junxue Pu; Mingyi Wu (Carbohydrate Polymers, 2025)

Parental stress and environmental influences on children's physician-diagnosed food allergy - Chan Lu; Ying Jiang; Lin Wang; Mengju Lan; Faming Wang (Building and Environment, 2025)

Early-life exposure to outdoor temperature and the risk of childhood allergic diseases: A multicentre retrospective cohort study - Faming Wang; Lin Wang; Ying Jiang; Mengju Lan; Wenhui Yang; Zijing Liu; Chan Lu (Building and Environment, 2025)

Chronic exposure to hexavalent chromium induces esophageal tumorigenesis via activating the Notch signaling pathway - Yilin Zhu; Fanrong Liu; Lei Liu; Jinfu Wang; Fengyuan Gao; Lan Ye; Honglei Wu; Chengjun Zhou; Guimei Lin; Xiaogang Zhao; Peichao Li (Journal of Zhejiang University-SCIENCE B, 2025)

Regional sea level budget around Taiwan and Philippines over 2002‒2021 inferred from GRACE, altimetry, and in-situ hydrographic data - Wen-Hau Lan; Chi-Ming Lee; Chung-Yen Kuo; Li-Ching Lin; Eko Yuli Handoko (Journal of Geodesy, 2025)
The regional sea level budget and interannual sea level changes around Taiwan and Philippines are studied using altimetry, GRACE, and in-situ hydrographic data during 1993‒2021. Results show that the average sea level trend around Taiwan and Philippines during 1993–2021 derived from the altimetric data is 3.6 ± 0.2 mm/yr. Over 2002–2021, the study shows closure of sea level budget in the eastern ocean of Taiwan and Philippines within the observed data uncertainties, and the ocean mass accounts for 88%–100% of the observed sea level rise. In contrast, the sea level budget is not closed in the western ocean of Taiwan and Philippines, probably due to the lack of complete coverage by in-situ ocean observing systems. In addition, both regional sea level anomalies and their steric component around Taiwan and Philippines exhibit pronounced interannual and decadal variabilities. The trade wind stress associated with El Niño–Southern Oscillation and Pacific Decadal Oscillation offers a compelling explanation for the interannual and decadal signals of sea level anomalies in the southern ocean of Taiwan, with negative correlations of − 0.78 to − 0.64, indicating that trade wind stress makes a negative contribution to interannual-to-decadal sea level variability. In the northwestern ocean of Taiwan, the sea level variation is strongly influenced by the local monsoon system and shallow bathymetry with an annual amplitude of 90.3 ± 2.9 mm, larger than those in other regions around Taiwan and Philippines, where ocean mass is dominant with a high correlation with the sea level (+ 0.75 to + 0.78).

Metagenomic Analysis of Gut Microbiome of Persistent Pulmonary Hypertension of the Newborn - Linli Han; Chuyang Lin; Yue Lan; Yimin Hua; Jinlin Wu; Zhenxin Fan; Yifei Li (Cardiovascular Toxicology, 2025)

From alleys to arterial streets: Unpacking the influence of diverse street types and associated business on urban theft patterns - Debao Chen; Lin Liu; Xin Gu; Minxuan Lan; Zihan Su; Hanlin Zhou (Applied Geography, 2025)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Long-term subculture induces syncytialization and influent the response to bisphenol A (BPA) of placental JEG-3 cells - Yu-Shiuan Huang; Ai-An Chang; Zhi-Jie Yang; Jung-An Chen; Chi-Kang Lin; Hsin-Chieh Lan (Reproductive Toxicology, 2024)

Functional characterization of four antenna-enriched odorant binding proteins in Rhaphuma horsfieldi reveals the importance of RhorOBP1 in odorant recognition and insecticide resistance - Yin-Lan Liang; Shun-Si Li; Ning-Na Yin; Shu-Lin Li; Yu-Yue Lu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Single-cell atlases reveal leaf cell-type-specific regulation of metal transporters in the hyperaccumulator Sedum alfredii under cadmium stress - Guo Yu; Jingyu Xiang; Jie Liu; Xuehong Zhang; Hua Lin; Geoffrey I. Sunahara; Hongwei Yu; Pingping Jiang; Huachun Lan; Jiuhui Qu (Journal of Hazardous Materials, 2024)

Room-temperature synthesis of carbon polymer dots from biomass for advanced sensing and fluorescent applications - Lin Lan; Rui Bao; Xin Kong; Liang Liu; Jinsong Wang; Jianhong Yi (Journal of Environmental Chemical Engineering, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

Effect of multi-processing technologies on the quality of sweet potato starch and associated starch pearl products - Min-Yu Lan; Jer-An Lin; Sheng-Yi Chen; Gow-Chin Yen (Food Bioscience, 2024)

Metagenomic analysis manifesting intrinsic relatedness between antibiotic resistance genes and sulfate- and iron-reducing microbes in sediment cores of the Pearl River Estuary - Zhaohong Li; Lan Lin; Xiuqin Xie; Lili Ming; Songzhang Li; Lan Liu; Ke Yuan; Li Lin; Ligang Hu; Tiangang Luan; Baowei Chen (Environmental Pollution, 2024)

Investigating carbon peak prediction scenarios and implementation strategies in higher education institutions: A case study of Shandong Jianzhu university - Qianmiao Yang; Lan Wang; Ran Huo; Weihua Lin; Xiaofeng Li (Energy and Buildings, 2024)

Enhancing the efficiency and stability of carbon-based perovskite solar cells through treatment of the CsPbI2Br surface with neostigmine bromide - Lin Gao; Fengli Liu; Yongsheng Tu; Ruoshui Li; Dongbin Jiang; Zhenbo Du; Jihuai Wu; Zhang Lan (Chemical Engineering Journal, 2024)

The construction of a peptide vaccine with multifunctional DNA tetrahedron exoskeleton - Jiale Liang; Xin Qin; Siqi Xu; Mei Zhang; Lan Yao; Zhiqiang Liu; Geru Zhang; Taoran Tian; Yunfeng Lin (Chemical Engineering Journal, 2024)

New insight into Clostridium butyricum-ferroferric oxide hybrid system in exogenous carbon dioxide-assisted anaerobic fermentation for acetate and butyrate production - Panyu Li; Zhiwen Lin; Chenyi Li; Qingyi Luo; Sishuo Weng; Yue Zeng; Zhenzhen Lan; Wei Wang; Yongkui Zhang (Bioresource Technology, 2024)

Outstanding enhancement of caproate production with microwave pyrolyzed highly reductive biochar addition - Qinglian Wu; Lin Deng; Tian Lan; Hui Wang; Kaiming Wang; Huacheng Zhu; Yanping Zhou; Wanqian Guo (Bioresource Technology, 2024)

Parental stress interaction with environmental factors in childhood allergic asthma: Early life significance - Chan Lu; Lin Wang; Mengju Lan; Ying Jiang; Faming Wang (Building and Environment, 2024)

The endonuclease FEN1 mediates activation of STAT3 and facilitates proliferation and metastasis in breast cancer - Min Wu; Xiaoshan Huang; Benmeng Wu; Miaolin Zhu; Yaqin Zhu; Lin Yu; Ting Lan; Jingjing Liu (Molecular Biology Reports, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

Genome-Wide Characterization of ABC Transporter Genes and Expression Profiles in Red Macroalga Pyropia yezoensis Expose to Low-Temperature - Lin Tian; Lan Wu; Xue-Feng Zhong; Li-Hong Ma; Guo-Ying Du (Marine Biotechnology, 2024)

On the Revival Mechanism of Typhoon Doksuri (2023) Remnants after Its Landfall - Chunyi Xiang; Lin Dong; Yu Lan; Hui Wang; Runling Yu; Xiaoyong Zhuge; Da Liu; Qian Wang (Journal of Meteorological Research, 2024)

Phytotoxicity of Prussian blue nanoparticles to rice and the related defence mechanisms: In vivo observations and physiological and biochemical analysis - Kai Xu; Yilun Lan; Chenghua Xing; Yuchun Rao; Engao Zhu; Jianfang Yan; Shaobin Wang; Xi-Lin Wu; Miaozhen Cai; Xiaoguang Duan (Chemosphere, 2024)

Diurnal contrast of urban park cooling effects in a “Furnace city” using multi-source geospatial data and optimal parameters-based geographical detector model - Xiong Yao; Baojian Ye; Yuxiang Lan; Zhongli Lin; Zhipeng Zhu; Feng Yang; Xianjun Zeng (Sustainable Cities and Society, 2024)

The spatial variations and driving factors of C, N, P stoichiometric characteristics of plant and soil in the terrestrial ecosystem - Wen-Lan Feng; Jin-Ling Yang; Li-Gang Xu; Gan-Lin Zhang (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Cadmium contamination in sediments from a mangrove wetland: Insights from lead isotopes - Zhenghua Tao; Tianxiang Xia; Fengyuan Chen; Lina Zhang; Rongfei Wei; Shanshan Chen; Lin Jia; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2024)

One-stone-for-two-birds strategy to achieve effective electrochemical nitrate reduction towards ammonia synthesis with Ru doped cobalt tungstate - Xue Bai; Keyu Zhou; Lan Lin; Huiying Li; Qianggen Li; Guangyin Fan (Fuel, 2024)

Rapid and simultaneous detection of cadmium and mercury in foods based on solid sampling integrated electrothermal vaporization technique - Hongyu Jia; Guanyu Lan; Xue Li; Lin Chen; Li Feng; Xuefei Mao (Food Chemistry, 2024)

Monoclonal antibody based colloidal gold immunochromatographic assay for the visual and rapid screening of profenofos - Ri-Sheng Chen; Jian-Cheng Yuan; Chong-Lan Luo; Yu Wang; Zi-Jian Chen; Ze-Shan Lin; Zhen-Lin Xu (Environmental Pollution, 2024)

Regulating cobalt-nitrogen function centers via Cu incorporation enhances ciprofloxacin destruction through peroxymonosulfate activation - Qiulin Li; Jieling Huang; Lan Lin; Guangyin Fan (Environmental Pollution, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Dielectric screening modulating charge carrier recombination in high-performance of CsPbI2Br carbon-based perovskite solar cells - Fengli Liu; Yuan Xu; Ruoshui Li; Chunyan Deng; Lin Gao; Haozhen Deng; Yu Jing; Dongbin Jiang; Qing Yao; Chenfang Zhong; Deng Wang; Jihuai Wu; et al. (Chemical Engineering Journal, 2024)

Novel flow field design for redox flow battery using algorithmic channel generation and self-adaptive network model and experimental verification - Wei-Wei Yang; Ren-Zhong Zhang; Meng-Yue Lu; Yi-Wan Lin; Lan-Xin Liang; Qian Xu (Chemical Engineering Journal, 2024)

Insight into the nonradical selective oxidation mechanism for versatile organic pollutants removal by perovskite activated peroxymonosulfate system - Qiao Wang; Xinhong Lin; Yifan Liu; Meirui Yu; Weikang Xu; Huarui Li; Nan Lan (Chemical Engineering Journal, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

White matter microstructure damage measured by automated fiber quantification correlates with pain symptoms in lung cancer patients - Li Ran; Jiang Liu; Xiaosong Lan; Xiaoyu Zhou; Yong Tan; Jing Zhang; Yu Tang; Lin Tang; Jiuquan Zhang; Daihong Liu (Brain Imaging and Behavior, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Rnai-based functional analysis of bursicon genes related to cuticle pigmentation in a ladybird beetle - Lan-Lan Liao; Wen-Ze Li; Lin Jin; Guo-Qing Li (Journal of Insect Physiology, 2024)

Hydroxyl radical mediated extracellular degradation of tetracycline under aerobic and anaerobic conditions stimulated by bio-FeS nanoparticles - Huixia Lan; Ke Li; Qiliang Cao; Qiaochu Liang; Yecheng Lin; Veeriah Jegatheesan; Binghua Yan; Heng Zhang; Yang Zhang (Journal of Hazardous Materials, 2024)

κ-Carrageenan masking bitterness perception in surimi gels containing potassium chloride-based salt substitutes: Gel properties, oral processing, and sensory evaluation - Ni He; Xinran Chen; Lin Li; Shaoyun Wang; Meijuan Lan; Yi Yuan; Zhenhui Zhang; Tongshuai Li; Xia Zhang; Xing He; Bing Li (Food Chemistry, 2024)

Multimodal enhancement of ferroptosis for synergistic cascade colorectal cancer therapy - Ziying Wu; Kun Chen; Weisheng Mo; Yue Wang; Xiewei Lin; Zhien Lan; Caijing Mo; Haocheng Wang; Xiaoying Li; Xingdi Fan; Hungchen Chen; Zhilin Shu; et al. (Chemical Engineering Journal, 2024)

Fluorinated metal-organic framework aerogels with enhanced moisture resistance and efficient gas diffusion for CO2 capture - Huijuan Zhao; Feifei Lan; Hang Wang; Shaojuan Chen; Guodong Zhao; Tong Lin; Xupin Zhuang (Chemical Engineering Journal, 2024)

Enhancing plant fiber antibacterial and antiviral performance through synergistic action of amino and sulfonic acid groups - Jinxin Lan; Yao Wu; Jiazhen Chen; Peng Wang; Hui Chen; Jinfeng Huang; Dongdong Lu; Changmei Lin; Xiaojuan Ma; Shilin Cao (Carbohydrate Polymers, 2024)

Characteristics of acidic hydrothermal treatment for disintegration of spiramycin fermentation residue and degradation of residual antibiotics - Gang Wang; Quancheng Shu; Jinzhi Sun; Yucan Liu; Xiaoyong Yang; Hao Lin; Jing Ding; Yanxiang Zhang; Lijuan Lan; Hongwei Sun (Bioresource Technology, 2024)

Design, synthesis, X-ray crystal structure, and antimicrobial evaluation of novel quinazolinone derivatives containing the 1,2,4-triazole Schiff base moiety and an isopropanol linker - Lan Yang; Muhan Ding; Jun Shi; Na Luo; Yuli Wang; Dongyun Lin; Xiaoping Bao (Molecular Diversity, 2024)

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

Nondestructive estimation of specific macroelement contents in thalli of the red macroalga Pyropia yezoensis using hyperspectral imaging - Shuai Che; Lan Wu; Zhen-Dong Wang; Lin Tian; Guo-Ying Du; Yun-Xiang Mao (Journal of Applied Phycology, 2024)

The effects of dietary supplementation of ginseng stem and leaf saponins on the antioxidant capacity, immune response, and disease resistance of crucian carp, Carassius auratus - Ying-da Wang; Xin Meng; Yong-chao Guan; Ze-lin Zhao; Luo-tao Tao; Jin-shuo Gong; Xin-lan Liu; Yan Zhao; Xiao-feng Shan (Fish Physiology and Biochemistry, 2024)

Insights gained into the injury mechanism of drug and herb induced liver injury in the hepatic microenvironment - Xiaomeng Zhang; Qi Geng; Lin Lin; Lulu Zhang; Changqi Shi; Bin Liu; Lan Yan; Zhiwen Cao; Li Li; Peipei Lu; Yong Tan; Xiaojuan He; et al. (Toxicology, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Analytical behavior of concrete-filled steel tubular pile used in coastal wharf structure subjected to combined loads - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2024)

Fe(II)-mediated Fe–N–P metabolism in an anammox-dominated system for enhanced nitrogen removal and Fe–P crystals (FePs) production - Biru Zhou; Lan Lin; Qian Zhang; Ying Wang; Zikun Zhang; Xiaoqing Xie; Wenzhi Cao; Yu-You Li; Yanlong Zhang (Journal of Cleaner Production, 2024)

On the modification of plant proteins: Traditional methods and the Hofmeister effect - Ziming Wang; Tiantong Lan; Jing Jiang; Tingyu Song; Jingsheng Liu; Hao Zhang; Ke Lin (Food Chemistry, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

An artificial neural network based approach to air supply control in large indoor spaces considering occupancy dynamics - Bo Lan; Ruichao Zhang; Zhun Jerry Yu; Borong Lin; Gongsheng Huang (Building and Environment, 2024)

Mixing with Schima Superba Enhanced Soil Fertility and Simplified Soil Microbial Community of Eucalyptus Urophylla Forests - Wentao Hu; Jinrui Chen; Mengyao Liu; Xueqin Tian; Xuemei Chen; Wei Lin; Zuying Xuan; Lan Pan (Journal of Soil Science and Plant Nutrition, 2024)

Production of cleavage-resistant phytase transgenic pigs by handmade cloning - Mingyuan Zhang; Jun Zhang; Haowen Yang; Shijin Chen; Xiaoliang Chen; Yuemeng Huang; Baojian Chen; Yanjun Wu; Qinyang Jiang; Yafen Guo; Yingming Wei; Xiukun Lin; et al. (Theriogenology, 2024)

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Optimization and mechanism of strengthened biological contact oxidation for rural domestic wastewater treatment - Yingfei Li; Shuhan Ge; Jialin Luan; Yanzhe Wang; Lin-Lan Zhuang; Jian Zhang (Journal of Water Process Engineering, 2024)

General performance, kinetic modification, and key regulating factor recognition of microalgae-based sulfonamide removal - Lin-Lan Zhuang; Weiyi Qian; Xiaoxiong Wang; Tong Wang; Jian Zhang (Journal of Hazardous Materials, 2024)

Quick calibration of massive urban outdoor surveillance cameras - Lin Shi; Xiaoji Lan; Xin Lan; Tianliang Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Screening and identification of selenium-enriched purine-lowering Lactobacillus plantarum and Lactococcus lactis with high stress tolerance and antioxidant capacity - Jia-Jun Liao; Cai-Yue Tan; Lan Liang; Yi-Zhen Luo; Hong-Lin Li; Yan-Yi Chen; Xiao-Dong Pei; Cheng-Hua Wang (Food Bioscience, 2024)

Challenges and enhancement technologies of medium chain carboxylates production in open culture anaerobic fermentation - Shu-Lin Wu; Lan Wu; Wei Wei; Jiali Shentu; Yuyang Long; Dongsheng Shen; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Enhanced sludge granulation and stable performance of an anammox expanded granular sludge bed (EGSB) reactor through the utilization of hydroxyapatite (HAP) particles - Lan Lin; Ying Song; Yanlong Zhang; Zibin Luo; Qian Li; Wenzhi Cao; Yu-You Li (Bioresource Technology, 2024)

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

Application of C30 tetracyclic polyprenoids as effective biomarker in oil-to source rock correlation in the Zhu III depression, Zhujiangkou Basin, northern South China - Lei Lan; Youchuan Li; Shuchun Yang; Yang Ouyang; Wenjing Ding; Qing Lin; Shanshan Zhou (Acta Oceanologica Sinica, 2024)

Molecular cloning, tissue distribution and nutritional regulation of four acyl-coenzyme A oxidase (acox) isoforms in Scylla paramamosain - Lin Zhideng; Lan Jinjie; Lin Huangbin; Huang Chaoyang; Zhang Mingyao; Huang Qincheng (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of peroxisomal β-oxidation, acyl-coenzyme A oxidase (ACOXs) play vital roles in maintaining energy homeostasis and regulating reactive oxygen species (ROS) metabolism. However, there are no studies on the functions of ACOXs in crustaceans. In the present study, four full-length cDNA sequences of acoxs , namely the acox-1a (2403 bp), acox-1b (2733 bp), acox-3a (2878 bp) and acox-3b (3445 bp), were successfully isolated from mud crab Scylla paramamosain , which encoded 666, 673, 701 and 658 amino acids, respectively. Sequence analysis showed that the ACOX-1a, ACOX-1b and ACOX-3a possessed conserved structural domains like FAD-binding motif, fatty acyl CoA oxidase domain and peroxisomal targeting signal, while the ACOX-3b lacked peroxisomal targeting signal. Results of phylogenetic tree indicated that the four ACOXs of mud crab grouped gathered with their corresponding orthologues from crustaceans. The acox-1a , acox-3a and acox-3b were highly expressed in hepatopancreas, and the acox-1b was mainly distributed in muscle and hepatopancreas. Compared with feeding groups, the expression levels of acox-1a , acox-3a and acox-3b in hepatopancreas and acox-3a in muscle were markedly up-regulated in fasting groups, suggesting that the acoxs had significant effects in modulating energy balance during fasting. In addition, fasting significantly increased the transcriptional levels of nuclear factor erythroid 2-related factor ( nrf2 ) and its downstream antioxidant genes (catalase ( cat ), glutathione peroxidase ( gpx ) and glutathione S-transferase ( gst )) to improve antioxidant capacity for removing excessive ROS produced by ACOX-mediated peroxisomal β-oxidation. These results would be conducive to providing new insights into evolutionary characteristics and functions of acoxs in crustaceans.

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Phylogenomics and biogeographical diversification of Collabieae (Orchidaceae) and its implication in the reconstruction of the dynamic history of Asian evergreen broadleaved forests - Hong-Yu Ji; Chao Ye; Yan-Qiong Chen; Jian-Wu Li; Arief Hidayat; Jiang-Lin Miao; Jian-Hua Li; Jian-Yong Wu; Jun-Wen Zhai; Si-Ren Lan; Xiao-Hua Jin (Molecular Phylogenetics and Evolution, 2024)

Children's food allergy: Effects of environmental influences and antibiotic use across critical developmental windows - Chan Lu; Ying Jiang; Mengju Lan; Lin Wang; Wanzhen Zhang; Faming Wang (Journal of Hazardous Materials, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

Long-term exposure to ambient ozone and adult-onset asthma: A prospective cohort study - Jiayue Zhang; Baozhuo Ai; Yuming Guo; Lan Chen; Ge Chen; Haitao Li; Hualiang Lin; Zilong Zhang (Environmental Research, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Geoarchaeological evidence of an ancient landslide dam (13–4.7 ka) and consequent outburst flood on the Minjiang River near Wenchuan, China - Niannian Fan; Xingguo Yang; Michael J. Storozum; Xuefeng Cheng; Lan Li; Weiming Liu; Zhipeng Lin; Xingnian Liu (CATENA, 2024)

Interspecies electron transfer and microbial interactions in a novel Fe(II)-mediated anammox coupled mixotrophic denitrification system - Ying Wang; Zikun Zhang; Lan Lin; Guowei Xing; Yushi Jiang; Wenzhi Cao; Yanlong Zhang (Bioresource Technology, 2024)

Has benchmarking improved the performance of the Australian electricity distribution utilities? A meta-frontier model - Lin-Lan Bu; Maria Kopsakangas-Savolainen; Bai-Chen Xie; Hong-Zhou Li; Yi-Meng Liu; Shao-Peng Yin (Utilities Policy, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

A balanced staple food structure effectively curbs the environmental impact and counters the nutrient losses from elevated CO2 - Jingjing Yin; Jianyi Lin; Xinhuan Zhang; Lan Wang; Mingliang Liu (Resources, Conservation and Recycling, 2024)

Vegetation greening accelerated hydrological drought in two-thirds of river basins over China - Xin Lan; Yuying Xie; Zhiyong Liu; Ting Yang; Liyan Huang; Xinrong Chen; Xiaohong Chen; Kairong Lin; Linyin Cheng (Journal of Hydrology, 2024)

Against catalyst deactivation during toluene oxidation on CuCeOx in flue gas: High oxidation efficiency and rapid oxidation pathway - Ziyang Guo; Beilong Lin; Jiali Tang; Jinhang Yang; Lan Fan; Mingli Fu; Daiqi Ye; Yun Hu (Journal of Environmental Chemical Engineering, 2024)

Role of rainfall temporal distribution on effective infiltration in the loess slope and prediction model - Gan Lin; Hengxing Lan; Ping Li; Langping Li; Shijie Liu; Weifeng Sun (Engineering Geology, 2024)

A dual-network structured poly (m-phenylene isophthalamide) nanofiber separator with Li6.4La3Zr1.4Ta0.6O12 for dendrite-free and high-safety lithium-metal batteries - Huijuan Zhao; Guodong Zhao; Fengquan Liu; Feifei Lan; Jianjun Zhou; Lin Li (Chemical Engineering Journal, 2024)

Identification of Key Factors in Cartilage Tissue During the Progression of Osteoarthritis Using a Non-targeted Metabolomics Strategy - Shiyu Sun; Minghui Chen; Tingting Zhang; Yanyan Wang; Weijun Shen; Tao Zhang; Jian Liu; Haidan Lan; Jianyuan Zhao; Fuqing Lin; Xuan Zhao (Phenomics, 2024)
This research was to reveal the key factors in the progression of osteoarthritis (OA) using non-targeted metabolomics and to find targeted therapies for patients with OA. Twenty-two patients with knee OA scheduled for total knee arthroplasty were divided into two groups: Kellgren–Lawrence (KL) grade 3 ( n = 16) and grade 4 ( n = 6), according to plain X-rays of the knee. After the operation, the cartilages of femur samples were analyzed using non-targeted metabolomics. When compared with grade 3 patients, the levels of choline, 2-propylpiperidine, rhamnose, and monomethyl glutaric acid were higher; while 1-methylhistamine, sphingomyelin (SM) (d18:1/14:0), zeranol, 3- (4-hydroxyphenyl)-1-propanol, 5-aminopentanamide, dihydrouracil, 2-hydroxypyridine, and 3-amino-2-piperidone were lower in grade 4 patients. Furthermore, some metabolic pathways were found to be significantly different in two groups such as the pantothenate and coenzyme A (CoA) biosynthesis pathway, the glycerophospholipid metabolism pathway, histidine metabolism pathway, lysine degradation pathway, glycine, serine and threonine metabolism pathway, fructose and mannose metabolism pathway, the pyrimidine metabolism pathway, and beta-alanine metabolism pathway. This work used non-targeted metabolomics and screened out differential metabolites and metabolic pathways, providing a reliable theoretical basis for further study of specific markers and their specific pathways in the progression of OA.

Causal Association of Cytokines and Growth Factors with Stroke and Its Subtypes: a Mendelian Randomization Study - Gengbin Chen; Tuo Lin; Manfeng Wu; Guiyuan Cai; Cheng Wu; Qian Ding; Jiayue Xu; Hongying Chen; Wanqi Li; Guangqing Xu; Yue Lan (Molecular Neurobiology, 2024)

Waste treats waste: Facile fabrication of porous adsorbents from recycled PET and sodium alginate for efficient dye removal - Jing Yu; Lan Bai; Zijun Feng; Lin Chen; Shimei Xu; Yuzhong Wang (Chemosphere, 2024)

Secondary infections may cause host mortality by inhibiting NRF1-mediated antiviral immune responses - Xu Feng-Lin; Wang Cheng-Qiang; Yin Cheng-Ming; Sun Ya-Nan; Cao Xiao-Tong; Lan Jiang-Feng (Aquaculture, 2024)

Atmospheric CO2 in the megacity Hangzhou, China: Urban-suburban differences, sources and impact factors - Yuanyuan Chen; Yanran Lu; Bing Qi; Qianli Ma; Kunpeng Zang; Yi Lin; Shuo Liu; Fengmei Pan; Shan Li; Peng Guo; Lihan Chen; Wengang Lan; et al. (Science of The Total Environment, 2024)

The rhizosphere microbiome reduces the uptake of arsenic and tungsten by Blechnum orientale by increasing nutrient cycling in historical tungsten mining area soils - Xiaolong Lan; Zengping Ning; Yanlong Jia; Wenjie Lin; Enzong Xiao; Qianyun Cheng; Qiaoxue Cai; Tangfu Xiao (Science of The Total Environment, 2024)

Ferrocene-functionalized zirconium-oxo clusters for achieving high-performance thermocatalytic redox reactions - Su-Juan Yao; Jiao-Min Lin; Long-Zhang Dong; Ying-Lin Li; Ning Li; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

A review on geological storage of marine carbon dioxide: Challenges and prospects - Jinzhou Zhao; Jianchao Zheng; Lan Ren; Ran Lin; Bo Zhou (Marine and Petroleum Geology, 2024)

Long-term toxicity assessment of antibiotics against Vibrio fischeri: Test method optimization and mixture toxicity prediction - Shuhan Ge; Wanqing Tian; Ziyi Lou; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Journal of Hazardous Materials, 2024)

Causal association between long-term exposure to air pollution and incident Parkinson’s disease - Baozhuo Ai; Jiayue Zhang; Shiyu Zhang; Ge Chen; Fei Tian; Lan Chen; Haitao Li; Yuming Guo; Angela Jerath; Hualiang Lin; Zilong Zhang (Journal of Hazardous Materials, 2024)

Comparative analysis of characteristics of antibiotic resistomes between Arctic soils and representative contaminated samples using metagenomic approaches - Xiuqin Xie; Baoying Chen; Siqi Zhu; Ruiqiang Yang; Ke Yuan; Ying Yang; Ruohong Chen; Lan Lin; Baowei Chen (Journal of Hazardous Materials, 2024)

Investigation of bioactive compounds and their correlation with the antioxidant capacity in different functional vinegars - Hua Bai; Shuang Wang; Zong-Min Wang; Lan-Lan Zhu; Hong-Bo Yan; Yan-Bo Wang; Xin-Yu Wang; Lin Peng; Ji-Zhou Liu (Food Research International, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

PHB2 inhibits WSSV replication by promoting the nuclear translocation of STAT - Jia-Yu Si; Lian-Jie Wu; Feng-Lin Xu; Xiao-Tong Cao; Jiang-Feng Lan (Fish & Shellfish Immunology, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Role of sea salt in modulating biomass-to-biocrude conversion via hydrothermal liquefaction - Xiaoyu Lin; Wangfang Ye; Yifan Mao; Zhiyu Li; Qian Lan; Quan He; Kang Kang; Liang Zhang; Tao Shui; Yulong Wu; Xiaomei Zhong; Jie Yang (Desalination, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Buried interface modulation by rubidium dihydrogen phosphate towards highly effective perovskite solar cells - Puzhao Yang; Jihuai Wu; Wenhui Lin; Xiaoyuan Jiang; Ying Wang; Weihai Sun; Zhang Lan; Jianming Lin (Chemical Engineering Journal, 2024)

Interactions and coupling mechanisms between Anammox, partial denitrification (PD) and hydroxyapatite (HAP) biomineralization in a PD/A-HAP system - Haozhe Mo; Lan Lin; Qian Zhang; Zikun Zhang; Jih-Gaw Lin; Wenzhi Cao; Yanlong Zhang (Chemical Engineering Journal, 2024)

Boosted outputs and robustness of polymeric tribovoltaic nanogenerator through secondary doping - Jia Meng; Chuntao Lan; Chongxiang Pan; Jun Yang; Xiong Pu; Zhong Lin Wang (Chemical Engineering Journal, 2024)

Self-healing, environmentally stable and adhesive hydrogel sensor with conductive cellulose nanocrystals for motion monitoring and character recognition - Yafang Wang; Anrong Yao; Baojie Dou; Cuimin Huang; Lin Yang; Juan Liang; Jianwu Lan; Shaojian Lin (Carbohydrate Polymers, 2024)

Effects of chemical oxygen demand and chloramphenicol on attached microalgae growth: Physicochemical properties and microscopic mass transfer in biofilm - Peihua Li; Yanan Yang; Lin-Lan Zhuang; Zhen Hu; Lijie Zhang; Shuhan Ge; Weiyi Qian; Wanqing Tian; Yinhu Wu; Hong-Ying Hu (Bioresource Technology, 2024)

Molecular detection and genetic characteristics of porcine circovirus 3 and porcine circovirus 4 in central China - Lin-Qing Wang; Jia-Xin Li; Xi-Meng Chen; Xin-Yue Cao; Hong-Lei Zhang; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2024)

Spatio-seasonal patterns and sources of major ions in the Longjiang River catchment, Southern China - Xiaolong Lan; Zengping Ning; Qingxiang Xiao; Haiyan Chen; Yanlong Jia; Wenjie Lin (Environmental Science and Pollution Research, 2024)

Tree barriers height information extraction under power line based on watershed segmentation and local maximum algorithm - Yan Li; Lv Zhou; Xue Lin Wen; Tai Ying Wu; Mian Lan; Di Zhang; Yi Zhan Zhao; Peng De Lai (International Journal of Remote Sensing, 2024)

Spatially selective defect management of CsPbI3 films for high-performance carbon-based inorganic perovskite solar cells - Hailiang Wang; Qixian Zhang; Zedong Lin; Huicong Liu; Xiaozhen Wei; Yongfa Song; Chunyu Lv; Weiping Li; Liqun Zhu; Kexiang Wang; Zhenhua Cui; Lan Wang; et al. (Science Bulletin, 2024)

Efficacy and mechanism of copper removal from electroplating wastewater by schwertmannite-like mineral - Ni Li; Mingyan Shi; Yimiao Lan; Hongguo Zhang; Guanfeng An; Shaonan Lin; Langming Xue (Journal of Environmental Chemical Engineering, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Absorption and utilization of polysaccharides from Cordyceps militaris fruiting bodies and their protective effects against CCl4-induced acute liver injury in mice - Lin Lan; Jingxin Wang; Hao Luo; Min Cao; Nianhong Guo; Guiling Fan; Shengyu Wang; Zaixing Sun; QiaoLing He; Yufeng Li (Food Bioscience, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Interaction of life-time and early-life exposure to antibiotics and indoor environmental factors on childhood plant allergy - Chan Lu; Mengju Lan; Lin Wang; Ying Jiang; Bin Li; Faming Wang (Building and Environment, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Molecular cloning and characterization of three carnitine palmitoyltransferase (cpt) isoforms from mud crab (Scylla paramamosain) and their roles in respond to fasting and ambient salinity stress - Zhideng Lin; Chaoyang Huang; Zhengrui Zhuo; Jun Xie; Hongliang Lan; Bixing Hu; Chengkang Zhang; Kunhuang Han; Weiqing Huang (Frontiers in Marine Science, 2024)
As rate-limiting enzymes of β-oxidation of fatty acids in mitochondria, the carnitine palmitoyltransferase (CPT) played an important role in regulating energy homeostasis of aquatic animals. However, there was very little research on β-oxidation of fatty acids in crustaceans. In the present study, the full-length cDNA sequences of cpt-1a , cpt-1b and cpt-2 were isolated from the hepatopancreas of Scylla paramamosain , and contained 4206, 5303 and 3486 bp respectively. Sequence analysis showed that the CPT-1A, CPT-1B and CPT-2 encoded proteins with 777, 775 and 672 amino acids respectively, and only the CPT-1A possessed a transmembrane region. In addition, both the CPT-1B and CPT-2 contained conservative functional domains like N-terminal domain and acyltransferases choActase 2, while the CPT-1A lacked. The results of phylogenetic tree indicated that the CPT-1A, CPT-1B and CPT-2 of S. paramamosain gathered together with their corresponding orthologues from crustaceans. The tissue distribution exhibited that the cpt-1a was highly expressed in hepatopancreas, followed by muscle, eyestalk and cranial ganglia, and the muscle, eyestalk and heart were main expressed tissues of cpt-1b . Furthermore, the high expression levels of cpt-2 were mainly detected in hepatopancreas, muscle and heart. The transcriptional levels of cpt-1a , cpt-1b and cpt-2 were significantly up-regulated under chronic low salinity stress. Besides, at the acute low salinity stress condition, the expression levels of cpt-1a , cpt-1b and cpt-2 in hepatopancreas were dramatically increased in 14‰ and 4‰ salinity groups at the 6h and 48h, while the transcriptional levels of cpt-1a , cpt-1b and cpt-2 in muscle were signally up-regulated in 14‰ and 4‰ salinity groups at the 12h and 24h, showing an alternate response pattern. Similarly, the present study found that fasting could markedly increase the expression levels of cpt-1a , cpt-1b and cpt-2 in hepatopancreas and muscle, especially cpt-1a in hepatopancreas as well as cpt-1a and cpt-1b in muscle. The results above indicated that the cpt-1a , cpt-1b and cpt-2 played a crucial part in providing energy for coping with fasting and salinity stress. These results would contribute to enhancing the knowledge of cpt phylogenetic evolution and their roles in energy metabolism of crustaceans.

Effective activation of peroxymonosulfate by CoCr-LDH for removing organic contaminants in water: from lab-scale to practical applications - Nguyen Trung Dung; Do Thi Hong Ha; Vu Dinh Thao; Nguyen Phuong Thao; Tran Dai Lam; Pham Thi Lan; Tran Thi Trang; Le Viet Ngan; Bui Dinh Nhi; Nguyen Thi Thuy; Kun-Yi Andrew Lin; Nguyen Nhat Huy (Environmental Science and Pollution Research, 2024)

Efficient removal and transformation of Cr(VI) from alkaline wastewater to form a ferrochromium spinel multiphase via a modified ferrite process - Yingying Lan; Yiwei Sun; Shasha Chu; Bo Yang; Lijuan Zhang; Lin Xiao; Jinlin Li; Xiaochao Yuan; Xin Yan; Vladimir V. Galvita; Xintai Su (Chemosphere, 2024)

Artificial humic acid coated ferrihydrite strengthens the adsorption of phosphate and increases soil phosphate retention - Shuang Gai; Bing Liu; Yibo Lan; Lin Han; Yixiong Hu; Guanghao Dongye; Kui Cheng; Zhuqing Liu; Fan Yang (Science of The Total Environment, 2024)

Effect of injecting inert gas at different spontaneous combustion stages on active groups in coal - Xiaoyuan Jiang; Shengqiang Yang; Buzhuang Zhou; Lin Lan (Fuel, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Ultrasonic treatment treated sea bass myofibrillar proteins in low-salt solution: Emphasizing the changes on conformation structure, oxidation sites, and emulsifying properties - Meijuan Lan; Tongshuai Li; Lin Li; Shaoyun Wang; Juncheng Chen; Tangyu Yang; Zhiru Li; Yipeng Yang; Xia Zhang; Bing Li (Food Chemistry, 2024)

Unveiling the aromatic intricacies of Wuyi Rock Tea: A comparative study on sensory attributes and odor-active compounds of Rougui and Shuixian varieties - Daoliang Wang; Zhibin Liu; Xiaoye Lan; Cainan Wang; Wensong Chen; Sijia Zhan; Yaqian Sun; Weiying Su; Chih-Cheng Lin; Wei Liu; Yuan Liu; Li Ni (Food Chemistry, 2024)

Characterization of type II IFNs and their receptors in a cyprinid fish, the blunt snout bream Megalobrama amblycephala - Bo Li; Shan Nan Chen; Lin Huang; Li Li; Li Ren; Jing Hou; Jing Yun Tian; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2024)

Highly active and stable VOx/TiO2 nanosheets for low-temperature NH3-SCR of NO: Structure-directing role of support - Liang-Yi Lin; Yu-Chen Wang; Zi-Lan Liu (Chemical Engineering Journal, 2024)

Association between occupational noise and obesity: a retrospective cohort study in China - Geyang Li; Weile Wu; Li Zhou; Weiling Chan; Jin Wang; Lejia Zhu; Lin Song; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

The adsorption and release mechanism of different aged microplastics toward Hg(II) via batch experiment and the deep learning method - Lianghong Li; Bin Xue; Haiying Lin; Wenlu Lan; Xinyi Wang; Junqi Wei; Mingen Li; Mingzhi Li; Yu Duan; Jiatong Lv; Zixuan Chen (Chemosphere, 2024)

Occurrence of leaf spot caused by Colletotrichum plurivorum on cowpea in Fujian Province, China - Yuli Dai; Lin Gan; Xiaofei Liu; Chengzhong Lan; Zhiqiang Li; Xiujuan Yang (Crop Protection, 2024)

The economic feasibility of aquavoltaics in Taiwan - A case study of whiteleg shrimp (Litopenaeus vannamei) culture - Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou; Hsun-Yu Lan; Cheng-Ting Huang; Fan-Hua Nan (Aquaculture, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Preconceptional, pregnant, and postnatal exposure to outdoor air pollution and indoor environmental factors: Effects on childhood parasitic infections - Chan Lu; Lin Wang; Ying Jiang; Mengju Lan; Faming Wang (Science of The Total Environment, 2024)

Assessing grassland cultural ecosystem services supply and demand for promoting the sustainable realization of grassland cultural values - Lan Wang; Lin Huang; Wei Cao; Jun Zhai; Jiangwen Fan (Science of The Total Environment, 2024)

Sulfur atom-directed metal–ligand synergistic catalysis in zirconium/hafnium-oxo clusters for highly efficient amine oxidation - Sheng-Nan Sun; Qian Niu; Jiao-Min Lin; Li-Ling He; Jing-Wen Shi; Qing Huang; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Unraveling the effects of sodium carbonate on hydrothermal liquefaction through individual biomass model component and machine learning-enabled prediction - Wangfang Ye; Xiaoyu Lin; Xiaomei Zhong; Qian Lan; Guifang Yang; Jianhui Huang; Yijing Wu; Zeyuan Zhao; Quan (Sophia) He; Yulong Wu; Xin Xu; Jie Yang (Fuel, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Warming and wetting-induced soil acidification triggers methanotrophic diversity loss and species turnover in an alpine ecosystem - Chaonan Li; Changting Wang; Ping Zou; Lin Xu; Haijun Liao; Nan Lan; Li Lei; Wenjun Xiong; Weidong Kong; Junming Wang; Xiangzhen Li (CATENA, 2024)

Multiple Pathways for the Enhancement of Wheat Growth by Chlorella vulgaris - Sheng-Nan Wang; Shu-Han Ge; Lin-Lan Zhuang; Jian Zhang (Journal of Plant Growth Regulation, 2024)

Sources, Variations, and Effects on Air Quality of Atmospheric Ammonia - Ziru Lan; Weili Lin; Gang Zhao (Current Pollution Reports, 2024)

Enhanced humus synthesis from Chinese medicine residues composting by lignocellulose-degrading bacteria stimulation: Upregulation of key enzyme activity and neglected indirect effects on humus formation - Chuan-Ming Xing; Zi-Lin He; Tian Lan; Bo Yan; Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Cai-Xia Wang; Wan-Qian Guo (Science of The Total Environment, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Rapid survey method for large-scale outdoor surveillance cameras using binary space partitioning - Xin Lan; Liangchen Zhou; Bingxian Lin; Jiahao Li; Guonian Lv (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Occurrence and bioaccumulation of parabens and their metabolites in the biota from a subtropical freshwater river ecosystem: Implications for human exposure - Yiling Lin; Yanan Zhao; Yuxian Liu; Yongyin Lan; Jiamin Zhu; Yanpeng Cai; Fen Guo; Feilong Li; Yuan Zhang; Zhihao Xu; Jingchuan Xue (Environmental Research, 2024)

Effect of N/P ratio on attached microalgae growth and the differentiated metabolism along the depth of biofilm - Weiyi Qian; Yanan Yang; Sai Chou; Shuhan Ge; Peihua Li; Xiaoxiong Wang; Lin-Lan Zhuang; Jian Zhang (Environmental Research, 2024)

DEM study on the effect of pore characteristic on single particle crushing behavior of porous particles - Du-min Kuang; Zhi-lin Long; Ikechukwu Ogwu; Feng-lan Kuang; Ling-ming Yang (Computers and Geotechnics, 2024)

Highly ion-conducting, robust and environmentally stable poly(vinyl alcohol) eutectic gels designed by natural polyelectrolytes for flexible wearable sensors and supercapacitors - Bai Huang; Wanwan Liu; Yufan Lan; Yuhui Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2024)

Compressible polydopamine modified pomelo peel powder/poly(ethyleneimine)/κ-carrageenan aerogel with pH-tunable charge for selective removal of anionic and cationic dyes - Jincheng Yu; Siyao Tian; Anrong Yao; Haoyi Hu; Jianwu Lan; Lin Yang; Xiaosheng Du; Shaojian Lin (Carbohydrate Polymers, 2024)

Metabolomics reveals that chronic restraint stress alleviates carbon tetrachloride-induced hepatic fibrosis through the INSR/PI3K/AKT/AMPK pathway - Shanshan Zhang; Binjie Liu; Lan Huang; Rong Zhang; Lin An; Zhongqiu Liu (Journal of Molecular Medicine, 2024)

Relationship between exposure to metalworking fluids and nonalcoholic fatty liver disease - Weiling Chan; Geyang Li; Li Zhou; Jin Wang; Lin Song; Lejia Zhu; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Multiply-mesoporous hydrophilic titanium dioxide nanohybrid for the highly-performed enrichment of N-glycopeptides from human serum - Yunfan Lin; Chengrun Du; Hongmei Ying; Yifan Zhou; Fangfang Kong; Hongli Zhao; Minbo Lan (Analytica Chimica Acta, 2024)

Cell size‐dependent species sensitivity to nanoparticles underlies changes in phytoplankton diversity and productivity - Yiping Zuo; Michael Southard; Qianna Xu; Guangxing Zhang; Emily Skibinski; Nicole Moon; Lan Gan; Yongsheng Chen; Lin Jiang (Global Change Biology, 2024)
Nanoparticle pollution has been shown to affect various organisms. However, the effects of nanoparticles on species interactions, and the role of species traits, such as body size, in modulating these effects, are not well‐understood. We addressed this issue using competing freshwater phytoplankton species exposed to copper oxide nanoparticles. Increasing nanoparticle concentration resulted in decreased phytoplankton species growth rates and community productivity (both abundance and biomass). Importantly, we consistently found that nanoparticles had greater negative effects on species with smaller cell sizes, such that nanoparticle pollution weakened the competitive dominance of smaller species and promoted species diversity. Moreover, nanoparticles reduced the growth rate differences and competitive ability differences of competing species, while having little effect on species niche differences. Consequently, nanoparticle pollution reduced the selection effect on phytoplankton community abundance, but increased the selection effect on community biomass. Our results suggest cell size as a key functional trait to consider when predicting phytoplankton community structure and ecosystem functioning in the face of increasing nanopollution.

Advances and perspectives of nanomaterials for photocatalytic degradation of biological ethylene toward the postharvest improvement of agricultural products - Lan Huong Nguyen; Duc Anh Dinh; Lan-Anh Phan Thi; Phuong V. Pham; Pardeep Singh; Pankaj Raizada; Kun-Yi Andrew Lin; Van-Huy Nguyen (Environmental Science and Pollution Research, 2023)

The Bioeconomic Analysis of Hybrid Giant Grouper (Epinephelus fuscoguttatus × Epinephelus lanceolatus) and Green Grouper (Epinephelus malabaricus): A Case Study in Taiwan - Po-Lin Huang; Farok Afero; Yao Chang; Bo-Ying Chen; Hsun-Yu Lan; Yen-Lung Hou; Cheng-Ting Huang (Fishes, 2023)
Grouper aquaculture is a rapidly growing and dynamic industry within the Taiwan aquaculture sector that serves as an important source of income generation. Farming fishes at a better location (FFABL) is a promising production strategy. This study evaluated the production and economic performance of grouper farming in Taiwan. This investigation employed two steps: (1) a cost–benefit analysis to determine the main component affecting profitability; and (2) multivariate statistics to clarify the relationship between biological and economic factors. The findings suggest that the best choice of species is hybrid giant grouper that generates and highlights a positive income, viable benefit–cost ratio and profit rate. The study found the feed management of hybrid giant groupers requires more consideration due to its low feed conversion ratio. The producers need to replace trash fish in commercial feed during the production cycle to ensure better feed management. Finally, this paper argues that feed is the main constraint for grouper farming, which is sensitive to any change in feed productivity, and this constraint must be solved to sustain the grouper industry in Taiwan.

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Enhancing start-up strategies for anammox granular sludge systems: A review - Lan Lin; Yanlong Zhang; Yu-You Li (Science of The Total Environment, 2023)

Comparison of microalgae cultivation modes for advanced wastewater purification and pollutant-resource conversion: A pilot study - Lin-Lan Zhuang; Pengfei Yang; Shuang Liang; Tong Yu; Chao Liu; Tingting Zhao; Guoliang Tan; Yueying Niu; Jian Zhang (Journal of Water Process Engineering, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

Correlation between microbial community succession and flavor substances during fermentation of Yongchuan Douchi - Lin Lan; Jingxin Wang; Shengyu Wang; QiaoLing He; Ruilin Wei; Zaixing Sun; Shuhua Duan; Yufeng Li (Food Bioscience, 2023)

Bridge frequency identification in city bus monitoring: A coherence-PPI algorithm - Yifu Lan; Zhenkun Li; Keijo Koski; Ludovic Fülöp; Timo Tirkkonen; Weiwei Lin (Engineering Structures, 2023)

Multifunctional graphene/Ag hydrogel with antimicrobial and catalytic properties for efficient solar-driven desalination and wastewater purification - Lin Lin; Wenrui Wang; Danyi Li; Siyi Xu; Ying Sun; Linfan Li; Kai Fan; Chenyang Xing; Lan Zhang; Jihao Li (Chemical Engineering Journal, 2023)

Partial denitrification-anammox granular sludge domesticated from high-strength anammox granules and the high-efficiency performance in treating low-nitrogen wastewater - Lan Lin; Zibin Luo; Yanlong Zhang; Yuanyuan Ren; Yu-You Li (Chemical Engineering Journal, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

Fe-pillared montmorillonite functionalized chitosan/gelatin foams for efficient removal of organic pollutants by integration of adsorption and Fenton degradation - Anrong Yao; Yafang Wang; Jincheng Yu; Siyao Tian; Yifei Zhan; Hongjiang Liao; Jianwu Lan; Shaojian Lin (Carbohydrate Polymers, 2023)

Long period changes of hippocampal diffusion kurtosis imaging and its correlation with cognitive dysfunction after incomplete cerebral ischemia–reperfusion in rats - Lan Fu; Lin-Na Guan; Hongye Zuo (Experimental Brain Research, 2023)

Effects of phosphorus supply and salt stress on plant growth, organic acid concentration, and sodium, potassium, calcium, magnesium, and phosphorus utilization in wheat - De-Yong Zhao; Zai-Wang Zhang; Guo-Lan Liu; Shuai-Peng Zhao; Xiao-Lin Zhang; Wang-Feng Zhao; Kadambot H. M. Siddique (Cereal Research Communications, 2023)

Effect of cell settlement on the electrochemical collision behaviors of single microbes - Hanxin Zhang; Guanyue Gao; Yafei Chen; Lan Lin; Dengchao Wang; Yining Fan; Yanran Liu; Qi Zhao; Jinfang Zhi (Analytica Chimica Acta, 2023)

Applying sheet iron to enhance the treatment efficiency of digested effluent with continuous flow and the corresponding mechanism - Cong Ding; Li-bin Chen; Li-ping Yu; Ru Wang; Lin-jiang Yuan; Lan Wang; Liang-wei Deng (Chemosphere, 2023)

Trophodynamics of halogenated organic pollutants (HOPs) in aquatic food webs - Jingqian Xie; Shuyi Tu; Kashif Hayat; Ruo Lan; Chuchu Chen; Tiantian Leng; Hanlin Zhang; Tian Lin; Weiping Liu (Science of The Total Environment, 2023)

The auto-oxidation characteristic of coal at different stages of the low-temperature oxidation process - Xiaoyuan Jiang; Shengqiang Yang; Buzhuang Zhou; Lin Lan (Fuel, 2023)

Low-temperature degradation of lignin in aprotic solvent system for preparation of monophenolic platform chemicals - Xu Zeng; Yan Xu; Qiqi Dai; Jiaqi Li; Qixuan Lin; Jun Ye; Chuanfu Liu; Wu Lan (Chemical Engineering Journal, 2023)

Acetylation at the O-6 position of t-Glc improved immunoactivity of α-1,6-glucan from longan by additionally activating Dectin-1 and CD14 receptors - Lin Liu; Haibo Lan; Yao Wang; Lei Zhao; Xuwei Liu; Zhuoyan Hu; Kai Wang (Carbohydrate Polymers, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Physiochemical responses of C. elegans under exposure to lanthanum and cerium affected by bacterial metabolism - Wenning Lan; Xiaojing Zhang; Junhao Lin; Xiaolian Xiao; Junkun Chen; Shiying Sun; Guanlan Hong; Jingjing Nian; Fangrong Zhang; Yun Zhang (Science of The Total Environment, 2023)

Study on the relationship between fractal dimension and particle fragmentation for marine coral sand under impact load - Lan Lin; Sa Li; Linying Huo; Xin Liu (Ocean Engineering, 2023)

High-performance nanofiltration concentrate treatment by a five-chamber bioelectrochemical system - Jialin Liang; Fan Zhong; Han Lin; Xubin Ma; Jun Lan; Bo Ye; Lei Zhang (Journal of Environmental Management, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Preparation of natural complex waxy structure for the evaluation of preservation performance of blueberry - Xuedong Gu; Juan Li; Lin Yang; Lei Liu; Lan Xiao (Food Bioscience, 2023)

Dual-edged effects and mechanisms of hydroxylamine in partial denitrification-anaerobic ammonium oxidation system - Qi Zhang; Lan Lin; Yuqi Chen; Yuzheng Wang; Xiao Li; Linxi Li; Wenzhi Cao; Yanlong Zhang (Environmental Research, 2023)

Remediation of arsenic contaminated water and soil using mechanically (ball milling) activated and pyrite-amended electrolytic manganese slag - Zhihao Ha; Mengyu Ma; Xiaohan Tan; Yanxin Lan; Yanmin Lin; Tian C. Zhang; Dongyun Du (Environmental Research, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Hybrid tribo/piezoelectric nanogenerator textile derived from 3D interlocked parallel-arranged yarns for bio-motion energy harvesting and tactile sensing - Lin Liu; Yuantao Li; Muchun Xu; Rui Tao; Qiao Zhong; Xi Yang; Shixia Lan; Jiyang Xie; Guo Chen; Yongyun Mao; Wanbiao Hu (Chemical Engineering Journal, 2023)

Comparison of uniform and non-uniform surface heating effects on in-canyon airflow and ventilation by CFD simulations and scaled outdoor experiments - Guanwen Chen; Jian Hang; Lan Chen; Yuanyuan Lin (Building and Environment, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Sulfur vacancy rich MoS2/FeMoO4 composites derived from MIL-53(Fe) as PMS activator for efficient elimination of dye: Nonradical 1O2 dominated mechanism - Qiao Wang; Jiahong Lu; Meirui Yu; Huarui Li; Xinhong Lin; Jinxu Nie; Nan Lan; Zhihong Wang (Environmental Pollution, 2023)

Indirect damage detection for bridges using sensing and temporarily parked vehicles - Zhenkun Li; Yifu Lan; Weiwei Lin (Engineering Structures, 2023)

Diagenetic effect on barium isotope compositions of barites in the lower Cambrian successions - Lan-Lan Tian; Wei Wei; Lin-Hui Dong; Songqi Pan; Zhenhua Jing; Fang Huang (Chemical Geology, 2023)

Combination of surfactants and enzyme cocktails for enhancing woody biomass saccharification and bioethanol production from lab-scale to pilot-scale - Wei Qi; Qifa Feng; Wen Wang; Yu Zhang; Yunzi Hu; Usama Shakeel; Lin Xiao; Lan Wang; Hongzhang Chen; Cuiyi Liang (Bioresource Technology, 2023)

Impact of rhizosphere priming on soil organic carbon dynamics: Insights from the perspective of carbon fractions - Hao Cui; Chaoyang Mo; Pengfei Chen; Rui Lan; Chao He; Jingdong Lin; Zhenhui Jiang; Jingping Yang (Applied Soil Ecology, 2023)

First report of Pestalotiopsis neolitseae causing leaf blight on Photinia × fraseri in China - Xiu-Lan Xu; Si-Yi Liu; Qian-Gang Xiao; Yi-Cong Lv; Ying-Gao Liu; Chun-Lin Yang (Journal of Plant Pathology, 2023)

Tissue residue distribution and withdrawal time estimation of trimethoprim and sulfachloropyridazine in Yugan black-bone fowl ( Gallus gallus domesticus Brisson) - Lin Zhao; Dawen Zhang; Jing Lan; Xiangdong Sun; Yun Zhang; Bing Wang; Bei Ni; Shuang Wu; Ruiying Zhang; Hui Liao (Food Additives & Contaminants: Part A, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Irisin protects against doxorubicin-induced cardiotoxicity by improving AMPK-Nrf2 dependent mitochondrial fusion and strengthening endogenous anti-oxidant defense mechanisms - Caili Zhuo; Juanjuan Xin; Wenjing Huang; Die Zhang; Xin Yan; Ruli Li; He Li; Jie Lan; Lan Lin; Lingyu Li; Xuemei Wang; Linling Liu; et al. (Toxicology, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

TRPC6 promotes daunorubicin-induced mitochondrial fission and cell death in rat cardiomyocytes with the involvement of ERK1/2-DRP1 activation - Li-Xia Xu; Rui-Xing Wang; Jian-Feng Jiang; Gao-Cheng Yi; Jin-Jin Chang; Rui-Lan He; Hai-Xia Jiao; Bin Zheng; Long-Xin Gui; Jun-Jin Lin; Zhi-Hong Huang; Mo-Jun Lin; et al. (Toxicology and Applied Pharmacology, 2023)

A green and multi-win strategy for coal fly ash disposal by CO2 fixation and mesoporous silica synthesis - Tongyao Ju; Yuan Meng; Siyu Han; Fanzhi Meng; Li Lin; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Science of The Total Environment, 2023)

A hybrid safety monitoring framework for industrial FCC disengager coking rate based on FPM, CFD, and ML - Mengxuan Zhang; Zhe Yang; Yunpeng Zhao; Mingzhu Lv; Xingying Lan; Xiaogang Shi; Jinsen Gao; Chuankun Li; Zhuang Yuan; Yang Lin (Process Safety and Environmental Protection, 2023)

Origin and diversification of a Himalayan orchid genus Pleione - Sha-Sha Wu; Ming-Tao Jiang; Jiang-lin Miao; Ming-He Li; Jie-Yu Wang; Li-Ming Shen; Dong-Hui Peng; Si-Ren Lan; Jun-Wen Zhai; Zhong-Jian Liu (Molecular Phylogenetics and Evolution, 2023)

Gut microbiota and ionizing radiation-induced damage: Is there a link? - Yueqiu Yu; Xiang Lin; Feiyang Feng; Yuanyun Wei; Shuang Wei; Yaqi Gong; Caimao Guo; Qingyu Wang; Peimeng Shuai; Tiantian Wang; Hui Qin; Guoqing Li; et al. (Environmental Research, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Updates on applications of low-viscosity grade Hydroxypropyl methylcellulose in coprocessing for improvement of physical properties of pharmaceutical powders - Cheng Jin; Fei Wu; Yanlong Hong; Lan Shen; Xiao Lin; Lijie Zhao; Yi Feng (Carbohydrate Polymers, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Overexpression of OsNF-YB4 leads to flowering early, improving photosynthesis and better grain yield in hybrid rice - Meifang Peng; Feng Gan; Xiaomin Lin; Run Yang; Shaoyi Li; Wei Li; Lan Wu; Xiaoli Fan; Kegui Chen (Plant Science, 2023)

Investigation of analytical behavior of concrete filled steel tubular (CFST) offshore rock-socketed pile under lateral load - Lan Lin; Fa-cheng Wang (Ocean Engineering, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Progress of increasing-block electricity pricing policy implementation in China's first-tier cities and the impact of resident policy perception - Boqiang Lin; Tianxu Lan (Energy Policy, 2023)

Inchworm-Inspired soft robot with magnetic driving based on PDMS, EGaIn and NdFeB (PEN) combination - Yanfang Guan; Yansheng Liu; Qilong Wang; Hao Geng; Tangyong Cui; Yuang Hu; Qing Luo; Aonan Li; Wujie Li; Yang Lin; Lin Zhang; Guangyu Liu; et al. (Chemical Engineering Journal, 2023)

Comparative analysis of the skin microbiota between two sea snakes, Hydrophis cyanocinctus and Hydrophis curtus, with versus without skin ulcer - Jun Zhong; Kun Guo; Zheng-Lan Liao; Yu Du; Chi-Xian Lin; Xiang Ji (Coral Reefs, 2023)

Simultaneous detection and phylogenetic analysis of porcine epidemic diarrhea virus and porcine circovirus 4 in Henan province, China - Hong-Xuan Li; Xi-Meng Chen; You-Yi Zhao; Hong-Lei Zhang; Lan-Lan Zheng; Lin-Qing Wang; Shi-jie Ma; Hong-Ying Chen (Archives of Virology, 2023)

Identification and genomic characterization of Ralstonia pseudosolanacearum strains isolated from pepino melon in China - Shanwen Ding; Lin Yu; Guobing Lan; Yafei Tang; Zhenggang Li; Zifu He; Xiaoman She (Physiological and Molecular Plant Pathology, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Totally-green cellulosic fiber with prominent sustained antibacterial and antiviral properties for potential use in spunlaced non-woven fabric production - Jinxin Lan; Yao Wu; Changmei Lin; Jiazhen Chen; Ruiqi Zhu; Xiaojuan Ma; Shilin Cao (Chemical Engineering Journal, 2023)

Late Pleistocene to Holocene sedimentary history in the Pearl River Delta revealed by OSL and radiocarbon dating - Penghui Lin; Yingjin Song; Weiqi Zhan; Ruonan Tian; Zhongbo Wang; Xiaolin Xu; Lan Luo; Mahmoud Abbas; Zhongping Lai (CATENA, 2023)

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

Designing bike-friendly cities: Interactive effects of built environment factors on bike-sharing - Lan Wang; Kaichen Zhou; Surong Zhang; Anne Vernez Moudon; Jinfeng Wang; Yong-Guan Zhu; Wenyao Sun; Jianfeng Lin; Chao Tian; Miao Liu (Transportation Research Part D: Transport and Environment, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Mediated anaerobic system performance, co-metabolizing flora and electron transfer by graphene oxide supported zero-valent iron composite - Huixia Lan; Linyu Ji; Ke Li; Yecheng Lin; Xiangzhi Wang; Wudi Zhang; Qiaochu Liang; Yang Zhang (Journal of Environmental Chemical Engineering, 2023)

A hydrogel-enabled cascade amplification of radiosensitization and immune activation for cancer radiotherapy - Qingxu Song; Gongde Lan; Qian Li; Yang Lin; Xin Chen; Hong Liu; Yufeng Cheng; Yuxia Luan (Chemical Engineering Journal, 2023)

Exploring the mechanism of Self-Consistent balance between microbiota and high efficiency in wastewater treatment - Ming-hui Zhong; Lin Yang; Kai Xiong; Hui-lin Yang; Xiao-lan Wang (Bioresource Technology, 2023)

α7 nicotinic acetylcholine receptor agonist improved brain injury and impaired glucose metabolism in a rat model of ischemic stroke - Ya-Yu Wang; Shih-Yi Lin; Cheng-Yi Chang; Chih-Cheng Wu; Wen-Ying Chen; Wei-Chi Huang; Su-Lan Liao; Wen-Yi Wang; Chun-Jung Chen (Metabolic Brain Disease, 2023)

Juvenile and Trash Fish Excluder Device (JTED) for Taiwanese Bottom Trawl - Chao-Ching Chen; Hsin-Zong Lin; Kuo-Wei Lan (Fishes, 2023)
Juvenile and trash fish excluder devices (JTEDs) are used to mitigate the ecological impact of trawling. Trawling has a large ecological footprint in Taiwan. Thus, this study designed three JTEDs, which differed only in grid interval, for single boat bottom otter trawls that are commonly used in Taiwan. The designed JTEDs were tested in the waters off of Kaohsiung on a Kaohsiung-based bottom trawler, and the results were as follows. (1) At least 300 species were caught, and 189 of these species had little commercial value; their weight accounted for 52.5% of the total catch. (2) The three JTEDs had good exclusion performance. (3) The ratios of the weight of bycatch excluded to the weight of total catch were 7.9%, 29.1%, and 36.2%, for grid intervals of 10, 15, and 20 mm, respectively. (4) JTEDs with grid intervals of 10, 15, and 20 mm were associated with a 0.4%, 11.5%, and 19.0% loss in revenue, respectively. (5) Mature (and thus commercially valuable) Loliginidae tended to be excluded when the grid interval was 20 or (especially) 15 mm. In general, the designed JTEDs should be used at a grid size of 15 mm because this strikes the best balance between profitability and sustainability.

Ambient air pollution associated with incidence and progression trajectory of cardiometabolic diseases: A multi-state analysis of a prospective cohort - Hongtao Zou; Shiyu Zhang; Miao Cai; Zhengmin (Min) Qian; Zilong Zhang; Lan Chen; Xiaojie Wang; Lauren D. Arnold; Steven W. Howard; Haitao Li; Hualiang Lin (Science of The Total Environment, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

The influence of organic sources and environments on source rock deposition during the periods of Cretaceous-Eocene and Oligocene-Miocene, northern Kalimantan - Lei Lan; Youchuan Li; Zhigang Zhao; Shuchun Yang; Qing Lin; Weilai Zhang (Acta Oceanologica Sinica, 2023)

The effect of short-term air pollutants exposure on outpatient admission for blepharitis in Shanghai, China: a hospital-based study - Han Zhao; Tong Lin; Yun Yang; Changming Feng; Wushuang Wang; Lan Gong (Environmental Science and Pollution Research, 2023)

An assessment of rainfall kinetic energy functional relationships with GPM DPR - Jayalakshmi Janapati; Balaji Kumar Seela; Pay-Liam Lin; Chen-Hau Lan; Chuan-Chi Tu; Utpal Kumar; Mu-Qun Huang (Journal of Hydrology, 2023)

Optimization and mechanism of coupling process between algal ponds and constructed wetlands for wastewater polishing and nutrient recovery - Pengfei Yang; Shuhan Ge; Zhiqiang Liu; Lin-Lan Zhuang; Weijiang Li; Chao Liu; Jian Zhang (Journal of Cleaner Production, 2023)

CH4 and CO2 emissions in water networks of rice cultivation regions - Ouping Deng; Jiangyou Ran; Xuesong Gao; Xiangjun Lin; Ting Lan; Ling Luo; Yalan Xiong; Jiang Liu; Dinghua Ou; Jianbo Fei; Rong Huang (Environmental Research, 2023)

Evaluation of Copper Levels in Dental Calculus of OSF Patients with Chewing Dried Areca-Nut Quids in Hunan Province of Mainland China - Xi-Fan He; Hui Wang; Ye Tian; Te Zhang; Zhi-Peng Qiu; Xiao-Jiao Cui; Jing-Sha Zhou; Xin-Lan Yan; Yi-Wei Wu; Yi-Sha Pan; Yang-Bo Ning; Lin Chen; et al. (Biological Trace Element Research, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

Detection and genetic analysis of porcine circovirus-like virus in pigs with diarrhea between 2016 and 2021 in Henan and Shanxi provinces of China - Liu-Hui Zhang; Lin-Qing Wang; Hong-Xuan Li; Hong-Lei Zhang; Lan-Lan Zheng; Xi-Meng Chen; Hong-Ying Chen (Archives of Virology, 2023)

NRP1 contributes to stemness and potentiates radioresistance via WTAP-mediated m6A methylation of Bcl-2 mRNA in breast cancer - Yang Wang; Lin Zhang; Xiao-Lin Sun; Ya-Chun Lu; Si Chen; Dong-Sheng Pei; Lan-Sheng Zhang (Apoptosis, 2023)

A prognostic cuproptosis-related lncRNA predictive signature for bladder cancer patients - Shaoqin Jiang; Jili Zhang; Qi Fan; Zhihao Li; Ruiling Dou; Zequn Lin; Zhenlin Chen; Yue Xu; Zhangcheng Huang; Jingyuan Lan; Wenwen Lin; Sijie Xu; et al. (Human Cell, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Ambient air pollution, bone mineral density and osteoporosis: Results from a national population-based cohort study - Yin Yang; Rui Li; Miao Cai; Xiaojie Wang; Haopeng Li; Yinglin Wu; Lan Chen; Hongtao Zou; Zilong Zhang; Haitao Li; Hualiang Lin (Chemosphere, 2023)

Landslide-impacted soils recover faster biologically than chemically or physically, though recovery also varies with forest type in subtropical China - Jian Li; Lan Xiao; Jonathan D. Bakker; Qinghu Luo; Hang Yu; Jianzhao Wu; Songyang Li; Loretta Pedersen; Can Chen; Tao Hong; Han Lin; Daojie Wang; et al. (Soil and Tillage Research, 2023)

Improving the biomass retention and system stability of the anammox EGSB reactor by adding a calcium silicate hydrate functional material - Lan Lin; Kyuto Ishida; Yanlong Zhang; Norihiro Usui; Ayaka Miyake; Nobuhiko Abe; Yu-You Li (Science of The Total Environment, 2023)

Screening of microalgae species and evaluation of algal-lipid stimulation strategies for biodiesel production - Yanan Yang; Shuhan Ge; Yitong Pan; Weiyi Qian; Shengnan Wang; Jian Zhang; Lin-Lan Zhuang (Science of The Total Environment, 2023)

Extract of Ginkgo biloba leaves attenuates neurotoxic damages in rats and SH-SY5Y cells exposed to a high level of fluoride - Jie Xiang; Yan-Lin Ma; Jian Zou; Xiao-Xiao Zeng; Xiao Xiao; Yan-Long Yu; Yang-Ting Dong; Long-Yan Ran; Xiao-Lan Qi; Wei Hong; Yan-Hui Gao; Zhi-Zhong Guan (Journal of Trace Elements in Medicine and Biology, 2023)

Mitochondrial alternative oxidase enhanced ABA-mediated drought tolerance in Solanum lycopersicum - Kang Qiao; Xiuhong Yao; Zuxu Zhou; Jiawei Xiong; Ke Fang; Jiayi Lan; Fei Xu; Xingguang Deng; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Characteristics, application and modeling of solid amine adsorbents for CO2 capture: A review - Li Lin; Yuan Meng; Tongyao Ju; Siyu Han; Fanzhi Meng; Jinglin Li; Yufeng Du; Mengzhu Song; Tian Lan; Jianguo Jiang (Journal of Environmental Management, 2023)

Role of chicken fat waste and hydrogen energy ratio as the potential alternate fuel with nano-additives: Insights into resources and atmospheric remediation process - Lin Yi-Chia; Manigandan Sekar; Arunachalam Chinnathambi; Omaima Nasif; Beata Gavurová; G.K. Jhanani; Kathirvel Brindhadevi; Nguyen Thuy Lan Chi (Environmental Research, 2023)

Arsenic shapes the microbial community structures in tungsten mine waste rocks - Xiaolong Lan; Wenjie Lin; Zengping Ning; Xinyu Su; Yushuang Chen; Yanlong Jia; Enzong Xiao (Environmental Research, 2023)

Diagnosis algorithms for indirect bridge health monitoring via an optimized AdaBoost-linear SVM - Yifu Lan; Youqi Zhang; Weiwei Lin (Engineering Structures, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Effects of spatial working memory capacity and resolution loads on postural stability while dual-tasking - Danxuan Zhang; Bin Wang; Chuan Zhang; Huiru Lin; Wencen Lan (Experimental Brain Research, 2023)

Characterising the influence of acid rain on the growth and physiological characteristics of Mirabilis jalapa Linn. in southern China - Lan-ying Chen; Lin Wang; Hao-yu Wang; Xun Zhu (Acta Physiologiae Plantarum, 2023)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

CircCERS6 Suppresses the Development of Epithelial Ovarian Cancer Through Mediating miR-630/RASSF8 - Xiaoqin Li; Xuemei Jiang; Jing Lu; Yuting Lin; Lan Jiang; Yan Li; Feng Wan; Changmin Wang (Biochemical Genetics, 2022)

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

Holocene sedimentary of the Pearl River Delta in South China: OSL and radiocarbon dating of cores from Zhuhai - Penghui Lin; Xiaolin Xu; Chaoyang Yan; Lan Luo; Mahmoud Abbas; Zhongping Lai (Frontiers in Marine Science, 2022)
Deltaic sediments provide a window for investigating delta development processes and the effects of human activities. Despite the fact that numerous studies have been conducted in the Pearl River Delta (PRD), the chronological data are still very limited, which hinder the detailed interpretation of the sedimentary records. The current study aims to establish high-resolution chronology on two cores from Zhuhai using quartz optically stimulated luminescence (OSL) and radiocarbon ( 14 C) dating and, further, to reconstruct the Holocene sedimentary history of the PRD. Core P1-1 has a depth of 79 m and core P3-2 a depth of 60 m. Thirteen quartz OSL samples from P1-1 produced ages between 10.4 and 0.16 ka. Eight OSL and eight 14 C ages from P3-2 span from 10.7 to 0.3 ka. The OSL and 14 C dates show a good agreement above the depth of 26 m (1.4–0.3 ka), but with discrepancies at depths of 26–54 m. 14 C ages (10.7–8.1 ka) are generally older (up to c. 2 ka) than quartz OSL ages, and the discrepancy decreases with depth. The age model shows three phases of the sedimentation process: (1) rapid accumulation rates of 7.48 (P1-1) and 7.52 (P3-2) m/ka between c. 10.7 and 7.5 ka in response to high sea level, (2) followed by a significantly reduced rate of 2.24 m/ka (P1-1) and a depositional hiatus (P3-2) from 7.5 to 2.5 ka as a result of reduced sediment supply and strong scouring by tidal processes, and (3) high sedimentation rates of 8.86 (P1-1) and 9.07 (P3-2) m/ka since 2.5 ka associated with intensive human activities and weakening tidal hydrodynamics. This sedimentary pattern is also evident in many other Asian deltas.

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Gregarious larval settlement mediates the responses of new recruits of the reef coral Acropora austera to ocean warming and acidification - Lei Jiang; Yu-Yang Zhang; Cheng-Yue Liu; Lin-Tao Huang; Hao-Ya Tong; Guo-Wei Zhou; Ming-Lan Guo; Tao Yuan; Hui Huang (Frontiers in Marine Science, 2022)
Gregarious larval settlement represents an important window for chimera formation in reef corals, yet it remains largely unknown how aggregated settlement and early chimerism could modify the performance and responses of coral recruits under elevated temperature and p CO 2 . In this study, single and aggregated recruits of the broadcast spawning coral Acropora austera were exposed to contrasts of two temperatures (28 versus 30.5°C) and p CO 2 levels (~500 versus 1000 μatm) for two weeks, and algal symbiont infection success, survivorship and growth were assessed. Results showed that symbiont infection success was mainly affected by temperature and recruit type, with reduced symbiont infection at increased temperature and consistently higher infection success in chimeric recruits compared to single recruits. Furthermore, although chimeric recruits with larger areal size had significantly higher survivorship in all treatments, the polyp-specific growth rates were considerably lower in chimeric entities than individual recruits. More importantly, the recruit type significantly influenced the responses of recruit polyp-specific growth rates to elevated temperature, with chimeras exhibiting lowered skeletal lateral growth under elevated temperature. These results demonstrate the benefits and costs associated with gregarious larval settlement for juvenile corals under ocean warming and acidification, and highlight the ecological role of larval settlement behavior in mediating the responses of coral recruits to climate change stressors.

Nanobubbles loaded with carbon quantum dots for ultrasonic fluorescence dual detection - Yankun Zhang; Bingtao Tang; Yu Xin; Qiong Wu; Lan Liu; Yunxia Wang; Kongxi Zhu; Guimei Lin; Hongjuan Wang (Journal of Zhejiang University-SCIENCE B, 2022)

Effects of soil organic matter components and iron aluminum oxides on aggregate stability during vegetation succession in granite red soil eroded areas - Zhe Lin; Zhi-gang Huang; Da-lan Liao; Wan-xia Huang; Juan Huang; Yu-song Deng (Journal of Mountain Science, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Three new sesquiterpene lactones from the whole plants of Elephantopus scaber - Ding-Chai Lin; Qing Tang; Xue-Fang Zhuo; Wen-Zhi Wang; Can-Jie Li; Guang-Kai Kuang; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Investment Feasibility Analysis of Large Submersible Cage Culture in Taiwan: A Case Study of Snubnose Pompano (Trachinotus anak) and Cobia (Rachycentron canadum) - Hsun-Yu Lan; Farok Afero; Cheng-Ting Huang; Bo-Ying Chen; Po-Lin Huang; Yen-Lung Hou (Fishes, 2022)
Onshore farming for premium aquaculture is under scrutiny and criticism partially due to possible causes of adverse environmental impacts on other resource users and the surrounding environment. The best alternative to preventing or minimizing these impacts is to utilize open seawater by large submersible cage culture. The current operation in Taiwan has demonstrated that the culture operation is technically feasible but economically demanding because of high capital and operating costs. Therefore, this study conducted an economic analysis of the expansion of large submersible cage culture by selecting two premium species of snubnose pompano (Trachinotus anak) and cobia (Rachycentron canadum) and examined the profitability of large submersible cage culture investment. This study found that the current operation of four-unit cages highlighted a negative net present value and internal rate of return with a payback period of over ten and six years, respectively. Large submersible cage culture can be financially profitable when its operation unit expands from 8 to 24 units. Increasing unit cages to eight incurred a gross margin of 17.09%, BCR 1.21, with a payback period of 5.36 years. Expanding the operation to 24-unit cages was a potentially lucrative investment with a gross margin of 18.51%, BCR 1.23, PI 2.15, internal rate of return of 20.84%, and a payback period of 3.55 years. Sensitivity analyses revealed that market price and survival rate significantly impact the profitability of large submersible cage culture. Finally, it is suggested that producers could invest in 8-unit cages and maintaining the survival rate of snubnose pompano and cobia at 80% and 40%, respectively.

Detection of bloom-forming dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense using qPCR assays - Xiao-Kun Hu; Zhuo-Ru Lin; Qing-Chun Zhang; Fan-Zhou Kong; Jing-Yi Cen; Yu-Lan Zeng; Ren-Cheng Yu (Journal of Applied Phycology, 2022)

Dissection of starch composition and physicochemical property in barley shrunken mutants - Na Lin; Xiaojuan Zhong; Qiang Yang; Hassan Karim; Jingyu Lan (Brazilian Journal of Botany, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Bioeconomic evaluation of Eleutheronema tetradactylum farming: a case study in Taiwan - Cheng-Ting Huang; Farok Afero; Fang-Yu Lu; Bo-Ying Chen; Po-Lin Huang; Hsun-Yu Lan; Yen-Lung Hou (Fisheries Science, 2022)

Multifunctional Role of Silica in Pharmaceutical Formulations - Yating Gao; Yue Zhang; Yanlong Hong; Fei Wu; Lan Shen; Youjie Wang; Xiao Lin (AAPS PharmSciTech, 2022)

Berberisides A-D: three novel prenylated benzoic acid derivatives and a clerodane glycoside from Berberis tsarica aherndt. - Zhao-Yue Dong; Qing-Hong Zeng; Lin Wei; Xin Guo; Yan Sun; Fan-Cheng Meng; Guo-Wei Wang; Xiao-Zhong Lan; Zhi-Hua Liao; Min Chen (Natural Product Research, 2022)

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Ambient gaseous pollutants and emergency ambulance calls for all-cause and cause-specific diseases in China: a multicity time-series study - Lan Chen; Xiaojie Wang; Zhengmin Qian; Liwen Sun; Lijie Qin; Chongjian Wang; Steven W. Howard; Hannah E. Aaron; Hualiang Lin (Environmental Science and Pollution Research, 2022)

Atmospheric deposition fluxes and health risk assessment of potentially toxic elements in Caohai Lake (Guizhou Province, China) - Shao-xia Lin; Zhuan-ling Zhang; Zhi-qiang Xiao; Xiao-lan Liu; Qing-hai Zhang (Journal of Mountain Science, 2022)

Environmental Regulation of Photosynthetically Produced Dissolved Organic Carbon by Phytoplankton Along a Subtropical Estuarine Bay - Jianhua Kang; Zhaohe Luo; Hala. F. Mohamed; Yili Lin; Shuhong Huang; Yu Wang; Wenlu Lan (Frontiers in Marine Science, 2022)
Photosynthetically produced dissolved organic carbon (PDOC) released by marine phytoplankton has an important significance on the marine carbon cycle and on the growth of heterotopic bacteria (HB). However, PDOC is often neglected in the estimation of global marine primary productivity and carbon sequestration capacity. This work studied the issue of PDOC and its environmental regulation mechanism through field investigation and lab experiments in an estuarine bay during southwest and northeast monsoon. We used the percentage of extracellular release (PER) as a key indicator to evaluate the contribution of PDOC to total primary productivity (TPP). We also compared PER among different seasons and sectors and then analyzed the inter-relationship between PDOC and bacterial carbon demand (BCD), size-fractionated phytoplankton, bacterial production (BP), and TPP. We finally discussed the impact factors of PDOC productivity. The results showed that the average contribution of PDOC to TPP in Qinzhou bay could reach 15% during two seasons, which satisfies about 25% of the carbon requirement by HB in the bay. Multiple factors contribute to the seasonal (SW monsoon 13% < NE monsoon 18%) and sectoral variation (outer bay 26% > middle bay 17% > inner bay 7%) in PER, the most significant of which are salinity and nitrogen to phosphorus ratios. PER is also related to phytoplankton community structure and nutrient limitation, the higher PER in the outer bay is attributed to the dual effect of picophytoplankton being the predominant species and a severe imbalance in the nitrogen to phosphorus ratio, both of which lead to increased phytoplankton PDOC release. On the other hand, the lower PER in the inner bay was mainly due to the dominance of microphytoplankton and nitrogen to phosphorus ratio which is close to the redfield ratio. There is still a non-uniform conclusion on the relationship between PER and TPP, suggesting that this relationship needs to be evaluated not only in a horizontal-independent way but also through seasonal and vertical dimensions. The non-linear relationship between PDOC and BCD found in this study potentially indicated weak coupling between phytoplankton exudation and bacterial metabolism. In addition to phytoplankton exudate, HB is still dependent on other sources of DOC to meet their carbon requirements.

Effect of High-Pressure Treatment on Blue Marlin ( Makaira nigricans ) Quality During Storage - Yi-Chen Lee; Hsien-Feng Kung; Shao-Lan Chen; Chung-Saint Lin; Chun-Yung Huang; Osamu Arakawa; Chih-Hua Tseng; Yung-Hsiang Tsai (Journal of Aquatic Food Product Technology, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Comparatively analyzing the liver-specific transcriptomic profiles in Kunming mice afflicted with streptozotocin- and natural food-induced type 2 diabetes mellitus - Yanjun Wu; Xiangxing Zhu; Arome Solomon Odiba; Zisheng Lin; Jiancong Wen; Daoyuan Gong; Jing Liang; Shuguang Wu; Ganqiu Lan (Molecular Biology Reports, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Functional variants of RPS6KB1 and PIK3R1 in the autophagy pathway genes and risk of bladder cancer - Lan Ma; Dongjian Zhang; Zhengkai Huang; Rui Zheng; Mulong Du; Qiang Lv; Chao Qin; Haiyan Chu; Lin Yuan; Zhengdong Zhang (Archives of Toxicology, 2022)

Assessing relative density of carbonate granular soil via dynamic cone penetration field and model tests - Lan Lin; Sa Li; Liqiang Sun; Tingting Li; Jiangsong Yin (Marine Georesources & Geotechnology, 2021)

Electrical Impedance Tomography Analysis Between Two Similar Respiratory System Compliance During Decremetal PEEP Titration in ARDS Patients - Po-Lan Su; Wei-Chieh Lin; Yen-Fen Ko; Kuo-Sung Cheng; Chang-Wen Chen (Journal of Medical and Biological Engineering, 2021)
Purpose The positive end-expiratory pressure (PEEP) level with best respiratory system compliance (Crs) is frequently used for PEEP selection in acute respiratory distress syndrome (ARDS) patients. On occasion, two similar best Crs (where the difference between the Crs of two PEEP levels is < 1 ml/cm H 2 O) may be identified during decremental PEEP titration. Selecting PEEP under such conditions is challenging. The aim of this study was to provide supplementary rationale for PEEP selection by assessing the global and regional ventilation distributions between two PEEP levels in this situation. Methods Eight ARDS cases with similar best Crs at two different PEEP levels were analyzed using examination-specific electrical impedance tomography (EIT) measures and airway stress index (SIaw). Five Crs were measured at PEEP values of 25 cm H 2 O (PEEP 25 ), 20 cm H 2 O (PEEP 20 ), 15 cm H 2 O (PEEP H ), 11 cm H 2 O (PEEP I ), and 7 cm H 2 O (PEEP L ). The higher PEEP value of the two PEEPs with similar best Crs was designated as PEEP upper , while the lower designated as PEEP lower . Results PEEP H and PEEP I shared the best Crs in two cases, while similar Crs was found at PEEP I and PEEP L in the remaining six cases. SIaw was higher with PEEP upper as compared to PEEP lower (1.06 ± 0.10 versus 0.99 ± 0.09, p = 0.05). Proportion of lung hyperdistension was significantly higher with PEEP upper than PEEP lower (7.0 ± 5.1% versus 0.3 ± 0.5%, p = 0.0002). In contrast, proportion of recruitable lung collapse was higher with PEEP lower than PEEP upper (18.6 ± 4.4% versus 5.9 ± 3.7%, p < 0.0001). Cyclic alveolar collapse and reopening during tidal breathing was higher at PEEP lower than PEEP upper (34.4 ± 19.3% versus 16.0 ± 9.1%, p = 0.046). The intratidal gas distribution (ITV) index was also significantly higher at PEEP lower than PEEP upper (2.6 ± 1.3 versus 1.8 ± 0.7, p = 0.042). Conclusions PEEP upper is a rational selection in ARDS cases with two similar best Crs. EIT provides additional information for the selection of PEEP in such circumstances.

Realization of Natural Human Motion on a 3D Biped Robot For Studying the Exoskeleton Effective - Chi-Ying Lee; Shih Chieh Lan; Jung-Ji Lin; Yu-Ting Lin; Po-Shen Chiang; Wei-Li Hsu; Kuo-Kuang Jen; Andy Y. S. Huang; Jia-Yush Yen (Journal of Medical and Biological Engineering, 2021)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Fine-mapping and gene candidate analysis for AhRt1, a major dominant locus responsible for testa color in cultivated peanut - Hao Chen; Xiangyu Chen; Rirong Xu; Wenjing Liu; Nian Liu; Li Huang; Huaiyong Luo; Dongxin Huai; Xinlong Lan; Yumei Zhang; Runfang Hu; Jianhong Chen; et al. (Theoretical and Applied Genetics, 2021)

Paternal exposure to microcystin-LR induces fetal growth restriction partially through inhibiting cell proliferation and vascular development in placental labyrinth - Lan Gao; An-Qi Cui; Jing Wang; Jing Chen; Xiao-Yi Zhang; Zhi-Jing Lin; Yuan-Hua Chen; Cheng Zhang; Hua Wang; De-Xiang Xu (Environmental Science and Pollution Research, 2021)

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Identifying rainfall threshold of flash flood using entropy decision approach and hydrological model method - Kairong Lin; Jiaqi Zhou; Ruhao Liang; Xiaozhang Hu; Tian Lan; Meixian Liu; Xin Gao; Denghua Yan (Natural Hazards, 2021)

miR-145-5p targets paxillin to attenuate angiotensin II-induced pathological cardiac hypertrophy via downregulation of Rac 1, pJNK, p-c-Jun, NFATc3, ANP and by Sirt-1 upregulation - Kuan-Ho Lin; V. Bharath Kumar; Tamilselvi Shanmugam; Marthandam Asokan Shibu; Ray-Jade Chen; Chia-Hua Kuo; Tsung-Jung Ho; V. Vijaya Padma; Yu-Lan Yeh; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Interaction between β-lactam antibiotic and phosphorus-accumulating organisms - Rong Huang; Jing Lan; Chaoguo Zhan; Yanhui Ge; Lin Zhao (Environmental Science and Pollution Research, 2021)

Characteristics of bacterial community and ARGs profile in engineered goldfish tanks with stresses of sulfanilamide and copper - Benjamin Makimilua Tiimub; Zhen-chao Zhou; Lin Zhu; Yang Liu; Xin-Yi Shuai; Lan Xu; Christophe’ Niyungeko; Ling-Xuan Meng; Yu-Jie Sun; Hong Chen (Environmental Science and Pollution Research, 2021)

Association between population density and infection rate suggests the importance of social distancing and travel restriction in reducing the COVID-19 pandemic - Heliang Yin; Tong Sun; Lan Yao; Yan Jiao; Li Ma; Lin Lin; J Carolyn Graff; Lotfi Aleya; Arnold Postlethwaite; Weikuan Gu; Hong Chen (Environmental Science and Pollution Research, 2021)

LINC00200 contributes to the chemoresistance to oxaliplatin of gastric cancer cells via regulating E2F1/RAD51 axis - Mengxin Lin; Meifang Xu; Zongbin Xu; Zongqi Weng; Bingqiang Lin; Yanqin Lan; Qing Liu; Xiaoyan Lin; Jie Pan (Human Cell, 2021)

Acute effects of particulate matter with different sizes on respiratory mortality in Shenzhen, China - Feng Zhu; Lan Chen; Zhengmin Qian; Yuxue Liao; Zhen Zhang; Stephen Edward McMillin; Xiaojie Wang; Hualiang Lin (Environmental Science and Pollution Research, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

A survey of chloramphenicol residues in aquatic products of Shenzhen, South China - Lan Luo; Shaoyou Lu; Chengpeng Huang; Fu Wang; Yan Ren; He Cao; Qihui Lin; Zhiqiang Tan; Xiaodong Wen (Food Additives & Contaminants: Part A, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Five matrine-type alkaloids from Sophora tonkinensis - Qing Tang; Ding Luo; Ding-Chai Lin; Wen-Zhi Wang; Can-Jie Li; Xue-Fang Zhuo; Zhong-Nan Wu; Yu-Bo Zhang; Guo-Cai Wang; Yao-Lan Li (Journal of Natural Medicines, 2021)

Analysis of the palladium response relationship of a receiving water body under multiple scenario changes in rainfall-runoff pollution - Fangfang Ding; Yuyan Liu; Lin Wang; Haofeng Liu; Caiye Ji; Lan Zhang; Dan Wu (Environmental Science and Pollution Research, 2021)

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

Cytotoxic p -terphenyls from the deep-sea-derived Aspergillus candidus - Yu-Kun Lin; Chun-Lan Xie; Cui-Ping Xing; Bao-Qu Wang; Xiao-Xue Tian; Jin-Mei Xia; Ling-Yun Jia; Ying-Ni Pan; Xian-Wen Yang (Natural Product Research, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Effects of Climate Change in Marine Ecosystems Based on the Spatiotemporal Age Structure of Top Predators: A Case Study of Bigeye Tuna in the Pacific Ocean - Kuo-Wei Lan; Yan-Lun Wu; Lu-Chi Chen; Muhamad Naimullah; Tzu-Hsiang Lin (Frontiers in Marine Science, 2021)
How top predators behave and are distributed depend on the conditions in their marine ecosystem through bottom−up forcing; this is because where and when these predators can feed and spawn are limited and change often. This study investigated how the catch rates of immature and mature cohorts of bigeye tuna (BET) varied across space and time; this was achieved by analyzing data on the Taiwanese longline fishery in the western and central Pacific Ocean (WCPO). We also conducted a case study on the time series patterns of BET cohorts to explore the processes that underlie the bottom-up control of the pelagic ecosystem that are influenced by decadal climate events. Wavelet analysis results revealed crucial synchronous shifts in the connection between the pelagic ecosystems at low trophic levels in relation to the immature BET cohort. Many variables exhibited decreasing trends after 2004–2005, and we followed the Pacific Decadal Oscillation (PDO) as a bottom-up control regulator. The results indicated that low recruitment into the mature cohort occurs 3 years after a decrease in the immature cohort’s food stocks, as indicated by a 3-year lag in our results. This finding demonstrated that, by exploring the connection between low-trophic-level species and top predators at various life stages, we can better understand how climate change affects the distribution and abundance of predator fish.

Activating Transcription Factor 6 Contributes to Functional Recovery After Spinal Cord Injury in Adult Zebrafish - Zhe Ji; Zhi-Lan Zhou; Qin Hao; Lin Zhao; Chun Cui; Shu-Bing Huang; Yan-Ling Yang; Yan-Qin Shen (Journal of Molecular Neuroscience, 2021)

Differential proteomics reveals main determinants for the improved pectinase activity in UV-mutagenized Aspergillus niger strain - Weiling Lin; Xiaohong Xu; Ruirui Lv; Wei Huang; Hafeez ul Haq; Yuanyuan Gao; Hongli Ren; Canhua Lan; Baoyu Tian (Biotechnology Letters, 2021)

Kinesin-7 CENP-E regulates the formation and structural maintenance of the acrosome - Zhen-Yu She; Kai-Wei Yu; Ya-Lan Wei; Ning Zhong; Yang Lin (Cell and Tissue Research, 2021)

Comparative analysis of developing grain transcriptome reveals candidate genes and pathways improving GPC in wheat lines derived from wild emmer - Fangyi Gong; Lin Huang; Tiangang Qi; Guan Tang; Jia Liu; Lan Xiang; Jingshu He; Youliang Zheng; Dengcai Liu; Bihua Wu (Journal of Applied Genetics, 2021)

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Multifunctional Role of Polyvinylpyrrolidone in Pharmaceutical Formulations - Yu Luo; Yanlong Hong; Lan Shen; Fei Wu; Xiao Lin (AAPS PharmSciTech, 2021)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

One-pot synthesis of substituted pyrrole–imidazole derivatives with anticancer activity - Ming Zhang; Yong Ding; Hong-Xia Qin; Zhi-Gang Xu; Hai-Tao Lan; Dong-Lin Yang; Cheng Yi (Molecular Diversity, 2020)

Visible light-induced green synthesis of 2-amino-4H-chromenes - Lu Chen; Chuyuan Lin; Yongyin Lan; Zhenzhen Li; Dandan Huang; Wei Yang; Yibiao Li (Environmental Chemistry Letters, 2020)

Two new compounds from the heartwood of Dalbergia melanoxylon - Shuai Lin; Rong-Hua Liu; Guang-Qiang Ma; Dan-Yi Mei; Feng Shao; Lan-Ying Chen (Natural Product Research, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Apical ectodermal ridge regulates three principal axes of the developing limb - Guo-hao Lin; Lan Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

(–)-β-Homoarginine anhydride, a new antioxidant and tyrosinase inhibitor, and further active components from Trichosanthes truncata - I-Ting Weng; Yen-An Lin; Guan-Yu Chen; Hsiu-Mei Chiang; Yi-Jung Liu; Chao-Jung Chen; Yu-Hsuan Lan; Chia-Lin Lee (Natural Product Research, 2020)

Stem-Cell Therapy as a Potential Strategy for Radiation-Induced Brain Injury - Chengyan Chu; Yue Gao; Xiaoyan Lan; Jianwen Lin; Aline M. Thomas; Shen Li (Stem Cell Reviews and Reports, 2020)

Synergistic effects of pazopanib and hyperthermia against uterine leiomyosarcoma growth mediated by downregulation of histone acetyltransferase 1 - Chiao-Yun Lin; Angel Chao; Ren-Chin Wu; Li-Yu Lee; Shir-Hwa Ueng; Chia-Lung Tsai; Yun-Shien Lee; Meng-Ting Peng; Lan-Yan Yang; Huei-Jean Huang; Hsin-Shih Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2020)

Long-term influence of maize stover and its derived biochar on soil structure and organo-mineral complexes in Northeast China - Qiang Sun; Jun Meng; Binoy Sarkar; Yu Lan; Li Lin; Haifeng Li; Xu Yang; Tiexin Yang; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2020)

The Fundamental and Functional Property Differences Between HPMC and PVP Co-Processed Herbal Particles Prepared by Fluid Bed Coating - Zhe Li; Fei Wu; YanLong Hong; Lan Shen; Xiao Lin; Yi Feng (AAPS PharmSciTech, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

First report of Fusarium oxysporum f. sp. canariensis causing Fusarium wilt on Canary Island date palm (Phoenix canariensis Hort. Ex Chabaud) in China - Cheng Zhong Lan; Yu Li Dai; Lin Gan; Jin Ai Yao; Xiu Juan Yang (Journal of Plant Pathology, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Impacts of elevated temperature and pCO2 on the brooded larvae of Pocillopora damicornis from Luhuitou Reef, China: evidence for local acclimatization - Lei Jiang; Ming-Lan Guo; Fang Zhang; Yu-Yang Zhang; Guo-Wei Zhou; Xin-Ming Lei; Xiang-Cheng Yuan; You-Fang Sun; Tao Yuan; Lin Cai; Jian-Sheng Lian; Sheng Liu; et al. (Coral Reefs, 2020)

Application of artificial neural network (ANN) and response surface methodology (RSM) for modeling and optimization of the contact angle of rice leaf surfaces - Jiantao Zhang; Gengchun Lin; Xuanchun Yin; Jiajun Zeng; Sheng Wen; Yubin Lan (Acta Physiologiae Plantarum, 2020)

Novel dammarane-type saponins from Gynostemma pentaphyllum and their neuroprotective effect - Shao-Fang Xing; Man Lin; Yu-Rong Wang; Tuo Chang; Wei-Ye Cui; Xiang-Lan Piao (Natural Product Research, 2020)

The impact of oceanic processes on the transient climate response: a tidal forcing experiment - Yi Yu; Hailong Liu; Pengfei Lin; Jian Lan (Acta Oceanologica Sinica, 2020)

A Bregman adaptive sparse-spike deconvolution method in the frequency domain - Shu-Lin Pan; Ke Yan; Hai-Qiang Lan; Zi-Yu Qin (Applied Geophysics, 2019)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

A rapid loess mudflow triggered by the check dam failure in a bulldoze mountain area, Lanzhou, China - Fanyu Zhang; Binbin Yan; Xiaoming Feng; Hengxing Lan; Chao Kang; Xishan Lin; Xinghua Zhu; Wenguo Ma (Landslides, 2019)

Cornel iridoid glycoside induces autophagy to protect against tau oligomer neurotoxicity induced by the activation of glycogen synthase kinase-3β - Cuicui Yang; Xuelian Li; Li Zhang; Yali Li; Lin Li; Lan Zhang (Journal of Natural Medicines, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Analysis of the elemental spectral characteristics of single elemental capture spectrum log using Monte-Carlo simulation - Chang-Lin Lan; Xu-Wen Zhan; Hong-Liang Wu; Yi Zhang; Tong Liu; Zhou Feng; Tao Lv (Applied Geophysics, 2019)

Protein glycosylation: a promising way to modify the functional properties and extend the application in food system - Qing Zhang; Lin Li; Qiuyu Lan; Meili Li; Dingtao Wu; Hong Chen; Yaowen Liu; Derong Lin; Wen Qin; Zhiqing Zhang; Jiang Liu; Wenyu Yang (Critical Reviews in Food Science and Nutrition, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Steroid-Enriched Fraction of Achyranthes bidentata Protects Amyloid β Peptide 1–40-Induced Cognitive Dysfunction and Neuroinflammation in Rats - Li-Wei Lin; Fan-Hsuan Tsai; Wan-Cheng Lan; Yih-Dih Cheng; Sheng-Chi Lee; Chi-Rei Wu (Molecular Neurobiology, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Expression and localization of MrgprD in mouse intestinal tract - Chenxing Zhou; Jia Li; Lin Liu; Zongxiang Tang; Fengyi Wan; Lei Lan (Cell and Tissue Research, 2019)

A female attractant for the blue gum chalcid, Leptocybe invasa (Hymenoptera: Eulophidae), from host plant (DH 201-2: Eucalyptus grandis × Eucalyptus tereticornis) - Tao Ma; Laijiao Lan; Na Lin; Lifei Zheng; Zhaohui Sun; Yizhen Li; Xiujun Wen (Arthropod-Plant Interactions, 2019)

Dynamic expressions of hypothalamic genes regulate seasonal breeding in a natural rodent population - Dawei Wang; Ning Li; Lin Tian; Fei Ren; Zhengguang Li; Yan Chen; Lan Liu; Xiangfa Hu; Xuechang Zhang; Ying Song; Roelof A. Hut; Xiao‐Hui Liu (Molecular Ecology, 2019)
Seasonal breeding is a universal reproductive strategy in many animals. Hypothalamic genes, especially type 2 and 3 iodothyronine deiodinases ( Dio2 / 3 ), RFamide‐related peptide 3 ( Rfrp‐3 ), kisspeptin ( Kiss‐1 ) and gonadotropin‐releasing hormone ( GnRH ), are involved in a photoperiodic pathway that encodes seasonal signals from day length in many vertebrate species. However, the seasonal expression patterns of these genes in wild mammals are less studied. Here, we present a four‐year field investigation to reveal seasonal rhythm and age‐dependent reproductive activity in male Brandt's voles ( Lasiopodomys brandtii ) and to detect relationships among seasonal expression profiles of hypothalamic genes, testicular activity, age and annual day length. From breeding season (April) to nonbreeding season (October), adult male voles displayed a synchronous peak in gonadal activity with annual day length around summer solstice, which was jointly caused by age structure shifts and age‐dependent gonadal development patterns. Overwintered males maintained reproductive activity until late in the breeding season, whereas most newborn males terminated gonadal development completely, except for a minority of males born early in spring. Consistently, the synchronous and opposite expression profiles of Dio2/3 suggest their central function to decode photoperiodic signals and to predict the onset of the nonbreeding season. Moreover, changes in Dio2/3 signals may guide the actions of Kiss‐1 and Rfrp‐3 to regulate the age‐dependent divergence of reproductive strategy in wild Brandt's vole. Our results provide evidence on how hypothalamic photoperiod genes regulate seasonal breeding in a natural rodent population.

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Influence of design probe and sequence mismatches on the efficiency of fluorescent RPA - Xiaoqing Liu; Qiongying Yan; Jianfei Huang; Jing Chen; Zhengyang Guo; Zhongdong Liu; Lin Cai; Risheng Li; Yan Wang; Guowu Yang; Quanxue Lan (World Journal of Microbiology and Biotechnology, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

NMDA Receptor Antagonist MK801 Protects Against 1-Bromopropane-Induced Cognitive Dysfunction - Lin Xu; Xiaofei Qiu; Shuo Wang; Qingshan Wang; Xiu-Lan Zhao (Neuroscience Bulletin, 2019)

OsDCL3b affects grain yield and quality in rice - Peng-Fei Liao; Jie-Xiu Ouyang; Jian-Jun Zhang; Lan Yang; Xin Wang; Xiao-Jue Peng; Dong Wang; You-Lin Zhu; Shao-Bo Li (Plant Molecular Biology, 2019)

A new benzofuran from the heartwood of Dalbergia latifolia - Rong-Hua Liu; Dan-Yi Mei; Shuai Lin; Ding-Qing Wang; Feng Shao; Lan-Ying Chen; Shan-Liang Guo (Natural Product Research, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

Study on the bio-function of lipA gene in Aspergillus flavus - Wenzhao Bai; Tiejun Feng; Faxiu Lan; Guanglan Lin; Yu Li; Opemipo Esther Fasoyin; Yaju Liu; Kunzhi Jia (Genes & Genomics, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

α-Glucosidase inhibitory and cytotoxic botryorhodines from mangrove endophytic fungus Trichoderma sp. 307 - Liuhong Zhang; Shah Iram Niaz; Zhen Wang; Yonghong Zhu; Yongcheng Lin; Jing Li; Lan Liu (Natural Product Research, 2018)

Cytological and transcriptome analyses reveal abrupt gene expression for meiosis and saccharide metabolisms that associated with pollen abortion in autotetraploid rice - Lin Chen; Muhammad Qasim Shahid; Jinwen Wu; Zhixiong Chen; Lan Wang; Xiangdong Liu (Molecular Genetics and Genomics, 2018)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Clearance of Amyloid Beta and Tau in Alzheimer’s Disease: from Mechanisms to Therapy - Shu-Hui Xin; Lin Tan; Xipeng Cao; Jin-Tai Yu; Lan Tan (Neurotoxicity Research, 2018)

Small-world indices via network efficiency for brain networks from diffusion MRI - Lan Lin; Zhenrong Fu; Cong Jin; Miao Tian; Shuicai Wu (Experimental Brain Research, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Spatiotemporal variations of annual shallow soil temperature on the Tibetan Plateau during 1983–2013 - Fuxin Zhu; Lan Cuo; Yongxin Zhang; Jing-Jia Luo; Dennis P. Lettenmaier; Yumei Lin; Zhe Liu (Climate Dynamics, 2018)

The roles of the COX2/PGE2/EP axis in therapeutic resistance - Dali Tong; Qiuli Liu; Lin-ang Wang; Qiubo Xie; Jian Pang; Yiqiang Huang; Luofu Wang; Gaolei Liu; Dianzheng Zhang; Weihua Lan; Jun Jiang (Cancer and Metastasis Reviews, 2018)

Effects of Zinc Supplementation During In Vitro Maturation on Meiotic Maturation of Oocytes and Developmental Capacity in Yak - Xianrong Xiong; Daoliang Lan; Jian Li; Yaqiu Lin; Xiangdong Zi (Biological Trace Element Research, 2018)

Spatial-temporal characteristics of epilithic algae succession on artificial substrata in relation to water quality in Erhai Lake, Yunnan Province, China - Bo Lan; Hailan Li; Xianfen Xiang; Junjie Lin; Jing Yin; Shao Yang (Biologia, 2018)

Erratum to: Co-spray Drying with HPMC as a Platform to Improve Direct Compaction Properties of Various Tablet Fillers - JinZhi Li; LiJie Zhao; Xiao Lin; Lan Shen; Yi Feng (AAPS PharmSciTech, 2018)

Genome-wide association analysis of lead accumulation in maize - Xiongwei Zhao; Yajuan Liu; Wenmei Wu; Yuhua Li; Longxin Luo; Yuzhou Lan; Yanhua Cao; Zhiming Zhang; Shibin Gao; Guangsheng Yuan; Li Liu; Yaou Shen; et al. (Molecular Genetics and Genomics, 2018)

Anti-amyloidgenic and neurotrophic effects of tetrahydroxystilbene glucoside on a chronic mitochondrial dysfunction rat model induced by sodium azide - Ru-yi Zhang; Lan Zhang; Li Zhang; Yu-lan Wang; Lin Li (Journal of Natural Medicines, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Increased temperature mitigates the effects of ocean acidification on the calcification of juvenile Pocillopora damicornis, but at a cost - Lei Jiang; Fang Zhang; Ming-Lan Guo; Ya-Juan Guo; Yu-Yang Zhang; Guo-Wei Zhou; Lin Cai; Jian-Sheng Lian; Pei-Yuan Qian; Hui Huang (Coral Reefs, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

A new diaryl 1, 2-diketone from the heartwood of Dalbergia latifolia - Rong-hua Liu; Ding-qing Wang; Pu-zhao Zhang; Feng Shao; Lan-ying Chen; Hui-lian Huang; Shuai Lin (Natural Product Research, 2018)

Age- and gender-related differences of CPAP acceptance for obstructive sleep apnea syndrome in Taiwan - Yi-Chih Huang; Chou-Chin Lan; Yao-Kuang Wu; Wen-Lin Su; Mei-Chen Yang (Sleep and Biological Rhythms, 2018)

Association of MSI2 Gene Polymorphism with Age-at-Onset of Schizophrenia in a Chinese Population - Zhi-Lin Luan; Xiao-Hui Cui; Hu Xu; He-Yuan Lu; Yu-Yuan Li; Tian-Lan Lu; Dai Zhang (Neuroscience Bulletin, 2017)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Identification of two novel chicken GPR133 variants and their expression in different tissues - Kai Tian; Qihai Xiao; Xueyou Zhang; Xi Lan; Xiaoling Zhao; Yan Wang; Diyan Li; Huadong Yin; Lin Ye; Qing Zhu (Functional & Integrative Genomics, 2017)

Co-spray Drying with HPMC as a Platform to Improve Direct Compaction Properties of Various Tablet Fillers - JinZhi Li; LiJie Zhao; Xiao Lin; Lan Shen; Yi Feng (AAPS PharmSciTech, 2017)

The Study of Graph Measurements for Hub Identification in Multiple Parcellated Brain Networks of Healthy Older Adult - Cong Jin; Yi-Ping Chao; Lan Lin; Zhenrong Fu; Baiwen Zhang; Shuicai Wu (Journal of Medical and Biological Engineering, 2017)

The association study of nonsyndromic cleft lip with or without cleft palate identified risk variants of the $$\varvec{GLI3}$$ G L I 3 gene in a Chinese population - Yirui Wang; Yimin Sun; Yongqing Huang; Yongchu Pan; Bing Shi; Jian Ma; Lan Ma; Feifei Lan; Yuxi Zhou; Jiayu Shi; Jinfang Zhu; Hongbing Jiang; et al. (Journal of Genetics, 2017)

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effect of culture conditions on metabolites produced by the crinoid-derived fungus Aspergillus ruber 1017 - Yong-Fang Li; Xue-Bin Wu; Shah-Iram Niaz; Liu-Hong Zhang; Zhi-Jian Huang; Yong-Cheng Lin; Jing Li; Lan Liu (Natural Product Research, 2017)

A prospective study of mitochondrial DNA copy number and the risk of prostate cancer - Amy Moore; Qing Lan; Jonathan N. Hofmann; Chin-San Liu; Wen-Ling Cheng; Ta-Tsung Lin; Sonja I. Berndt (Cancer Causes & Control, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Detection of chlorophylls in spores of seven ferns - Mei-Hwei Tseng; Kuei-Huei Lin; Yi-Jia Huang; Ya-Lan Chang; Sheng-Cih Huang; Li-Yaung Kuo; Yao-Moan Huang (Journal of Plant Research, 2017)

Heme oxygenase-1 protects spinal cord neurons from hydrogen peroxide-induced apoptosis via suppression of Cdc42/MLK3/MKK7/JNK3 signaling - Siyuan Wang; Tao Zhang; Zhen Yang; Jianhua Lin; Bin Cai; Qingfeng Ke; Wenbin Lan; Jinxing Shi; Shiqiang Wu; Wenping Lin (Apoptosis, 2017)

New lasiodiplodins from mangrove endophytic fungus Lasiodiplodia sp. 318 # - Jiguo Huang; Jiayi Xu; Zhen Wang; Dilfaraz Khan; Shah Iram Niaz; Yonghong Zhu; Yongcheng Lin; Jing Li; Lan Liu (Natural Product Research, 2017)

Relation of Transcriptional Factors to the Expression and Activity of Cytochrome P450 and UDP-Glucuronosyltransferases 1A in Human Liver: Co-Expression Network Analysis - Shilong Zhong; Weichao Han; Chuqi Hou; Junjin Liu; Lili Wu; Menghua Liu; Zhi Liang; Haoming Lin; Lili Zhou; Shuwen Liu; Lan Tang (The AAPS Journal, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Cluster spacing optimization of multi-stage fracturing in horizontal shale gas wells based on stimulated reservoir volume evaluation - Ran Lin; Lan Ren; Jinzhou Zhao; Leize Wu; Yuanzhao Li (Arabian Journal of Geosciences, 2017)

The genetic relationship between Habo alkaline intrusion and its surrounding deposits, Yunnan Province, China: geological and S–Pb isotopic evidences - Zhongneng Meng; Qian Zhang; Lin Ye; Yupin Liu; Jiangbo Lan; Dapeng Wang (Acta Geochimica, 2016)

Influence of Florfenicol on the Treatment Effect of Intermittent Aeration Dynamic Membrane Bioreactors, and its Enhanced Removal Process Investigation - Xiang Wu; Hao Wu; Lin Mao; Lan Yu; Rongfei Zhang; Jinyun Ye (Water, Air, & Soil Pollution, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Cobalt Protoporphyrin Upregulates Cyclooxygenase-2 Expression Through a Heme Oxygenase-Independent Mechanism - Hsiao-Yun Lin; Chon-Haw Tsai; Chingju Lin; Wei-Lan Yeh; Cheng-Fang Tsai; Pei-Chun Chang; Ling-Hsuan Wu; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Repair process and enzymatic activity associated with induction of shell regeneration in the invasive species Pomacea canaliculata - Song Yang; Lin-kang Ni; Liu-lan Zhao; Jin-wei Yang; Qiao Liu; Jia-en Zhang; Zhi He; Shuang Peng (Molluscan Research, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Identification and characteristics analysis of toll-like receptors family genes in yak - Daoliang Lan; Baoshan Lin; Xianrong Xiong; Xiaonong Yang; Jian Li (Genes & Genomics, 2016)

Lasiodiplodins from mangrove endophytic fungus Lasiodiplodia sp. 318# - Jing Li; Yanyu Xue; Jie Yuan; Yongjun Lu; Xun Zhu; Yongcheng Lin; Lan Liu (Natural Product Research, 2016)

Erratum to: Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Naringenin Suppresses Neuroinflammatory Responses Through Inducing Suppressor of Cytokine Signaling 3 Expression - Ling-Hsuan Wu; Chingju Lin; Hsiao-Yun Lin; Yu-Shu Liu; Caren Yu-Ju Wu; Cheng-Fang Tsai; Pei-Chun Chang; Wei-Lan Yeh; Dah-Yuu Lu (Molecular Neurobiology, 2016)

Phosphocreatine protects against LPS-induced human umbilical vein endothelial cell apoptosis by regulating mitochondrial oxidative phosphorylation - Zhengwu Sun; Xiaoyan Lan; Anil Ahsan; Yalin Xi; Shumin Liu; Zonghui Zhang; Peng Chu; Yushu Song; Fengyuan Piao; Jinyong Peng; Yuan Lin; Guozhu Han; et al. (Apoptosis, 2016)

Niching sustainability in an Indigenous community: protected areas, autonomous initiatives, and negotiating power in natural resource management - Pei-Shan Sonia Lin; Yen-Lan Liu (Sustainability Science, 2016)

Spontaneous white matter lesion in brain of stroke-prone renovascular hypertensive rats: a study from MRI, pathology and behavior - Yuhua Fan; Linfang Lan; Lu Zheng; Xiaotan Ji; Jing Lin; Jinsheng Zeng; Ruxun Huang; Jian Sun (Metabolic Brain Disease, 2015)

Effect of combination of nerve fragments with nerve growth factor in autologous epineurium small gap coaptation on peripheral nerve injury repair - Bo Feng; Hua Ma; He Hu; Lan Zhang; Zhi Zhang; Youming Pang; Yongjun Wang; Kecheng Niu; Ligong Lin (Cell and Tissue Banking, 2015)

A Nampt inhibitor FK866 mimics vitamin B3 deficiency by causing senescence of human fibroblastic Hs68 cells via attenuation of NAD+-SIRT1 signaling - Tuzz-Ying Song; Shu-Lan Yeh; Miao-Lin Hu; Mei-Yau Chen; Nae-Cherng Yang (Biogerontology, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Introduction of telomerase reverse transcriptase gene into epidermal stem cells derived from human skins - Lian-Qun Wang; De-Wu Liu; Wei Lan; Zun-Wen Lin; Pei-Xing Huang (Tissue Engineering and Regenerative Medicine, 2015)

Estimation of hourly and daily photosynthetically active radiation in Inner Mongolia, China, from 1990 to 2012 - Lunche Wang; Wei Gong; Lan Feng; Aiwen Lin; Bo Hu; Min Zhou (International Journal of Climatology, 2015)
Measurements of photosynthetically active radiation ( PAR ) in Inner Mongolia, China, from 2005 to 2012 were used to investigate its relationship with global solar radiation ( G ) under various sky conditions. Monthly mean daily PAR generally increased from 13.98 mol m −2 d −1 in December to 40.48 mol m −2 d −1 in June with annual mean value being 29.02 mol m −2 d −1 . Monthly daily F p (ratio of PAR to G) increased from 1.68 mol MJ ‐1 in December to 1.88 mol MJ ‐1 in August with annual average of 1.80 mol MJ ‐1 . Clearness index ( K t ) was used for characterizing sky conditions and it was discovered that clear skies (49.4%) were the dominated sky conditions. By studying the dependence of PAR on optical air mass, K t and cosine of solar zenith angle, two different models have been introduced and tested at four other sites in China. The model performances have been analysed and the daily PAR values during 1990–2012 at Inner Mongolia, China, have been reconstructed. It was found that PAR increased at the rate of 0.54 mol m −2 d −1 decade ‐1 since 1990 and the most evident increases were observed in summer (1.96 mol m −2 d −1 decade ‐1 ). However, PAR decreased at the rate of ‐0.37 mol m −2 d −1 decade ‐1 in spring during 1990–2012.

Two new macrosporin dimers from the fungus Alternaria sp. XZSBG-1 - Bin Chen; Lan Liu; Xun Zhu; Jun Wang; Yi Long; Si-Ping Jiang; Ai-Guo Xu; Yong-Cheng Lin (Natural Product Research, 2015)

Estimation of hourly and daily ultraviolet solar irradiation under various sky conditions at Sanya, Southern China - Lan Feng; Lunche Wang; Wei Gong; Aiwen Lin; Bo Hu (Theoretical and Applied Climatology, 2015)

Structural transformation of oyster, hard clam, and sea urchin shells after calcination and their antibacterial activity against foodborne microorganisms - Yu-Chun Chen; Chun-Lan Lin; Chih-Ting Li; Deng-Fwu Hwang (Fisheries Science, 2015)

Causes and Consequences of MicroRNA Dysregulation in Neurodegenerative Diseases - Lin Tan; Jin-Tai Yu; Lan Tan (Molecular Neurobiology, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Investigation of the hazardous substance causing crayfish-induced rhabdomyolysis via a mouse model, a hemolysis assay, and a cytotoxicity assay - Xiao-Feng Chen; Jiang-Wei Lin; Tzu-Ming Pan; Min-Jie Cao; Chao-Lan Shi; Qiu-Feng Cai; Guang-Ming Liu (Fisheries Science, 2015)

Myo10 is required for neurogenic cell adhesion and migration - Huali Yu; Mingming Lai; Yuguang Guo; Lin Yuan; Yongsheng Lan; Xingzhi Wang; Xiaojuan Zhu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Influence of Val108/158Met COMT Gene Polymorphism on the Efficacy of Modified Electroconvulsive Therapy in Patients with Treatment Resistant Depression - Zhaoyu Lin; Hongbo He; Chunping Zhang; Zhijie Wang; Miaoling Jiang; Qirong Li; Xiaochang Lan; Minling Zhang; Xiong Huang (Cell Biochemistry and Biophysics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Seasonal characteristics and tetrodotoxin-producing ability of bacteria in gastropod Oliva hirasei - Chun-Lan Lin; Ya-Jung Wu; Wen-Feng Lin; Cheng-Hong Hsieh; You-Liang Hsieh; Deng-Fwu Hwang (Hydrobiologia, 2014)

TGFβ can stimulate the p38/β-catenin/PPARγ signaling pathway to promote the EMT, invasion and migration of non-small cell lung cancer (H460 cells) - Li-Chiung Lin; Shih-Lan Hsu; Chieh-Liang Wu; Chi-Mei Hsueh (Clinical & Experimental Metastasis, 2014)

Expression of the HPV18E2 Gene in Cervical Cancer and Premalignant Lesions and its Clinical Significance - Ling Mou; Bin Wu; Ya Hu; Ying Lan; Feng-Lin Lv (Cell Biochemistry and Biophysics, 2014)

The role of Mss11 in Candida albicans biofilm formation - Pei-Wen Tsai; Yu-Ting Chen; Cheng-Yao Yang; Hsueh-Fen Chen; Te-Sheng Tan; Tzung-Wei Lin; Wen-Ping Hsieh; Chung-Yu Lan (Molecular Genetics and Genomics, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Three-dimensional reconstruction method for measuring the knee valgus angle of the femur in northern Chinese adults - Tong Liu; Chen-yu Wang; Jian-lin Xiao; Lan-yu Zhu; Xue-zhou Li; Yan-guo Qin; Zhong-li Gao (Journal of Zhejiang University-SCIENCE B, 2014)

GRP78 expression and regulation in the mouse uterus during embryo implantation - PengFei Lin; YaPing Jin; XiangLi Lan; YanZhou Yang; Fenglei Chen; Nan Wang; Xiao Li; YuJie Sun; AiHua Wang (Journal of Molecular Histology, 2014)

Tomato plant growth promotion and antibacterial related-mechanisms of four rhizobacterial Bacillus strains against Ralstonia solanacearum - Abdulwareth A. Almoneafy; Kaleem Ullah Kakar; Zarqa Nawaz; Bin Li; Mumtaz Ali saand; Yang Chun-lan; Guan-Lin Xie (Symbiosis, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Profiling of differentially expressed genes in ectomycorrhizal fungus Pisolithus tinctorius responding to mycorrhiza helper Brevibacillus reuszeri MPt17 - Ai-Dong Zhou; Xiao-Qin Wu; Lan Shen; Xu-Ling Xu; Lin Huang; Jian-Ren Ye (Biologia, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Changes in land use and agricultural production structure before and after the implementation of grain for green program in Western China — taking two typical counties as examples - Ping Zhou; An-bang Wen; Dong-chun Yan; Zhong-lin Shi; Jin Guo; Zhan-sheng Ju; Yi-lan Zhang (Journal of Mountain Science, 2014)

Anti-neuroinflammatory Effect of a Novel Caffeamide Derivative, KS370G, in Microglial cells - Dah-Yuu Lu; Bor-Ren Huang; Wei-Lan Yeh; Hsiao-Yun Lin; Shiang-Suo Huang; Yu-Shu Liu; Yueh-Hsiung Kuo (Molecular Neurobiology, 2013)

Synthesis, characterization, and DNA binding of a novel ligand and its Cu(II) complex - Mei-Jin Li; Tao-Yu Lan; Zhi-Shan Lin; Changqing Yi; Guo-Nan Chen (JBIC Journal of Biological Inorganic Chemistry, 2013)

Transcriptional responses of maize seedling root to phosphorus starvation - Hai-Jian Lin; Jian Gao; Zhi-Ming Zhang; Ya-Ou Shen; Hai Lan; Li Liu; Kui Xiang; Maojun Zhao; Shufeng Zhou; Yong-Zhong Zhang; Shi-Bin Gao; Guang-Tang Pan (Molecular Biology Reports, 2013)

Identification and Characterization of an Extracellular Alkaline Phosphatase in the Marine Diatom Phaeodactylum tricornutum - Hung-Yun Lin; Chi-Yu Shih; Hung-Chun Liu; Jeng Chang; Ying-Lan Chen; Yet-Ran Chen; Han-Tso Lin; Yu-Yung Chang; Chun-Hua Hsu; Han-Jia Lin (Marine Biotechnology, 2013)

Distribution and temporal trend of polybrominated diphenyl ethers in one Shanghai municipal landfill, China - Kai Huang; Jie Guo; Kuang-fei Lin; Xiao-yu Zhou; Jun-xia Wang; Peng Zhou; Feng Xu; Mei-Lan Zhang (Environmental Science and Pollution Research, 2013)

Indole-3-Acetic Acid Production by Endophytic Streptomyces sp. En-1 Isolated from Medicinal Plants - Lan Lin; Xudong Xu (Current Microbiology, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Structural controls on coalbed methane reservoirs in Faer coal mine, Southwest China - Ming Li; Bo Jiang; Shoufa Lin; Fengjuan Lan; Jilin Wang (Journal of Earth Science, 2013)

High density of IL-17-producing cells is associated with improved prognosis for advanced epithelial ovarian cancer - Chunyan Lan; Xin Huang; Suxia Lin; Huiqiang Huang; Qichun Cai; Jiabin Lu; Jihong Liu (Cell and Tissue Research, 2013)

Wogonin enhances antitumor activity of tumor necrosis factor-related apoptosis-inducing ligand in vivo through ROS-mediated downregulation of cFLIPL and IAP proteins - Lan Yang; Qiong Wang; Daoxia Li; Yuqiong Zhou; Xuelian Zheng; Hong Sun; Jiaqi Yan; Lin Zhang; Yong Lin; Xia Wang (Apoptosis, 2013)

An Adaptation Due to Climate Change in Southwest Coast of Taiwan - Yuan-Jyh Lan; Tai-Wen Hsu; Yue-Chen Lin; Ching-Jer Huang (Coastal Management, 2013)

Standard spectrum measurement and simulation of elemental capture spectroscopy log - Hong-Liang Wu; Ning Li; Chang-Lin Lan; Xiang-Zhong Kong; Hua Chai (Applied Geophysics, 2013)

Non-coding RNAs in Alzheimer's Disease - Lin Tan; Jin-Tai Yu; Nan Hu; Lan Tan (Molecular Neurobiology, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Abnormal concentration and origin of heavy hydrocarbon in upper permian coal seams from Enhong syncline, Yunnan, China - Fengjuan Lan; Yong Qin; Ming Li; Yucheng Lin; Aikuan Wang; Jian Shen (Journal of Earth Science, 2012)

Effect of Sulfate Availability on the Isotopic Signature of Reduced Sulfurous Compounds in the Sediments of a Subtropical Estuary - Lan-Feng Fan; Saulwood Lin; Wei-Gang He; Kuo-Ming Huang; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

Structural and functional conservation of CLEC-2 with the species-specific regulation of transcript expression in evolution - Lan Wang; Shifang Ren; Haiyan Zhu; Dongmei Zhang; Yuqing Hao; Yuanyuan Ruan; Lei Zhou; Chiayu Lee; Lin Qiu; Xiaojing Yun; Jianhui Xie (Glycoconjugate Journal, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Novel phosphatidylinositol 3-kinase inhibitor NVP-BKM120 induces apoptosis in myeloma cells and shows synergistic anti-myeloma activity with dexamethasone - Yuhuan Zheng; Jing Yang; Jianfei Qian; Liang Zhang; Yong Lu; Haiyan Li; Heather Lin; Yongsheng Lan; Zhiqiang Liu; Jin He; Sungyoul Hong; Sheeba Thomas; et al. (Journal of Molecular Medicine, 2012)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

Mortality in a Chinese chrysotile miner cohort - Xiaorong Wang; Sihao Lin; Eiji Yano; Hong Qiu; Igtanius T. S. Yu; Lapah Tse; Yajia Lan; Mianzhen Wang (International Archives of Occupational and Environmental Health, 2012)

Quasi-stationary planetary wave-mean flow interactions in the Northern Hemisphere stratosphere and their responses to ENSO events - XiaoQing Lan; Wen Chen; Lin Wang (Science China Earth Sciences, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Cordyceps cicadae extracts ameliorate renal malfunction in a remnant kidney model - Rong Zhu; Yi-ping Chen; Yue-yi Deng; Rong Zheng; Yi-fei Zhong; Lin Wang; Lan-ping Du (Journal of Zhejiang University-SCIENCE B, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Modulation of endogenous peroxidase by exogenous peroxidase in chinese red radish seedling - Li Wang; Lan Wang; Fang-Jun Li; Lin-Song Wang; Myeong-Hyeon Wang (Horticulture, Environment, and Biotechnology, 2011)

Invasion of the African sharp-tooth catfish Clarias gariepinus (Burchell, 1822) in South China - K. V. Radhakrishnan; Zhao Jun Lan; Jun Zhao; Ning Qing; Xio Lin Huang (Biological Invasions, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Cytotoxicity, apoptosis-inducing effects and structure-activity relationships of four natural xanthones from Gentianopsis paludosa Ma in HepG2 and HL-60 cells - Lan Ding; Bo Liu; Shi-dong Zhang; Qian Hou; Lin-lin Qi; Qi-yin Zhou (Natural Product Research, 2011)

Production of reactive oxygen species and induction of signaling pathways for the ACO gene expressions in tomato plants triggered by the volatile organic compound ether - Kuo-Chih Lin; Pi-Chi Sun; Pei-Lan Lin (Plant Cell Reports, 2011)

Characterization of a ZmSERK gene and its relationship to somatic embryogenesis in a maize culture - Suzhi Zhang; Xinggui Liu; Yueai Lin; Guangning Xie; Fengling Fu; Hailan Liu; Jing Wang; Shibin Gao; Hai Lan; Tingzhao Rong (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

An intelligent electronic capsule system for automated detection of gastrointestinal bleeding - Hong-ying Liu; Gang Wang; Kang Wei; Xi-tian Pi; Lan Zhu; Xiao-lin Zheng; Zhi-yu Wen (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic polymorphisms of the DNA repair geneMPG may be associated with susceptibility to rheumatoid arthritis - S. Y. Chen; L. Wan; C. M. Huang; Y. C. Huang; J. J. C. Sheu; Y. J. Lin; S. P. Liu; Y. C. Lan; C. H. Lai; C. W. Lin; C. H. Tsai; F. J. Tsai (Journal of Applied Genetics, 2010)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Simple monitoring method for precaution of landslides watching tilting and water contents on slopes surface - Taro Uchimura; Ikuo Towhata; Trinh Thi Lan Anh; Jou Fukuda; Carlos J. B. Bautista; Lin Wang; Ichiro Seko; Taro Uchida; Akira Matsuoka; Yosuke Ito; Yuichi Onda; Sho Iwagami; et al. (Landslides, 2010)

Responses of soil chemical and biological properties to nitrogen addition in a Dahurian larch plantation in Northeast China - Ya-Lin Hu; De-Hui Zeng; Yun-Xia Liu; Yu-Lan Zhang; Zhen-Hua Chen; Zheng-Quan Wang (Plant and Soil, 2010)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

FORMOSAT-3/COSMIC observations of the ionospheric auroral oval development - Ho-Fang Tsai; Jann-Yenq Liu; Chien-Hung Lin; Mei-Lan Hsu (GPS Solutions, 2010)

Evidence for marine transgression between 7500–5400BC at the Luotuodun Site in Yixing, Jiangsu Province - Lan Li; Cheng Zhu; Liugen Lin; Quanhong Zhao; Gongyue Shi; Chaogui Zheng; Chao Fan (Journal of Geographical Sciences, 2009)

Multicentre evaluation of the Elecsys® hepatitis B surface antigen II assay for detection of HBsAg in comparison with other commercially available assays - Ji-Dong Jia; Ma Hong; Lai Wei; Xin-Xin Zhang; Yuan-Li Mao; Lan-Lan Wang; Zhi-Liang Gao; Jin-Lin Hou; Jun Zhang (Medical Microbiology and Immunology, 2009)

Light acclimation and HSO3 − damage on photosynthetic apparatus of three subtropical forest species - Nan Liu; Zhi-Fang Lin; Lan-Lan Guan; Gui-Zhu Lin; Chang-Lian Peng (Ecotoxicology, 2009)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

EGb761 Protects Hydrogen Peroxide-induced Death of Spinal Cord Neurons through Inhibition of Intracellular ROS Production and Modulation of Apoptotic Regulating Genes - Xiaoyan Jiang; Baoming Nie; Saili Fu; Jianguo Hu; Lan Yin; Lin Lin; Xiaofei Wang; Peihua Lu; Xiao-Ming Xu (Journal of Molecular Neuroscience, 2009)

Effects of three phthalate esters on the life-table demography of freshwater rotifer Brachionus calyciflorus Pallas - Lan-Lan Zhao; Yi-Long Xi; Lin Huang; Chun-Wang Zha (Aquatic Ecology, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Pc4, a putative movement protein of Rice stripe virus, interacts with a type I DnaJ protein and a small Hsp of rice - Lianming Lu; Zhenguo Du; Meiling Qin; Ping Wang; Hanhong Lan; Xiaoqing Niu; Dongsheng Jia; Liyan Xie; Qiying Lin; Lianhui Xie; Zujian Wu (Virus Genes, 2009)

High-frequency direct somatic embryogenesis from leaf tissues of Drimiopsis kirkii Baker (giant squill) - T. H. Lan; P. I. Hong; C. C. Huang; W. C. Chang; C. S. Lin (In Vitro Cellular & Developmental Biology - Plant, 2009)

Cloning and sequence analysis of the gene encoding 19-kD subunit of Complex I from Dunaliella salina - Yi Liu; Dai Rong Qiao; Hong Bo Zheng; Xu Lan Dai; Lin Han Bai; Jing Zeng; Yi Cao (Molecular Biology Reports, 2008)

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Lin-Li Xie; Ya-Chao Qin; Charles Q. Cheng (Biological Trace Element Research, 2008)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

A further investigation of the decadal variation of ENSO characteristics with instability analysis - Xiangfeng Meng; Dexing Wu; Xiaopei Lin; Jian Lan (Advances in Atmospheric Sciences, 2006)

Investigation of iodine concentration in salt, water and soil along the coast of Zhejiang, China - Ying-li Lu; Ning-jian Wang; Lan Zhu; Guo-xing Wang; Hui Wu; Lin Kuang; Wen-ming Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

Production of 2-(2-phenylethyl) Chromones in Cell Suspension Cultures of Aquilaria sinensis - Shu-Yuan Qi; Meng-Ling He; Li-Dong Lin; Chuan-Hai Zhang; Lan-Juan Hu; Hui-Zhen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Measurement of chlorophyll fluorescence reveals mechanisms for habitat niche separation of the intertidal seagrasses Thalassia hemprichii and Halodule uninervis - Chiu-Yueh Lan; Wen-Yuan Kao; Hsing-Juh Lin; Kwang-Tsao Shao (Marine Biology, 2005)

Role of withdrawal in reinstatement of morphine-conditioned place preference - Lin Lu; Hai Chen; Wenjuan Su; Xin Ge; Wen Yue; Fen Su; Lan Ma (Psychopharmacology, 2005)

An Amplification Mechanism of Intraseasonal Long Rossby Wave in Subtropical Ocean - Xiaopei Lin; Dexing Wu; Qiang Li; Jian Lan (Journal of Oceanography, 2005)

Nucleotide Sequences and Functions of the Epstein-Barr Virus Latent Membrane Protein 1 Genes Isolated from Salivary Gland Lymphoepithelial Carcinomas - Kai Yu Jen; Masaya Higuchi; Jun Cheng; Jiang Li; Lan Yan Wu; Ying Fang Li; Han Liang Lin; Zhilong Chen; Vladimir Gurtsevitch; Masahiro Fujii; Takashi Saku (Virus Genes, 2005)

Purification and some properties of ?-N-acetyl-D-glucosaminidase from prawn (Penaeus vannamei) - Xiao-Lan Xie; Qing-Xi Chen; Jian-Cheng Lin; Yue Wang (Marine Biology, 2004)

Spatial and temporal dynamics of soil organic carbon in reserved desertification area - Shu-lan Cheng; Hua Ouyang; Hai-shan Niu; Lin Wang; Feng Zhang; Jun-qin Gao; Yu-qiang Tian (Chinese Geographical Science, 2004)

Acute Aquatic Toxicity of N-Methyl-2-Pyrrolidinone to Daphnia magna - C.-H. Lan; C.-Y. Peng; T.-S. Lin (Bulletin of Environmental Contamination and Toxicology, 2004)

RAPD markers in diversity detection and variety identification of Tibetan hulless barley - Zeng Yu; Lan Li-Qiong; Luo Huan; Bai Jie; Yang Man-Ye; Miao Chen; Cai Ying-Fan; Qiang Xiao-Lin; Chen Fang (Plant Molecular Biology Reporter, 2002)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)

Reactivation of morphine conditioned place preference by drug priming: role of environmental cues and sensitization - Lin Lu; Nan-Jie Xu; Xin Ge; Wen Yue; Wen-Juan Su; Gang Pei; Lan Ma (Psychopharmacology, 2002)

Inhibitory effect of esculetin on oxidative damage induced by t -butyl hydroperoxide in rat liver - Wea-Lung Lin; Chau-Jong Wang; Yu-Ying Tsai; Chuen-Lan Liu; Jin-Ming Hwang; Tsui-Hwa Tseng (Archives of Toxicology, 2000)

The Arterial Supply of the Cubital Joint in the Bactrian Camel (Camelus bactrianus) - Jian-Lin Wang; Gao-Lan; Cui-Sheng; Gen-Xuan Wang; Hai-Yan Li (Veterinary Research Communications, 2000)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)